Integrating UAV-derived enhanced disease detection index and texture features for monitoring southern corn rust severity - Yanan Wei; Qing Li; Jia Yin; Dalei Hao; Renan Caldas Umburanas; Yongyuan Gao; Weijian Yu; Zhixiong Li; Yachang He; Guanyu Qiao; Yu Zhang; Carlos Camino; et al. (Computers and Electronics in Agriculture, 2026)

Long-term impact of 3-D urban expansion on the thermal environment in the Yangtze River Delta region, China - Chenglong Yin; Ruishan Chen; Xiangming Xiao; Yi Yin; Tim Van de Voorde; Yinshuai Li; Nan Jia; Hong Wei; Li Pan; Fei Meng; Yanbin Chen; Bo Xiong; et al. (Land Use Policy, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

A SASP-related four-gene signature associated with intervertebral disc degeneration: integrated bioinformatics analysis and validation of pinocembrin as a therapeutic candidate - Ge-Liang Yao; Shi-Jiang Wang; Ying Zhang; Jia-Ming Liu; Hong-Hai Song; Zhi-Li Liu (Molecular Biology Reports, 2026)

miR-133b induces antitumor immunity in cervical cancer through modulating CMTM6/PD-L1 axis - Wei-Ming Tan; Jia-Qi Wang; Li Li; Xu-Ji Liu; Hong-Bing Wang; Hui Zeng (Molecular Genetics and Genomics, 2026)

A multistage cost-effective strategy for the molecular diagnosis of unexplained vision loss patients: practice in inherited ocular fundus disease - Junyi Wang; Jia Li; Limeng Dai; Xintong Zhu; Yanling Long; Xiaohong Meng; Shiying Li; Xiaoyong Huang; Hong Guo (Molecular Genetics and Genomics, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

Towards physically consistent prediction of groundwater salinization in coastal reclamation areas: A novel PMF-weighted SHAP framework - Zhengyang Jia; Hui Yu; Hai Yang; Zi Chen; Enping Xie; Lili Hou; Hong Zhang; Yun Li; Xuan Yu (Water Research, 2026)

Selective depression of calcite by sodium phytate in the flotation separation of smithsonite from calcite under an Al-BHA-NaOL collector system - Hongqin Chen; Yanhai Shao; Xiao Meng; Jinhui Li; Xinru Jia; Hong Lin; Chengxiang Li (Minerals Engineering, 2026)

Global, regional, and national burden of schizophrenia and its environmental drivers, 1990-2021: Retrospective analysis and projections to 2040 - Yixin Liu; Xiangyu Fan; Jiayue Yu; Shaonan Tong; Ying Sun; Pu Lei; Liangjia Wang; Min Jia; Xiancang Ma; Lichun Qiao; Peiqi Lu; Hong Li; et al. (Journal of Environmental Sciences, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

Superior removal of phthalate acid esters from water using a magnetic PIM-1 adsorbent - Ruobing Jia; Shunying Li; Keda Guo; Shiqi Yang; Yingying Zhang; Qiangqiang Xu; Hong Ye; Hehe Li; Shuangyang Li; Shengpeng Shi (Chemical Engineering Journal, 2026)

Structural stability and capacity fading mechanisms in titanium niobium oxides as anodes of lithium-ion batteries - Yang Li; Zhenxun Tang; Dongwei Ma; Kai Zhang; Jia Hong Pan (Chemical Engineering Journal, 2026)

Cross-species assembly of optimal isomerases DbZISO and DsCRTISO enhances all-trans-lycopene production in engineered E. coli - Jia-Yi Jiang; Shui-Feng Li; Jia-Yuan Luo; Jv-Liang Dai; Hao-Hong Chen; Jian-Guo Jiang (Bioresource Technology, 2026)

Aggregation-induced dual-emission carbon dots for visual discrimination of methanol from ethanol - Hui-Shuang Li; Cheng-Feng Zhang; Li-Jia Liu; Hong-Wei Li; Fuquan Bai; Yuqing Wu (Analytica Chimica Acta, 2026)

Integrated dual-mode analytical device combining gas pressure and distance readout for rapid analysis of urea - Linghuan Li; Yuanyuan He; Xiangyue Zeng; Dali Zhuo; Xiaoyu Dong; Hong Luo; Jia Liu; Shu Zhang; Zhirong Zou (Analytica Chimica Acta, 2026)

Genome mining of Trp-anthranilic acid cyclic dipeptides in Aspergillus driven by analysis of NRPS adenylation domains - Hua-Wei Lv; Zhi-Yan Zhang; Jia-Gui Tang; Meng-Di Zhu; Bin Wei; Mahmoud Emam; Hong Wang; Xing-Nuo Li (Archives of Microbiology, 2026)

Dietary selenium supplementation can serve as a strategy to counteract the DHA reduction in fish caused by replacing fish oil with linseed oil - Xiangtong Yuan; Feng Chen; Luyao Jia; Yuming Lai; Handong Li; Jian Sun; Hong Ji (Aquaculture, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

Machine learning-integrated multi-objective application and optimization framework for sulfur-based reactive filler towards nutrient removal - Jia-Min Xu; Jia-Qiang Lv; Wen-Ke He; Hong-Cheng Wang; Xiang-Li Zeng; Yu-Qi Wang; Wan-Xin Yin; Fang Huang; Gui-Jiao Zhang; Heng Dong; Yanchen Liu; Aijie Wang; et al. (Water Research, 2026)

Corrigendum to “A case study of Lepiota brunneoincarnata poisoning with endoscopic nasobiliary drainage in Shandong, China” [Toxicon 161C (2019) 12-16] - Jian Sun; Hong-Shun Zhang; Hai-Jiao Li; Yi-Zhe Zhang; Qian He; Jun-Jia Lu; Yu Yin; Cheng-Ye Sun (Toxicon, 2026)

Physicochemical pretreatment for enhancing anammox and related coupled processes in the treatment of high-strength ammonium industrial wastewater: Research advances and prospects - Long Jiao; Xue-chao Wang; Jia-lin Xue; Zhuo-yuan You; Jie Li; Jia-jun Fu; Hong Yu (Journal of Environmental Chemical Engineering, 2026)

Boride-derived catalysts for hydrogen evolution: Precursor-controlled reconstruction toward M-Co(OH)2 and M-Ni(OH)2 active phases and their application in Al-H2O batteries - Chen Chen; Zhenyu Wang; Yasen Li; Jiayao Gao; Xin Chen; Mingjie Jia; Die Shao; Yiming Wang; Xuejian Li; Fuqiang Yu; Guangwen Xu; Junli Xu; et al. (Journal of Environmental Chemical Engineering, 2026)

Identification and formation pathways of oxidation products of chlorinated paraffins during ozonation in municipal wastewater - Enrui Li; Hongping Wang; Yibin Sun; Song Tang; Chao Wang; Yi Wan; Xudong Jia; Hong Chang (Journal of Environmental Sciences, 2026)

Enhancing wheat yield through improved sowing uniformity in China: A meta-analysis - Peiyin Jia; Jing-Wei Fan; Xin-Mao Li; Chu-Yi Sun; Jairo A. Palta; Hong Zhao; Wen-Yuan Luo; Lan Yang; Jian Zhang; Feng-Min Li; Yan-Lei Du (Field Crops Research, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Nori and kelp intake attenuates antibiotic-induced gut dysbiosis and resistome expansion - Shilin Hu; Jin-Feng Xi; Tian Liang; Jia-Yang Xu; Ying-Xin Xue; Xin-Wei Yu; Jing-Jing Peng; Hong-Bo Li; Xi-Mei Xue (Journal of Environmental Sciences, 2026)

Making Waves: Emerging Risks as Regulatory Mismatch Meets Automation in LLM-Agents like OpenClaw for Water Treatment and Environmental Infrastructure - Yu-Qi Wang; Boyan Xu; Hao-Lin Yang; Jia-Ji Chen; He-Wen Li; Wen-Zhe Wang; Hong-Cheng Wang (Water Research, 2026)

The ATP-binding cassette (ABC) transporter YbiT deficient mutant of Riemerella anatipestifer displays attenuation and confers promoting immune protection in geese - Hong Li; Chihuan Li; Siping Zhu; Xintong Zhu; Chao Ren; Zhixin Zhu; Guowang Chen; Tonglei Wu; Qinghui Jia; Li Chen; Yonghui Li; Zhiqiang Zhang (Veterinary Microbiology, 2026)

Development of a gravity-driven self-centering rubber bearing for seismic isolation - Hong-Tai Zhang; Bing Zhao; Ping Xiang; Xue-Bin Ren; Yang Li; Li-Sheng Luo; Liang-Jiu Jia (Soil Dynamics and Earthquake Engineering, 2026)

Installation-induced long-term settlement of jacked piles in marine soft clay: Field investigation and analytical framework - Xibin Li; Huanhuan Hong; Xianlin Jia; Yong Zhao; Linfei Zhang (Ocean Engineering, 2026)

Unveiling strong microclimatic cooling by small wetlands in China: landscape context-dependent spatial and climatic drivers - Yue Jia; Wen J. Wang; Shengjie Ba; Yuyu Zhou; Tianxing He; Suri G. Bao; Paolo Cherubini; Zhihua Liu; Mai He Li; Yeqiao Wang; Hong S. He (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

From outcrossing to reproductive assurance: Seasonal plasticity in the breeding system of bi-seasonal flowering Tamarix ramosissima Ledeb. (Tamaricaceae) - Meng-Yuan Zhang; Jia-Hui Leng; Hong-Ju Cui; Jun-Xue Shi; Yuan-yuan Li; Xiang Shi (Flora, 2026)

Titanate-functionalized separator enables an in-situ redox reaction toward intrinsically dendrite-free aqueous zinc-ion batteries - Tong Jiang; You Fu; Zhenyu Wang; Siqinhaolu Hao; Yaxin Li; Zilong Liu; Mingjie Jia; Yongjian Ai; Yinggang Jia; Guangwen Xu; Hong-bin Sun (Chemical Engineering Journal, 2026)

Electrochemical induced in situ biogas upgrading and nitrogen removal during anaerobic digestion of food waste hydrolysate - Weiyao Huang; Siman Yang; Ze Zhao; Feng Ju; Lei Huang; Meng Li; Hongguo Zhang; Jiaqi Yan; Yunmin Zhong; Xuanxian Liao; Shuyuan Hong; Yue Huang; et al. (Bioresource Technology Reports, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

A new dipeptide from entomogenous fungus Metapochonia suchlasporia Y9 - Hong-Yan Yang; Jia-Qian Yang; Zhi-Pu Huang; Ke-Tao Zhang; Xin-Yi Chen; Jin-Li Zhao; Yan Wang; Qing Zhao; Xiao-Mei Zhang (Natural Product Research, 2026)

Three new ent -kaurene diterpenoid glucosides from the flowers of Inula japonica Thunb. - Zheng Niu; Jia-Qi Chen; Guan-Ke Liu; Li-Qin Ding; Chun-Yan Chen; Bing-Yang Zhang; Yu-Hong Li; De-Qin Zhang; Tie Yao; Feng Qiu (Natural Product Research, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Formulation and biological evaluation of a Perilla frutescens seed oil nanoemulsion: A novel therapeutic agent for alleviating gut-liver axis inflammation - Jia-Yu Ye; Wei Zhang; Mei Qin; Hong-Jie Cui; Jian Li (Research in Veterinary Science, 2026)

The soybean gene GmSP1L-8 improves salt tolerance through the enhancement of the ROS scavenging system - Hui-Bing Mou; Shuang Jiao; Xiang-Min Zheng; Xiao-Hong Liu; Zhuo Li; Jia-Ning Xun; Ke Zhao; Xianzhong Feng; Hong Zhai; Xi Bai (Plant Science, 2026)

Fusarielins Q–Y: fusarielin polyketides from Fusarium asiaticum QA-6 inhabiting the roots of the cultivated Artemisia argyi and their antibacterial activity against aquatic pathogens - Xiao-Shan Shi; Sui-Qun Yang; Yu-Liang Dong; Xiao-Ming Li; Ling-Hong Meng; Yan-He Li; Dun-Jia Wang; Xing-Wang Zhou; Bin-Gui Wang (Phytochemistry, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Summer thermal heterogeneity and overheating risk among older adults in elderly care facilities in the severe cold region of China - Jia Li; Bolun Zhao; Mohd Farid Mohamed; Wardah Fatimah Mohammad Yusoff; Yu Hong; Yili Guo (Building and Environment, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

Continuous Planting Reshapes Root Endophytic Microbes and Drives Growth Decline in Casuarina equisetifolia - Lei Hong; Yuhua Wang; Mingzhe Li; Jianjuan Li; Qingxu Zhang; Miaoen Qiu; Xiaoli Jia; Qingui Su; Wenxiong Lin; Haibin Wang; Zeyan Wu (Indian Journal of Microbiology, 2026)

Biochemical and multi-omics analyses reveal skeletal muscle adaptation to chronic low-salinity stress of marine medaka (Oryzias melastigma) - Tian-Hong Chen; Qing-Hao Zhan; Xiao-Yu Zeng; Ning-Ning Ma; Qi-Liang Li; Run-Jie Jin; Jia-Lang Zheng; Qing-Ling Zhu (Fish Physiology and Biochemistry, 2026)

Endothelial VEGFR2 insufficiency promotes the transition of lymphatic to hematopoietic transcriptional programs - Taotao Li; Xudong Cao; Fei Zhou; Xiujuan Li; Wenjuan Ma; Xiuyan Zhang; Haoyu Zhong; Beibei Xu; Man Chu; Xiwen Jia; Kai Ding; Xin Shen; et al. (Angiogenesis, 2026)

Structurally constrained hybrid modeling for cross-year prediction and mechanistic interpretation of marine biofouling evolution - Zhiqiang Cui; Haonan Huang; Yuanbei Li; Qiang Xu; Yuwei Hong; Mengting Jia (Ocean Engineering, 2026)

Inhibitory effect of moisture loss on braised pork quality by rapid cooling assisted with static magnetic field - Lirong Jia; Haijun Qiao; Hong Zhu; Pengcheng Wen; Zhilong Jia; Pengjie Wang; Xingmin Li; Ju Qiu (Meat Science, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

Maximum mean discrepancy enhanced Informer for accurate cross-domain dual-timescale effluent prediction in wastewater treatment plants - Jun-Hong Zhou; Yang-Guang Xia; Xiao-Li Yang; Xin-Yi Xiang; Yu-Jia Fu (Bioresource Technology, 2026)

Designing virtual environments for psychological health: nature connectedness mediates the benefits of indoor virtual green exercise on restoration - Xing-xing Jia; Jing-cheng Xu; Yu-cheng Xu; Hong-yi Li; Bing Zhao; Wei Wei (Building and Environment, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Design, synthesis, and biological evaluation of novel isobenzofuran-1(3H)-one derivatives with antioxidant properties and improved oral bioavailability - Debasis Das; Kun Zhang; Lingzhi Xie; Yong Li; Yimeng Wu; Dandan Qiao; Yuxi Cao; Jianhe Jia; Jian Hong (Molecular Diversity, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

A novel PGPR Streptomyces sp. for efficient phthalate biodegradation: Mechanistic insights and application in contaminated soil - Hong-Jia Huang; Yi-Tong Huang; Miao Xin; Xiao-Qiong Zhu; Hui LYU; Jiayu Hu; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Meng Li; Da-Wei Li; et al. (Journal of Hazardous Materials, 2026)

Exploring the multidimensional synergistic evolution mechanism of green watershed policies in China: A network analysis approach - Zhisheng Jia; Hongyang Wang; Minghui Zhang; Shihao Duan; Li Ma; Pei Hong; Shengyan Pu; Fengchang Wu (Journal of Cleaner Production, 2026)

Resonant effects of seismicity on substance migration in rock fractures - Zhi-Jie Che; Jia-Qing Zhou; Li-Guo Guo; Fu-Shuo Gan; Hong-Bin Liu; Changdong Li; Yi-Feng Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Zinc isotopic fractionation during magmatic differentiation and hydrothermal processes: implications for Li mineralization in the Jiajika granitic pegmatites, Sichuan, China - Jia-Wen Liu; Shi-Hong Tian; Xian-Lei Geng; Ying-Li Gong; Lu Chen; Shi-Qi Huang (Geochimica et Cosmochimica Acta, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Concentration-oriented vs. health-oriented strategies: future anthropogenic sectoral emission reductions for PM2.5 and ozone control over eastern China - Ziyu Long; Lei Chen; Ke Li; Jia Zhu; Xi Chen; Wenhao Qiao; Zhenjiang Yang; Yang Yang; Xu Yue; Hong Liao (Environmental Pollution, 2026)

Inhibition of zinc dendrites by fluorine and nitrogen-codoped vertical graphene for flexible zinc-ion hybrid supercapacitors - Jia Qiao; Shanyi Zhu; Mingliang He; Binghua Zhou; Guobing Zhou; Huiqin Li; Gan Jet Hong Melvin; Mingxi Wang; Hironori Ogata; Yoong Ahm Kim; Morinobu Endo; Zhipeng Wang (Chemical Engineering Journal, 2026)

Rational design of carbon dots with pyrrole rings for visible in vitro diagnosis of vulnerable atherosclerotic plaque - Xuelian Wang; Wanting Fu; Minye Ji; Jian Zhang; Jia Qi; Junli Zuo; Ying Chen; Yan He; Qingwen Gu; Hong Wu; Zhilei Cong; Jinping Li; et al. (Chemical Engineering Journal, 2026)

Multi-objective optimization of residential layout designs considering summer outdoor thermal comfort, wind environment, and sunlight duration - Lingkun Jia; Ying Li; Xiaoke Tian; Yuehua Lin; Xiaoqiang Hong (Building and Environment, 2026)

Phylotranscriptomics reveals conflicts of deep nodes in Saxifragales - Hui-Ling Li; Hong Chang; Huan-Huan Xie; Lei Zhang; Guo-Qian Hao; Dimitar Dimitrov; Peng-Chuan Sun; Nathanael Walker-Hale; Jia-Liang Li; Xiao-Ting Xu (Molecular Phylogenetics and Evolution, 2026)

Variation characteristics and segment differences of urban heat exposure risk in continuous time series: A comprehensive synchronous comparison of daily and hourly scales - Junmao Zhang; Xia Yao; Meixia Lin; Tao Lin; Yuan Chen; Wenhui Li; Hongkai Geng; Yicheng Zheng; Zixu Jia; Hong Ye; Guoqin Zhang (Landscape and Urban Planning, 2026)

Experimental investigation on dynamics and flow resistance of granular-fluid flows - Cong-jiang Li; Yu-xiang Hu; Hong-yu Luo; Jie-yuan Zhang; Hai-Bo Li; Jia-wen Zhou (Engineering Geology, 2026)

Ultrasound-activated in situ nano-vaccines (SATNAV) for precise CRPC sono-immunotherapy via multi-reprograming the immunosuppressive microenvironment - Xinzhi Xu; Jing Fu; Yujie Wan; Jiaqi Gong; Ruixia Hong; Jia Tang; Qizhi Wang; Ying Li; Kaifeng Huang; Yizhe Zhong; Hang Zhou; Jichun Yang; et al. (Chemical Engineering Journal, 2026)

Metabolic reprogramming by baicalein disrupts fibroblast–macrophage crosstalk in idiopathic pulmonary fibrosis - Wen Zhang; Liu-Liu Yuan; Jia-Rong Li; Tian-Sheng Zheng; Li-Hong Fan (Chemico-Biological Interactions, 2026)

Observation of Concurrent Latitudinal and Longitudinal Fractionations of α- and β-HCH in Chinese Rural Surface Soil: Implications for Global Lifecycle - Shuai Hao; Yi-Fan Li; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Wen-Long Li; Ning-Zheng Zhu; Pu-Fei Yang; Hong-Liang Jia; Min-Gang Cai; Roland Kallenborn; Derek CG Muir (Archives of Environmental Contamination and Toxicology, 2026)

Ferlapioside: a new bromine substituted iridoid glycoside from the roots of Ferula lapidosa Korovin - Xin-Xin Li; Kholida Ibodullaevna Khasanova; Jia-Huan Shang; Anarbay Uraimovich Babekov; Wen-Jun Li; Jing-Juan Li; Hong-Tao Zhu; Komila Alibekovna Eshbakova; Ying-Jun Zhang (Natural Product Research, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Designing emulsified systems with soybean oil body membrane protein aggregate: Insights into chain bead-like structure, molecular interactions and interfacial behavior - Xiaoyu Li; Mengting Jia; Ikram Alouk; Hong Zhang; Duoxia Xu; Xuebing Xu (Food Research International, 2026)

Docosahexaenoic acid (DHA) enhances lipid utilization in adipocytes through PPARα-ACSL4 axis-promoted lipid droplets-mitochondrial coupling in grass carp (Ctenopharyngodon idellus) - Rongrong Xue; Luyao Jia; Mingkui Wei; Handong Li; Jian Sun; Tao Zhao; Hong Ji (Food Research International, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Aroma in ‘Munage’ Grape Spirits response to different inoculation strategies of H. uvarum/P. fermentans in mixed fermentation with S. cerevisiae - Jia-Qi Wang; Jia-Liang Hu; Qian-Qian Feng; Yang Zhang; Hong-Yan Zhang; Su-Fang Zhang; Yun-Kui Li; Hua-Feng Yang; Guo-Jie Jin (Food Bioscience, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

Anodic potential and conductive carrier synergistically drive nitrite-free extracellular electron transfer-dependent anaerobic ammonium oxidation (Anammox) in mixed microbial communities - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Fei-Fan Shi; Ru Fan; Jia-Ying Xu (Bioresource Technology, 2026)

Genetic diversity of Theileria species identified from questing and parasitic ticks in selected areas in Qinghai, China - Yuan Han; Zhi Li; Yong Fu; Junlong Liu; Dan Jia; Chunhua Li; Hong Yin; Mengtong Lei (Veterinary Research Communications, 2026)

Epidemiological and evolutionary analysis of porcine circovirus type 2 within pig populations in central China during 2021-2024 - Jia-Xin Li; Hao Li; Feng-Shuo Wang; Yun-Yun Li; Guang-Cai Wang; Hong-Lei Zhang; Xue-Yan Ding; Lan-Lan Zheng; Shi-Jie Ma (Archives of Virology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Subspecies-specific epigenetic remodeling drives differential cold adaptation in geng/xian rice - Dong-Ao Li; Xiao-Long Xu; Yu-Hong Luo; Zu-Wen Zhou; Yong-Qing Qian; Qian Tang; Xi-Tong Zhu; Jia-Ming Song; Ling-Ling Chen (Plant Science, 2026)

Heterogeneous interaction between NO and SO2 on α-Fe2O3 surfaces under atmospheric conditions - Yongcheng Jia; Jun Liu; Tianzeng Chen; Hao Li; Yonghong Wang; Peng Zhang; Biwu Chu; Qingxin Ma; Hong He (Journal of Environmental Sciences, 2026)

How vehicle and fuel specifications affect evaporative and refuelling emissions from petrol vehicles - Chunxiao Hao; Yunshan Ge; Xin Wang; Jindong Liang; Peng Chen; Hong Bao; Jiachen Li; Dailin Yin; Chongyao Wang; Ruonan Li; Junfang Wang; Jia Ke; et al. (Journal of Environmental Sciences, 2026)

Dietary silymarin improves gut–liver health by enhancing intestinal barrier integrity and modulating TLR4/NF-κB and NLRP3-mediated inflammatory responses in Aeromonas hydrophila–infected grass carp - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Yun Zhang; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Distinctive evolutions of specific surface area in CO2 activation of biochars from different biomasses - Hong Zhang; Xin Jia; Jun Pan; Yuhui Zhang; Jiancheng Yang; Kaixuan Li; Xuejing Liu; Shurong Wang; Guangwen Xu (Chemical Engineering Journal, 2026)

Hydraulic retention time extension and multi-point reflux promote full-scale partial mainstream anaerobic ammonium oxidation (Anammox) at low temperatures - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Wen-Bo Liang; Yu-Jia Fu (Chemical Engineering Journal, 2026)

Wind tunnel test of non-uniform snow distribution on large-span suspended gable roofs with snow fences - Jianshuo Wang; Aoyou Liu; Junxiang Zhao; Zhihua Chen; Ningning Hong; Xizhi Zhang; Li Jia; Julita Krassowska (Cold Regions Science and Technology, 2026)

The optimal dietary valine requirement of juvenile Onychostoma macrolepis - Xiangtong Yuan; Lingwei Zhu; Lu Zhou; Luyao Jia; Handong Li; Jian Sun; Hong Ji (Animal Feed Science and Technology, 2026)

Two new abietane diterpenoids from Salvia cavaleriei var. simplicifolia - Qian Wu; Jie Yang; Mi-Na Yang; Li-Jia Ye; Hong-Fen Jiang; Miao Zhang; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Lateral groundwater-river exchanges estimation via actively heated fiber optics based thermal response test - Zi Chen; Hui Yu; Shijia Mei; Hai Yang; Teng Xu; Zhengyang Jia; Hong Zhang; Yuehua Jiang; Yun Li; Quanping Zhou; Jie Li; Yuping Chen (Journal of Hydrology, 2026)

Dysregulation of hepatopancreatic microRNAs in Penaeus vannamei in response to Ecytonucleospora hepatopenaei (EHP) infection: Implications for innate immunity and metabolic function - Li-Guo Yang; Lei Feng; Li-Yan Ma; Xue-Feng Song; Jia-Yuan Xu; Bian-Bian Zhang; Wen-Hong Fang; Xin-Cang Li (Journal of Invertebrate Pathology, 2026)

Concurrent removal of cetirizine hydrochloride and biodiesel accumulation in Chlorella vulgaris - Wen-Bo Yan; Zhong-Hong Zhang; Guo-Hui He; Jia-Xuan Tang; Hui-Lin Guo; Yi-Fan Zhan; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Journal of Hazardous Materials, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Study on the irradiation control of urease activity and its solidification of red clay to enhance radon reduction - Yuanyuan Tang; Rui Liang; Jia Wei; Yiqing Sun; Weihang Peng; Fubing Li; Chengyu Zhang; Changshou Hong (Journal of Environmental Radioactivity, 2026)

Mechanisms of corrosive media formation and anti-corrosion coating in Acid-Deposit environments - Jia Kang; Huan Liu; Qiaoyan Zhou; Haiyan Li; Xiuju Zhang; Hong Yao (Fuel, 2026)

Enhanced extraction of polyphenols from persimmon peel via subcritical solvent-assisted method: Targeting α-amylase/α-glucosidase inhibition and mechanistic elucidation - Di Zhao; Xinyi Zhang; Ruona Li; Yiwei Sun; Junqing Bai; Hong Xiao; Yu Zhang; Yongqiu Yan; Fuhuai Jia; Huaide Xu; Mei Li (Food Chemistry, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Tunable synthesis of tailored high-energy-density fuels from coal-based fluorene - Bing-Wei Chen; Hua-Jun Zhai; Yan-Cheng Hu; Yan-Hong Tan; Jia Li; Zhilian Wu; Lin Shao; Jing-Pei Cao (Chemical Engineering Journal, 2026)

Characterizing dynamic indoor pollutant dispersion pathways using an interpretable attention-driven spatiotemporal modeling framework - Ruiliang Ma; Yuan Zhao; Li Wang; Lingshu Jia; Zhongji Guo; Guolong Li; Tao Huang; Xiaoxuan Mao; Hong Gao; Jianmin Ma (Building and Environment, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Design, synthesis and activity evaluation of usnic acid monoesterification derivatives - Qing Zhang; Jun-Li He; Xiao-Xia Zhuo; Yi-Meng Hao; Hong-Ting Duan; Yan Jia; Jing-Jing Wang; Li-Ning Wang (Natural Product Research, 2026)

Development of a migration model for additives in desiccants and deoxidisers in food packaging using rice flour as food stimulant - Hongyi Liu; Rujin Bai; Dan Hong; Hong Zhang; Zhou Chen; Siting Li; Aijin Ma; Yingmin Jia (Food Additives & Contaminants: Part A, 2026)

From inhalation to systemic damage: Decoding the mechanistic cascade of silica nanoparticle-induced multi-organ toxicity - Jia-Qi Ban; Li-Hong Ao; He-Qun Gu; Yun-Geng Wei; Qiong Tian; Xiu He; Hua Zhao; Jun Li (Toxicology, 2026)

Quercetin alleviates Deoxynivalenol-induced myocardial fibrosis in chicken by regulating MCU-mediated mitochondrial calcium overload - Hong-yu Fu; Yi Fang; Jia Chen; Hongxue Yang; Xuehan Jiang; Yishan Yin; Bo Li; Xiaoxiao Chen; Jingzeng Cai; Ziwei Zhang (Journal of Hazardous Materials, 2026)

Tracing the global origins of black tea using rapid XRF techniques coupled with advanced machine learning - Yicong Li; Nicholas Birse; Wanqi Jia; Manus Carey; Yunhe Hong; Xiaotong Liu; Di Wu; Christopher T. Elliott (Food Research International, 2026)

Associations of urinary environmental phenols with obesity and lipid metabolism in children and adolescents: The expanded Chinese National Human Biomonitoring (CNHBM) project - Nan Jiang; Qi Chen; Beijing Cheng; Ke Meng; Jia Wang; Tianlin Li; Han Chen; Yinghao Liao; Hong Sun; Ran Liu (Environmental Research, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

Novel senescence inducer ICA-11c, a derivative of icaritin, YAP-dependently suppresses hepatocellular carcinoma cells - Hong-fei Chen; Shuai Shen; Shuang-li Wang; Li Ye; Ji-chong Li; Wen-li Cao; Zi-lin Hou; Jian-huan Jia; Qing-bo Liu; Guo-dong Yao; Shao-jiang Song (Chemico-Biological Interactions, 2026)

Deciphering the role and mechanism of biochar dosage and inoculum-to-substrate ratio in modulating interspecies electron transfer and alleviating acid inhibition - Yu-Hong Qiu; Zi-Fan Wu; Jia-Bing Li; Zhi-Man Yang (Biomass and Bioenergy, 2026)

CD33 Isoform Splicing Dysregulation: A Molecular Determinant of Microglial Dysfunction in Alzheimer’s Disease Pathology - Xiao-Yan Li; Yu Zhang; Zhao Ran; Jia-Xin Luo; Xiao-Qin Yu; Mei-Hong Lu (Molecular Neurobiology, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Genome-Wide DNA Methylation and RNA Analysis Reveal Epigenetic and Transcriptomic Changes in Carbapenem-Resistant Klebsiella pneumoniae Strains - Jia Tao; Liru Wang; Lixin Yan; Xinxin Hu; Wei Hong; Jiale Li; Wei Jia; Jianning Jin (Current Microbiology, 2026)

Mechanisms of Fish Intestinal Damage Under Environmental Stress: Insights From Carbonate Saline–Alkali Water Perspective - Jia Rui Cui; Qi Fang Lai; Yue‐Hong Li (Reviews in Aquaculture, 2026)
The intestinal tract is an important functional organ in fish, as it plays a key role in digestion and absorption, mucosal immunity, endocrine function, and metabolism. Therefore, damage to this organ greatly impacts fish health. This injury is usually associated with a poor aquaculture water environment, stressful conditions, and pathogen presence. In this review, in light of gut injury being a common pathology in aquaculture, we have summarized the current understanding of the intestinal damage of fish caused by carbonate water stress, and the mechanism of intestinal tissue damage caused by carbonate saline water stress, including the intestinal barrier function of fish and the role of various cells and molecules involved in the occurrence and development of diseases. Comparative data on carbonate stress responses across different teleost lineages (such as the Cyprinidae and Perciformes) have been integrated. The review also covers current methods for treating intestinal damage in fish, including dietary interventions, medications, and probiotics. Our findings highlight the need for more in‐depth research in this area to better understand the mechanisms underlying the occurrence of intestinal tissue damage in fish in carbonate‐based saline waters and to develop effective preventive and therapeutic strategies. Improved development of saline–alkaline waters and research into new treatments are essential for the sustainability of aquaculture and the health and productivity of farmed fish.

High-Resolution Underwater Imaging via Richardson–Lucy Deconvolution Beamforming with Acoustic Frequency Comb Excitation - Jie Li; Jiace Jia; Deyue Hong; Yi Zhu; Shuo Yang; Zhiwen Qian; Jingsheng Zhai (Journal of Marine Science and Engineering, 2025)
Underwater acoustic imaging is essential in marine science and engineering, enabling high-resolution detection and characterization of underwater structures and targets. However, conventional deconvolution beamforming methods using broadband signals often suffer from model mismatch, inter-frequency interference, and limited noise robustness. To overcome these challenges, this study rigorously analyzes the point spread function of the imaging system and introduces Acoustic Frequency Comb (AFC) excitations to enhance resolution. By exploiting the autocorrelation characteristics of AFC signals and optimizing key parameters, imaging artifacts are effectively suppressed and the main-lobe width is narrowed, resulting in a 50% improvement in range resolution. Comparative analyses identify the Richardson–Lucy algorithm as the most effective in enhancing azimuthal resolution and maintaining robustness under array perturbations and low signal-to-noise ratios. Parametric studies further demonstrate that AFC excitation outperforms conventional linear frequency modulated pulses, achieving a 30% main-lobe width reduction, 10 dB sidelobe suppression, and a 14 dB noise decrease. Finally, tank experiments confirm the simulation results, showing that accurate PSF modeling enabled by AFC ensures high angular resolution. The discrete spectral structure facilitates more effective separation of signal and noise during iterative deconvolution, while excellent autocorrelation characteristics guarantee high range resolution, yielding superior overall imaging performance.

Presence and sources of antibiotics in Dongzhai Harbor, Hainan Island - Tuan-Tuan Wang; Hong-Jin Zhang; Tuan-Qi Guo; Jia-Yu Luo; Bi-Jiao Li; Wen-Qing Liao; Ling Mo; Sai Wang; Yue-Hua Huang (Marine Pollution Bulletin, 2025)

Unveiling the effect of Fe(III) and sulfate on ammonium oxidation under anaerobic condition: interactions and extracellular electron transfer - Weizhuo Ye; Jiaqi Yan; Jia Yan; Qixing Ji; Lei Huang; Meng Li; Hongguo Zhang; Shuyuan Hong; Jinying Cai (Water Research, 2025)

GAS1 affects proliferation, apoptosis, and steroid hormone levels by regulating mitochondrial functions and the PI3K/AKT pathway in bovine granulosa cells - Wenjie Yu; Na Pei; Haitao Jia; Yijing Yin; Hong Xu; Tian Tian; Chang Liu; Lingxia Xu; Ze Li; Zibin Liu; Xiaoshi Cai; Mingkai Yu; et al. (Theriogenology, 2025)

Synoptic-scale precipitation events recorded by high-resolution intra-shell δ18O of land snail in the Asian monsoon marginal zone - Qian Zhang; Jibao Dong; Guozhen Wang; Fan Luo; Ya-na Jia; Chengcheng Liu; Xiulan Zong; Xiangzhong Li; John Dodson; Hong Yan (Quaternary Science Reviews, 2025)

Phytochemical profiling of Bai traditional food: Eight previously undescribed meroterpenoids derivatives with cytotoxic potential from the flowers of Rhododendron pachypodum - Ying Wang; Jie Luan; Ji-Ai Wang; Xiu Chen; Fu-Cai Ren; Bing Chen; Jing Jia; Gao-Hong Zhang; Yong Li; Jiang-Bo He (Phytochemistry, 2025)

Melatonin improves synaptic morphological plasticity of adolescent male rats after perinatal BDE-209 exposure via SIRT1-mediated LIMK1 and CREB signaling - Jingjing Gao; Jinghua Shen; Lu Gao; Dongying Yan; Ying Wang; Jia Meng; Dawei Chen; Hong Li; Jie Wu (NeuroToxicology, 2025)

Study on the adsorption performance of microplastics by alum sludge modified with heat treatment and chitosan - Jia-Qi Diao; Hong-Ji Li; Tao Zhang; Jing Yang; Cong Liu (Journal of Environmental Chemical Engineering, 2025)

Biodegradation of unpretreated polypropylene microplastic and agricultural polypropylene film by a bacterium isolated from an oil reservoir - Sheng Jin Li; Yun Yang Wan; Zhe Ke Zhong; Ying Jia Zhu; Hong Mei Mu; Sheng Bao Shi (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of high-performance crystalline zirconium phosphate adsorbents and its ammonium ion intercalation mechanism for next-generation hemodialysis - Jingwen Feng; Jianjun Cheng; Jingwen Li; Susu Jia; Feiping Cao; Jiajin Feng; Dapeng Zhou; Jiahua Shi; Choon-Hong Tan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2025)

Construction of a machine learning-based prediction model for rice varieties—cooking—mastication - Mengjie Ma; Zhengbiao Gu; Li Cheng; Zhaofeng Li; Caiming Li; Mingyi Shen; Jinyi Wu; Jia Liu; Yan Hong (Food Research International, 2025)

Ziziphi Spinosae Semen jujubosides extract ameliorates cognitive impairment by modulating brain BDNF/TrkB pathways and intestinal barrier integrity in HFD-fed mice - Shan Jia; Taofu Tu; Hong Yuan; Fengchen Li; Xiaoyu Wang; Yonghong Meng; Yalong Lu (Food Bioscience, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Predicting and interpreting nitrogen removal performance and functional microbial abundance of single-stage partial nitrification and anammox system using machine learning methods - Xiulin Mu; Fangxu Jia; Shengming Qiu; Yiran Li; Ning Mei; Xingcheng Zhao; Baohong Han; Xiangyu Han; Jingjing Zhang; Hong Yao (Bioresource Technology, 2025)

Fermentation of Panax ginseng C.A. Meyer extract with lactic acid bacteria exerts hepatoprotective effects via activating the NRF2 pathway - Jia-Jun Liang; Hong-Xia Liu; Jian-Gang Yan; Guo Xie; Wen-Li Liu; Jia-Hui Lin; Xiao-Min Li; Xin-Liang Mao (Journal of Molecular Histology, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Exploring the main and interactive effects of urban morphology on land surface temperature across different functional zones: A local geoshapley analysis based on XAI - Jin-Tao Yang; Xing-Wen Zhou; Xu Chen; Xiong Yao; Mao Li; Ming-Hui Yin; Fei Dong; Shi-Hong Yan; Jia-Liang Zhao (Sustainable Cities and Society, 2025)

Cost-benefit analysis of remanufacturing of used agricultural machinery parts in China - Jia-qi Shen; Zong-yi Zhang; Hong-bo Li (Journal of Cleaner Production, 2025)

Achieving partial nitritation-anammox in membrane-aerated biofilm reactor by hydroxylamine addition - Ning Mei; Fangxu Jia; Ying Liu; Yiran Li; Xin Qi; Baohong Han; Xu Zhang; Tao Liu; Hong Yao (Journal of Environmental Management, 2025)

Potential of different fractions of polyphenols in persimmon peels: Phenolic profiles, bio-activities, and mechanism of inhibition against α-glucosidase - Di Zhao; Xinyi Zhang; Yingying Zhang; Ruona Li; Junqing Bai; Hong Xiao; Yu Zhang; Yongqiu Yan; Fuhuai Jia; Huaide Xu; Mei Li (Food Chemistry, 2025)

Gut microbiota modulation by structurally diverse foodborne polysaccharides: In vitro fermentation and prebiotic activity evaluation - Lu Wang; Jia-hao Fan; Yao Yang; Hong-wei Qiu; He-he Li; Wen-yi Kang; Guang-ping Lv (Food Bioscience, 2025)

rGO/polypyrrole-modified bioelectrode reshapes microbial communities for enhanced energy-recovering denitrification in carbon-limited wastewater - Yue-Jia Yang; Hong-Li Lu; Naif Abdullah Al-Dhabi; Wang-Wang Tang; Shuai Wang; Dan Cui (Environmental Research, 2025)

Climate-driven expansion of Takayama acrotrocha blooms: First outbreak along the north coast of Shandong, China linked to intense precipitation and warming - Xin Hong; Zheng-Xi Zhou; Jin-Xiu Wang; Chao Liu; Hui-Xia Geng; Yi-Jia Song; Yi-Fan Li; Fan-Zhou Kong; Qing-Chun Zhang; Ren-Cheng Yu (Environmental Pollution, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Eco-friendly taro stem-sourced cellulose/polypyrrole hybrid aerogel: An efficient capture strategy for microplastics removal - Wei-peng Qiu; Hai-ze Su; Hao Su; Shao-hua Luo; Li-shan Lai; Jia-le Zhu; Zhen-lin Xu; Hong Wang; Peng Wen (Chemical Engineering Journal, 2025)

YY1 lactylation promotes fibroblast senescence by targeting the PU.1-BTG2 axis to promote oral submucous fibrosis - Muhammad Tufail; Jing Zhang; Cai-Yun He; Jia-Ju Hu; Jie Liang; Wen-Dong Wan; Yu-Qi Huang; Zhen Rao; Hong Wu; Can-Hua Jiang; Ning Li (Chemico-Biological Interactions, 2025)

The individual and synergistic effects of dietary lipids and DHA on the growth performance, feed utilization, lipid metabolism, antioxidant capacity, and immune responses of grass carp (Ctenopharyngodon idellus) - Rongrong Xue; Handong Li; Shanghong Ji; Luyao Jia; Lu Zhou; Mingkui Wei; Tao Zhao; Jian Sun; Hong Ji (Animal Feed Science and Technology, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Extreme Phenotypic Variation Confounds Acanthocephalan Systematics: A Case Study of Longicollum pagrosomi and Pomphorhynchus zhoushanensis (Acanthocephala: Echinorhynchida) - Cui‐Hong Zhao; Hui‐Xia Chen; Matthew Thomas Wayland; Rui‐Jia Yang; Xiao‐Hong Gu; Liang Li (Zoologica Scripta, 2025)
The phylum Acanthocephala is a ubiquitous group of zooparasites, with major socio‐economic importance. The true diversity of the Acanthocephala is obscured by the phenomena of cryptic speciation and a large degree of intraspecific variation. In this study we describe an example of extreme phenotypic variation in neck morphology. The pomphorhynchid acanthocephalans, Longicollum pagrosomi and Pomphorhynchus zhoushanensis were originally differentiated on the basis of differences in neck morphology; P. zhoushanensis possesses a neck bulb whereas this structure is absent in L. pagrosomi . However, ASAP and phylogenetic analyses of the ITS, 12S, cox 1 and cox 2 sequence data, together with comparative mitogenomics, revealed that the two taxa are in fact conspecific. Therefore, the presence or absence of a neck bulb represents extreme phenotypic variation, and this character is not reliable for distinguishing the genera Pomphorhynchus and Longicollum. In the absence of other characters to discriminate the two genera, Longicollum is relegated to a junior synonym of Pomphorhynchus . A new combination Pomphorhynchus pagrosomi (Yamaguti, 1935) comb. nov. is proposed for L. pagrosomi Yamaguti, 1935 and P. zhoushanensis Li, Chen, Amin & Yang, 2017 is relegated to a junior synonym of P. pagrosomi .

Probiotics reduce the severity of DSS-induced colitis in aged mice by enhancing intestinal barrier function and modulating gut microbiota - Ai-Ling Liu; Hong Lv; Hong-Ying Wang; Hong Yang; Yue Li; Yan-Fang Jia; Jia-Ming Qian (GeroScience, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Rapid self-assembled electroactive biohybrid cathode-driven electron transfer for enhanced uranium bioremediation - Keng-Qiang Zhong; Le-Yi Chen; Meng Li; Xing Chen; Xing Lu; Yu-Chen Yang; Hao-Wen He; Bao-Hua Jing; Hong-Guo Zhang; Jia Yan; Yi-Feng Zhang (Journal of Hazardous Materials, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Simplified synthetic community reveals the enrichment of phthalate-degrading bacteria in maize rhizosphere enhancing phthalate degradation - Jia-Lu Wei; Yu-Hong Huang; Jun-Hua Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Curcumin-mediated photodynamic treatment efficiently inhibits Bacillus cereus and extends the shelf-life of flat rice noodles - Hao-Ran Ji; Jia-Jun Yan; Zi-Hui Chen; Wen-Li Shi; Li-Wen Chen; Juan Wang; Yu Ding; Ai-Min Jiang; Bing Du; Cai-Hu Liao; Hong-Tao Lei; Quan Zhou; et al. (Food Research International, 2025)

Cadmium activated oxidative stress and endoplasmic reticulum stress pathway promote apoptosis in the common carp (Cyprinus carpio L.) brain - Jia Liu; Wei Lu; Zheng-yao Guo; Yue-hong Li; Wen-fa Lv (Fish & Shellfish Immunology, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

HFIP-driven Schmidt-type reaction enables chromone-3-carbonitriles and its applications - Jia Xu; Jie Lei; Li-Xin Zhang; Shan Yu; Cheng-He Zhou; Zhi-Gang Xu; Hong-Wei Du; Zhong-Zhu Chen (Molecular Diversity, 2025)

Pseudomonas bambusae sp.nov., an Aniline Blue-Decolorizing Bacterium Isolated from Decaying Round Bamboo Culms - Xiao-Long He; Jia-Yan Wang; Jin-Jia Liang; Cheng-Jing Ren; Xin-Yi Guo; Wen-Jie Ke; Min Wu; Hong-Zheng Liu; Min Jin; Fang-Li Sun; Shuai-Bo Han (Current Microbiology, 2025)

Engineering hypo-osmotic Crypthecodinium cohnii via SL-ALE for high-yield DHA biosynthesis from agricultural byproducts - Yi-Tong Yao; Yu-He Zhang; Yan Huang; Xiao Zhang; Chen-Yu Wang; Jia-Qi Zheng; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Algal Research, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Molecular docking-based design of novel tricyclic tetrahydropyridothienopyrimidinone derivatives as AChE/MAO-B dual inhibitors - Juan Zhang; Yue Li; Jia-Dong Shao; Guo Wei; Nai-Yu Zhang; Kong-Kai Zhu; Kai-Ming Wang; Cheng-Shi Jiang; Jia-Hong Wang (Molecular Diversity, 2025)

Evidence for cognitive compensation mechanism in the postoperative delirium: a prospective multi-modal neuroimaging cohort study - Guo-Bin Zhang; Hao-Yi Li; Jia-Mei Lv; Xiao-Kang Zhang; Yong-Gang Wang; Yun-Yun Duan; Hong-Yan Chen; Zhi-Zheng Zhuo; Ya-Ou Liu; Hua-Wei Huang (Brain Imaging and Behavior, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Integrated proteomic and transcriptomic analysis reveals venom composition in the ectoparasitoid wasp, Anisopteromalus calandrae - Die Liu; Jia-peng Yang; Li Liu; Yue Zhang; Yu-yun Zhu; Ren-huai Dai; Guy Smagghe; Hong Yang (Journal of Stored Products Research, 2025)

Soil mesofauna bacterial diversity: Insights from cultured collembolans, enchytraeids, and mites species - Bo-Wen Liu; Jing Wen; Shuai-Fei Ye; Jia-Jia Gu; Ming-Xin Li; Xiao-Bo Xiong; Zong-Zheng Liang; Hong-Tao Wang (Food Webs, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Environmental levels of bis(2-ethylhexyl)-tetrabromophthalate (TBPH) cause thyroid toxicity and early carcinogenic signals in juvenile fish - Xiang-sheng Hong; Liang Yan; Wei Sang; Wang Liu; Zhi-tong Li; Juan Wang; Sai-hong Yan; Jia-jing Xin; Gao-feng Zhao; Xu-fa Ma; Jin-miao Zha (Environmental Pollution, 2025)

Efficient zinc extraction from industrial wastewater with novel phenyl phosphate for saline wastewater net-zero emission - Shuai Li; Jianguang Yang; Hong Liu; Jia Ning; Bo Han; Shenghai Yang; Hai Yu; Fang Hu; Hongliang Zhang; Yongming Chen (Desalination, 2025)

Ice ball size and temperature change during cryoablation in a lard and an ethiodized-oil tissue phantom - Nai-Wen Chang; Shu-Huei Shen; Chien-An Liu; Felix Antony Halim; Jia-An Hong; Chih-Chien Li; Ping-Lang Yen (Cryobiology, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

A new fossil record of Adiantum (Pteridaceae) from Oligocene of Qaidam Basin, Northwest China and its palaeoenvironmental implications - Hong-Yu Chen; Tao Yang; Ya Li; Dieter Uhl; Lei Han; Jia-Hao Cai; Li Zhang; Yong-Dong Wang; De-Fei Yan (Palaeoworld, 2025)

Supplementation of exogenous RpfE facilitates polychlorinated biphenyl degradation in soil by stimulating endogenous rpfE expression and promoting cell growth - Hong Zou; Fengjun Xu; Xinyi Li; Yangyang Jia; Yulong Fu; Chaofeng Shen (Journal of Hazardous Materials, 2025)

Hexavalent chromium and cellular senescence: A comprehensive analysis from chromate-exposed occupational population and chromate-inhaled mouse model - Zhiqiang Ji; Yali Zhang; Guiping Hu; Shiyi Hong; Zekang Su; Qiaojian Zhang; Li Wang; Tiancheng Wang; Shanfa Yu; Qian Bu; Fang Yuan; Xiaojun Zhu; et al. (Journal of Hazardous Materials, 2025)

Efficiencies, pathways and mechanism on simultaneous biodegradation of phthalates and polycyclic aromatic hydrocarbons by bacterial consortium - Yao-Si Chen; Jia-Lu Wei; Jie-Bin Zhou; Yu-Hong Huang; Guang-Xuan Tang; Yan-Wen Li; Hai-Ming Zhao; Lei Xiang; Nai-Xian Feng; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Molecular characterization, expression pattern and the function of TRAF2 from blood parrot Amphilophus citrinellus ×Vieja melanura response to LPS stimulation - Jie-Li Cai; Yue Zhang; Hui Gao; Qi Wang; Wei Huang; Yi-Jie Cai; Wei-Xin Jia; Jun-Jie Wang; Xiao Chen; Hong-Yan Sun (Fish & Shellfish Immunology, 2025)

Z-scheme MIL-88A(Fe)/LaFeO3 heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced organic pollutant detoxification - Ruo-Xuan Mei; Peng Wang; Fu-Xue Wang; Zi-Chen Zhang; Xiao-Hong Yi; Zi-Yu Jia; Ke-Xin Li; Chong-Chen Wang (Environmental Research, 2025)

Two-dimensional nitrogen-doped carbon nanosheets-coated porous SiO composites sponges for durable anode materials of high-energy lithium-ion batteries - Zaohong Zhang; Weichen Chen; Jie Tian; Kai Zhang; Carlos Ponce de León Albarrán; Chuan Wu; Zhicong Shi; Zibiao Li; Jia Hong Pan (Chemical Engineering Journal, 2025)

CD39 activities in the treated acupoints contributed to the analgesic mechanism of acupuncture on arthritis rats - Yu-Jia Li; Jie Lin; Si-Qi Tang; Wei-Min Zuo; Guang-Hong Ding; Xue-Yong Shen; Li-Na Wang (Purinergic Signalling, 2025)

Moxibustion pre-treatment attenuates seizure severity during status epilepticus and counteracts the proconvulsant function of the purinergic P2X7 receptor - Hong-Wei Zhang; Jia-Jia Li; Yulihan Tang; Mao-Lin Tian; Sheng Huang; Meng-Juan Sun (Purinergic Signalling, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

The Eyes are The Windows To The Soul: Pupillary Changes Reflect The Consolidation of New and Old Memories During Sleep - Wei-Kun Su; Yan-Jia Luo; Fangyuan Li; Hong Jiang; Jing Wang; Ya-Dong Li (Neuroscience Bulletin, 2025)

Metabolome and Genome Analysis of a Novel Endophytic Fungus Aureobasidium pullulans KB3: Discovery of Polyketones and Polyketone Biosynthesis Pathway - Shuai Wang; Jia-Nuo He; Ying-Jie Wang; Wen-Ya Zhao; Qing-Xia Yang; Ya-Na Wang; Yang Zhang; Li-Ping Zhang; Hong-Wei Liu (Biochemical Genetics, 2025)

Decoding plant‐induced transcriptomic variability and consistency in two related polyphagous mites differing in host ranges - Lei Chen; Li‐Xue Guo; Xin‐Yue Yu; Shi‐Mei Huo; Ary A. Hoffmann; Jia‐Yi Zhou; Jing‐Tao Sun; Xiao‐Yue Hong (Molecular Ecology, 2025)
The diet breadth of generalist herbivores when compared to specialists tends to be associated with greater transcriptional plasticity. Here, we consider whether it may also contribute to variation in host range among two generalists with different levels of polyphagy. We examined two related polyphagous spider mites with different host ranges, Tetranychus urticae (1200 plants) and Tetranychus truncatus (90 plants). Data from multiple populations of both species domesticated on common beans and transferred to new plant hosts (cotton, cucumber, eggplant) were used to investigate transcriptional plasticity relative to population‐based variation in gene expression. Compared to T. truncatus , T. urticae exhibited much higher transcriptional plasticity. Populations of this species also showed much more variable expression regulation in response to a plant host, particularly for genes related to detoxification, transport, and transcriptional factors. In response to the different plant hosts, both polyphagous species showed enriched processes of drug/xenobiotics metabolism, with T. urticae orchestrating a relatively broader array of biological pathways. Through co‐expression network analysis, we identified gene modules associated with host plant response, revealing shared hub genes primarily involved in detoxification metabolism when both mites fed on the same plants. After silencing a shared hub CYP gene related to eggplant exposure, the performance of both species on the original bean host improved, but the fecundity of T. truncatus decreased when feeding on eggplant. The extensive transcriptomic variation shown by T. urticae might serve as a potential compensatory mechanism for a deficiency of hub genes in this species. This research points to nuanced differences in transcriptomic variability between generalist herbivores.

Impact of different green manure crops or fallow on yield and quality of a Chinese cabbage - Cai Zhao; Li Jin; Hong Fan; Yu Jia; Zhilong Fan; Wen Yin; Aizhong Yu; Falong Hu; Wei He; Qiang Chai (Plant and Soil, 2025)

Characterization and functional analysis of CsTLR13M/13S, two novel teleost toll-like receptor 13 in antimicrobial immunity - Ji-xing Feng; Sheng-jia Wang; Hong-ye Wang; Xue-peng Li (Aquaculture, 2025)

Persistent Wnt signaling affects IVF embryo implantation and offspring metabolism - Yanping Jia; Yingdong Liu; Yanhe Li; Xiaohong Guan; Junting Xu; Zihui Yan; Kuisheng Liu; Yalin Zhang; Dandan Bai; Jiani Xiang; Yan Zhang; Shangyu Hou; et al. (Science Bulletin, 2025)

Environmental adversity, endoplasmic reticulum stress, and neurogenesis - Zuohui Zhang; Wen Wen; Di Hu; Hui Li; Hong Lin; Jia Luo (NeuroToxicology, 2025)

Assessing how the partial substitution of phosphate by modified chickpea protein affects the technofunctional, rheological, and structural characteristics of pork meat emulsions - Yu Wang; Ning-ning Liu; Ke Li; Bo Chen; Jia-le Wang; Jun-guang Li; Yan-hong Bai (Meat Science, 2025)

Regulating the Cu-Ce interaction of CuCeOx/SAPO-34 catalysts to achieve a wide reaction temperature window for the collaborative synergistic removal of NOx and toluene at low temperatures and reaction mechanisms - Rong Liu; Xuehui Jia; Lin Li; Fengying Li; Xiang Tu; Weicheng Xu; Hansun Fang; Danping Li; Hong Huang; Chenglong Yu (Journal of Hazardous Materials, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

New micro- and macro- perspective on the removal process of 1H-benzotriazole by UV/PDS: Degradation mechanism, kinetics and multi-factor impact on removal efficiency - Juan Dang; Li-ao Gao; Xue Jia; Xiao-meng Zhang; Hong-jin Wu; Shi-bo Zhang; Qing-zhu Zhang; Shuai Tian (Journal of Environmental Management, 2025)

Investigating the fine structures of ginkgo starch during kernel development and their correlations with thermal properties - Yan Lu; Lian Zhou; Cai-Yun Zhang; Yan Qi; Xiao-Min Zhang; Zhang Pan; Hong-Jia Zhang; Yu-Ping Ling; Qing Liu; Chang-Quan Zhang; Li Wang (Food Chemistry, 2025)

An improved direct analysis method of transmission towers incorporating geometric defects and bolt slippage effects - Yu Zhu; Hong-Nan Li; Xing Fu; Jia-Xiang Li; Rui-Zeng Wei (Engineering Structures, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Multi-functional copper-based nanoenzyme system with antioxidant, ferroptosis inhibition for traumatic brain injury - Bowen Jia; Yuchen Yao; Yejia Xu; Yang Zhao; Jing Li; Yumeng Wu; Xiaofeng Zeng; Shijun Hong; Qianqian Li; Xuexia Liu; Chengliang Luo (Chemical Engineering Journal, 2025)

Transcriptome profiling reveals abnormal cell wall components in the cleistogamy mutant 1 (clm1) lodicule of foxtail millet - Zi-Dong Li; Xin-Li Yao; Lingqian Zhang; Jiajing Zhang; Jian-Hong Hao; Huashuang Wu; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; et al. (Planta, 2025)

Functional identification of mango MiEXPLA1a2 and MiEXPA4e1 genes in transgenic Arabidopsis and tomato - Xiang-juan Zhang; Ji-hong Yang; Jia-jun Li; Hui-jun Yang; Ming-qing Li; Yue-xing Zhang; Cong Luo; Xin-hua He (Plant Science, 2025)

Structurally diverse dammarane-derived triterpenoids from the twigs of Aglaia perviridis Hiern and their α-glucosidase and PTP1B inhibitory activities - Ming-Hui Feng; Jia-Sheng Liu; Fei Yang; Bin Wang; Ai-Hong Liu; Song-Wei Li; Shui-Chun Mao (Phytochemistry, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

A CRISPR/Cas9-induced point mutation on the GABA receptor subunit RDL confers high resistance to phenylpyrazole insecticides in the rice planthopper Laodelphax striatellus - Hui-Jie Wu; Jia-Peng Yang; Wen-Jing Ma; Zheng-Hao Li; Hong-Yu Feng; Zhang-Nv Yang; Hai-Jun Xu (Insect Biochemistry and Molecular Biology, 2025)

Seasonal and regional differences of heavy metals and nutrients from the five mariculture areas of large yellow croaker: Implications for environmental and fish quality - Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Jia-Lang Zheng; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Environmental Pollution, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Mantle evolution beneath a back-arc basin: Highly siderophile elements and Os isotope of Dongco ophiolitic peridotites, Tibet - Xiao-Ni Li; Wei-Qi Zhang; Tong Liu; Chang Zhang; Yin-Zheng Lin; Zhen Zhang; Jia-Ning Zhu; Hong-Yu Li; Chuan-Zhou Liu (Chemical Geology, 2025)

Deciphering the contribution of algae-rich microbial communities to dissolved organic matter in a eutrophic lake with distinct rainy and dry seasons - Han Yan; Hong-Fa Guo; Jia-Xun Li; Zhuo Chen; Shi-Qi Yin; Mo-Yu Shen; Yi Tao; Yin-Hu Wu; Hong-Ying Hu (Algal Research, 2025)

Interaction Between Hypoxia-Inducible Factor 1-alpha Gene Polymorphism and Helicobacter pylori Infection on Gastric Cancer in a Chinese Tibetan Population - Su-Hua Li; Yan Li; Meng-Jun Zhang; Qi An; Jia-Nan Tao; Xue-Hong Wang (Biochemical Genetics, 2025)

New perspectives on the immune regulatory role of dietary silymarin in the intestines of juvenile grass carp (Ctenopharyngodon idella) - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

Rethinking electrification strategy for China's passenger vehicle fleet decarbonization in resource-constrained environments - Xingyu Xue; Yin Li; Guorui Jia; Frank T. Hong; Zhenhong Lin; Chen Liu (Resources, Conservation and Recycling, 2025)

Antimicrobial polyketides from the endophytic fungus Fusarium asiaticum QA-6 derived from medicinal plant Artemisia argyi - Xiao-Shan Shi; Sui-Qun Yang; Xiao-Ming Li; Yan-He Li; Dun-Jia Wang; Xin Li; Ling-Hong Meng; Xing-Wang Zhou; Bin-Gui Wang (Phytochemistry, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Health risks of rare earth elements exposure: Impact on mitochondrial DNA copy number and micronucleus frequency - Shiyi Hong; Yali Zhang; Qiaojian Zhang; Zekang Su; Guiping Hu; Li Wang; Shanfa Yu; Xiaojun Zhu; Guang Jia (Journal of Environmental Sciences, 2025)

Prediction of the exposure profile of bisphenol A in Chinese population by physiologically-based pharmacokinetics modeling - Jun He; Li Zhang; Hong Jin; Daoyuan Yang; Li Jia; Bin Han; Haixia Sui; Jiabin Guo (Environmental Pollution, 2025)

Emerging biotechnological strategies advancing biological lignin valorization towards polyhydroxyalkanoates - Hai-Yuan Jia; Tao Xu; Chen Wang; Hong-Wei Zhu; Bing-Zhi Li; Ying-Jin Yuan; Zhi-Hua Liu (Bioresource Technology, 2025)

Skeletal muscle-specific Bambi deletion induces hypertrophy and oxidative switching coupling with adipocyte thermogenesis against metabolic disorders - Xiangping Yao; Xudong Mai; Ye Tian; Yifan Liu; Guanghui Jin; Ze Li; Shujie Chen; Xiaoshuang Dai; Liujing Huang; Zijing Fan; Guihua Pan; Xiaohan Pan; et al. (Science China Life Sciences, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Sonneralignan A, a new lignan from the fruit of mangrove Sonneratia apetala - Yue-Yao Li; Jia-Lang Xia; Meng Bai; Kai Liu; Jin-Hua Wei; Zu-Ran Lv; Yong-Hong Liu; Cheng-Hai Gao; Xiang-Xi Yi (Natural Product Research, 2025)

Effect of food addiction of lysine on feeding habit in fish - Hong-Liang Lu; Yun-Liang Miao; Jia-Ming Zou; Zi-Jun Hu; Ying-Cen Li; Xu-Fang Liang; Shan He (Aquaculture, 2025)

Bicyclic polyprenylated acylphloroglucinol-related meroterpenoids as potent DRAK2 inhibitors from Hypericum patulum - Jin-Chang Huang; Xin-Yu Jia; Yi-Fan Lv; Hong-Hong Xu; Ming Han; Qiang-Qiang Yu; Yu-Ting Lu; Hong-Xun Yang; Yang Yang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Three new maaliane-type sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Sheng-Run Guo; Hou Zhu; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry Letters, 2025)

Anchoring multi-mechanism coupled miniature redox reactors with photothermal foam gels for simultaneous photoreduction U(VI) and interfacial evaporation from wastewater - Jia-Liang Yang; De-Bin Ji; Heng-Yu Tan; Zhi-Qiang Qiao; Zhi-Da Li; Dan-Dan Yuan; Hong-Jun Wu (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Widely targeted metabolomics analysis reveals dynamic changes in metabolites of 'Hass' avocado during postharvest ripening period - Ying Xin; Na Li; Hong-Tao Zhu; Ya-Zhi Li; Han-Zhang Xiang; Jia-Huan Shang; Man Zhang; Ying-Jun Zhang (Food Chemistry, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

The structures of two polysaccharides from Fructus Corni and their protective effect on insulin resistance - Guang-Yuan Ma; Lu-Kuan Hou; Jia-Hui Guo; Jing-Chun Sun; Qiuna Nong; Yu-Fan Wang; Sheng-Wei Hu; Wen-Jing Zhao; Jin Tan; Xiao-Feng Liu; Yuan Guo; Bo-Jing Zhang; et al. (Carbohydrate Polymers, 2025)

The Effect of Cuproptosis-Related Proteins on Macrophage Polarization in Mesothelioma is Revealed by scRNA-seq - Jia-Xin Xu; Li-Jing Ma; Li-Ying Tu; Qi-Sheng Tang; Bian Wu; Li-Hong Jiang (Biological Trace Element Research, 2025)

Exploring eutrophic effects of marine sediments underneath fish cage farms: Insights from changes in eukaryotic and bacterial communities and volatile organic compounds - Fa-Guo Wan; Yong-Long Chen; Jia-Lang Zheng; Wang-Yang Jin; Tian-Hong Chen; Qing-Ling Zhu; Qing-Hao Zhan; Li-Hua Jiang; Shun Chen; Wei-Hua Song; Xiao-Jun Yan (Science of The Total Environment, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

Deciphering the inhibition mechanisms of microplastics on the full-stage sludge anaerobic digestion via enrichment to anaerobic microbes and toxicity of released compounds - Zixuan Zhang; Peng Liu; Taishuo Zhang; Kai Li; Xiaowei Wu; Hong Qiang; Hanzhong Jia; Lingyan Zhu (Journal of Hazardous Materials, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Late Quaternary vertical throw rates along the Gyaring Co fault in central Tibet - Duo Wang; Lichun Chen; Hong Chang; Shugang Kang; Yongshun Jia; Jinhua Du; Fei Han; Yanbao Li; Gongming Yin; Wenjun Zheng; Xulong Wang (Journal of Asian Earth Sciences, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Dual physically crosslinked azobenzene liquid crystal elastomers programmable for multi-modal information encryption - Jia-Xin Yang; Xue-Li Zhang; Lu Yin; Jie Jiang; Ting Liu; Jing-Yu Liu; Zhi-Ting Xu; Hong-Yuan Bai; Hong-Wei Ma; Yue Zhao; Yang Li; Li Han (Chemical Engineering Journal, 2025)

Long-term distribution and evolution trends of absorption aerosol optical depth with different chemical components in global and typical regions - Hujia Zhao; Ke Gui; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Xiaofang Jia; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Differences in plant responses to nitrogen addition between the central and edge populations of invasive Galinsoga quadriradiata in China - Xing-Jiang Song; Xin-Di Li; Yu Chen; Jia Wang; Jia-Bin Zou; Zhi-Hong Zhu; Gang Liu (Journal of Plant Research, 2025)

Encapsulation of fluorescent carbon dots into mesoporous SiO2 colloidal spheres by surface functionalization-assisted cooperative assembly for high-contrast latent fingerprint development - Wenbo You; Linyunuo Lai; Jiahui Li; Yingying Zhao; Jie Tian; Liwu Zhang; Jia Hong Pan (Chemosphere, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

LSTM-based proxy model combined with wellbore-reservoir coupling simulations for predicting multi-dimensional state parameters in depleted gas reservoirs - Jinyong Zhang; Yi Hong; Lizhong Wang; Xiaochun Li; Hongwu Lei; Fangfang Li; Bo Gao; Jia-nan Zheng (Computers & Geosciences, 2025)

Subduction-collision and rapid uplift of the NW Yangtze Block during the Ediacaran-Cambrian transition: new evidence from the shoshonite series - Qi Deng; Zheng-Jiang Wang; Hao Liu; Shuang-Jian Li; Jia-Hong Liu; Qi-Yu Wang; Jia-Shan Lin; Xiao-Wei Lan (International Geology Review, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Shear strain prediction of reservoir landslide based on FBG monitoring and bagging-MLP algorithm - Jia Wang; Hong–hu Zhu; Xiao Ye; Feng Tian; Wei Zhang; Hou–zhi Li; Hua–fu Pei (Bulletin of Engineering Geology and the Environment, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Comparison of water quality, planktonic community, and volatile organic compounds in the seawater from five cage culture areas of large yellow croaker - Jia-Lang Zheng; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Regulating self-assembly of concomitant isotropic Ag78 and anisotropic Ag110 nanoclusters - Xin-Lan Peng; Shuo Huang; Yu-Jing Zhao; Xi-Ming Luo; Hai-Yang Li; Jia-Hua Hu; Jia-Hong Huang; Shuang-Quan Zang (Science Bulletin, 2025)

Sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Min Tan; Li-Zhong Wang; Jun-Jie Hao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2025)

Aero-elastic characteristics of a wing in different proximity to the free surface - Ying-Hong Li; Shi-Li Sun; Hui-Long Ren; Jian Hu; Jia-Wei Chen (Ocean Engineering, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Radiofrequency affects the decrystallization efficiency and physicochemical properties of rape honey via crystal structure modification and inactivating enzyme - Shi-Ye Luo; Jia-Li Tao; Yan-Xiang Bi; Hong-Wei Xiao; Hua-Lei Chen; Xiang-Xin Li; Yin-Chen Wang; Xiao-Ming Fang (Food Chemistry, 2025)

Effect of chickpea protein modified with combined heating and high-pressure homogenization on enhancing the gelation of reduced phosphate myofibrillar protein - Yu Wang; Jia-le Wang; Ke Li; Jing-jing Yuan; Bo Chen; Yun-tao Wang; Jun-guang Li; Yan-hong Bai (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Enhanced dechlorination for multi-source solid wastes using gas-pressurized torrefaction and its removal mechanism - Jia Fu; Linlin Yi; Kaiyuan Li; Yan Zhang; Tong Zhang; Aijun Li; Tianrun Wang; Yanyan Zou; Xian Li; Hong Yao (Chemical Engineering Journal, 2025)

Unveiling additive-driven crystallization-kinetics control for efficient ultrapure red perovskite light emitting diodes - Tao Sheng; Yulin Mao; Jia Guo; Guangbao Wu; Junmin Xia; Zhipeng Zhang; Bingzhe Wang; Shengwen Li; Peiyuan Pang; Miao Zeng; Wei Hong; Dejian Yu; et al. (Chemical Engineering Journal, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

A comprehensive review on the application of neural network model in microbial fermentation - Jia-Cong Huang; Qi Guo; Xu-Hong Li; Tian-Qiong Shi (Bioresource Technology, 2025)

Inhibition of CB1R in the Hypothalamic Paraventricular Nucleus Ameliorates Hypertension Through Wnt/β-Catenin/RAS Pathway - Hong-Li Gao; Yu Yang; Hua Tian; Li-Yan Fu; Kai-Li Liu; Xiu-Yue Jia; Xiao-Lian Shi; Yu-Ming Kang; Xiao-Jing Yu (Cardiovascular Toxicology, 2025)

Evaluation of a transgenic tg(Hspa8b: GFP) Nile tilapia for monitoring of stress and anti-stress effects of the influence of temperature and vibration - Zhi Lei Yao; Jia Yue Li; Xiao Wang; Hong Ju Chen; Shi-Jin Jiang; Yan Zhao; Xiang Shan Ji (Aquaculture International, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Corrigendum: Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)

Potassium status and the risk of type 2 diabetes, cardiovascular diseases, and mortality: a meta-analysis of prospective observational studies - Yahui Fan; Min Wu; Lu Ding; Huixin Ji; Jinping Zhao; Xiaohui Li; Zhaofang Li; Sijiao Liu; Hong Jiang; Jia Shi; Haoyuan Lei; Mingxu Wang; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Anti-photoaging activity of triterpenoids isolated from Centella asiatica - Yi-yun Dang; Tao Liu; Yu-die Liu; Jia-yi Li; Yi Jing; Miao-jie Yang; Han Zhang; Miao-miao Jiang; Hong-hua Wu; Wen-zhi Yang; Nan Li; Peng Zhang (Phytochemistry, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Mechanism of membrane fouling mitigation by microalgae biofilm formation for low C/N mariculture wastewater treatment: EPS characteristics, composition and interfacial interaction energy - Yanbo Liu; Jing Zhu; Weirun Li; Binghan Xie; Guoyu Zhang; Yi Ding; Feng Liu; Haili Tan; Yuhong Jia; Hong You; Zhipeng Li (Journal of Environmental Chemical Engineering, 2024)

Meet-in-metabonomics: Insights into associations between hair heavy metal and adverse child growth in e-waste recycling area - Hong-Xuan Kuang; Meng-Yang Li; Jia-Rong Wang; Jian-Hua Tan; Wen-Yao Liang; Yang Zhou; Yun-Jiang Yu (Environmental Pollution, 2024)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Scalable and sustainable remediation of OPD-contaminated aquifer via amphipathic multi-component covalent organic polymers - Aiyuan Jia; Yongsheng Zhao; Jiahao Xing; Zhi Liu; Junhong Gu; Mei Hong; Yangxue Li (Chemical Engineering Journal, 2024)

Partitioned granular sludge coupling with membrane-aerated biofilm reactor for efficient autotrophic nitrogen removal - Ning Mei; Fangxu Jia; Hui Wang; Zhifeng Hu; Baohong Han; Yao Chen; Xingcheng Zhao; Xiangyu Han; Jingjing Zhang; Dongmei Li; Hong Yao; Jianhua Guo (Bioresource Technology, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Antennal transcriptome analysis of Psyttalia incisi (silvestri) (Hymenoptera: Braconidae): identification and tissue expression profiling of candidate odorant-binding protein genes - Deqing Yang; Dongliang Li; Lili Jiang; Jia Lin; Guoqing Yue; Kang Xiao; Xuxing Hao; Qinge Ji; Yongcong Hong; Pumo Cai; Jianquan Yang (Molecular Biology Reports, 2024)

Magnetic adsorbents for removal of bisphenol A: Design strategies of materials and adsorption mechanisms - Ruobing Jia; Yingying Zhang; Shunying Li; Jun Wang; Jun Kang; Qiangqiang Xu; Hong Ye (Chemosphere, 2024)

Super-large diameter slurry shield tunnel encountering boulder formation: Detection, treatment and data analysis - Wei-Hong Yang; Dong Su; Xing-Tao Lin; Zhi-Jia Lv; Zhan-Hu Yao; Hui Li; Ya-Zhou Zhang; Xiang-Sheng Chen (Transportation Geotechnics, 2024)

Manure application enriches phage-associated antimicrobial resistance and reconstructs ecological network of phage-bacteria in paddy soil - Jia-Ying Wang; Xin-Li An; Hong-Mei Zhang; Jian-Qiang Su (Soil Biology and Biochemistry, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Screening and tentatively identifying of volatile hazards of desiccant and deoxidizer in food package - Hongyi Liu; Rui Fan; Siting Li; Hong Zhang; Zhou Chen; Aijin Ma; Yingmin Jia (Food Control, 2024)

CDKN1A promotes Cis-induced AKI by inducing cytoplasmic ROS production and ferroptosis - Qian Gao; Jun-ming Chen; Chen-sui-zi Li; Jia-yi Zhan; Xue-dong Yin; Ben-shang Li; Hong-liang Dong; Lian-xiang Luo; Zhi-ling Li (Food and Chemical Toxicology, 2024)

Characterization, expression and functional analysis of Hsp40 during LPS challenge in blood parrot Amphilophus citrinellus ×Vieja melanura - Jie-Li Cai; Jun-Jie Wang; Yue Zhang; Hui Gao; Wei Huang; Yi-Jie Cai; Wei-Xin Jia; Xiao Chen; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Planting halophytes increases the rhizosphere ecosystem multifunctionality via reducing soil salinity - Jin-Peng Hu; Yuan-Yuan He; Jian-Hong Li; Zhao-Long Lü; Yue-Wei Zhang; Yuan-Hong Li; Jia-Lü Li; Ming-Xu Zhang; Yan-Hua Cao; Jin-Lin Zhang (Environmental Research, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Transferring red mud to efficient adsorbent for the adsorption and immobilization of Ni(Ⅱ) from aqueous solution - Wei Zhong; Xintong Li; Xin Ma; Zhanfang Cao; Hong Zhong; Jia Yang; Shuai Wang (Colloids and Surfaces C: Environmental Aspects, 2024)

Phase change thermal interface film with bicontinuous and textured filler network for efficient wearable heat dissipation - Jia-Qing Zhao; Xiang Wang; Xun-Rui Wang; Hong-Wei Zhao; Mei-Na Lu; Wayne-Qiang Xu; Hong-En Nian; Jin-Hong Li (Chemical Engineering Journal, 2024)

Study on the effects of electrode volume fraction and electrode particle radius on dynamic electrochemical-thermal-aging coupling characteristics of lithium cell based on cylindrical cell design method - Xu-Dong Yuan; Zhen-Kai Xiong; Lian-Cheng Li; Chuan-Ye Tang; Qi-Wei Jia; Hong-Chuan Tuo; Yan Zhang (Chemical Engineering Journal, 2024)

Asymmetric structural strategy enables efficient MR-TADF emitters with low efficiency roll-off and doping-concentration insensitivity - Zhang-Li Cheng; Jie Li; Hui Wang; Feng Huang; Ying-Chun Cheng; Hao Wu; Xin Xiong; Tong-Yuan Zhang; Jia Yu; Jun Ye; Kai Wang; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Fabrication of thermo-responsive microcapsule pesticide delivery system from maleic anhydride-functionalized cellulose nanocrystals-stabilized pickering emulsion template - Jun Li; Chao Wu; Hong-jun Xu; Jia-wei Ding; Yong-jiang Li; Hui Jiang; Hui-fen Su; Sheng Chen; Xin Li; Muhammad Asif Javaid; De-qiang Li (Carbohydrate Polymers, 2024)

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

Circ-Bptf Ameliorates Learning and Memory Impairments via the miR-138-5p/p62 Axis in APP/PS1 Mice - Hong-Fang Wang; Yi-Bo Li; Zi-Yu Liu; Wen-Meng Xie; Qing Liu; Run-Jiao Zhang; Wen-Yu Wang; Jia-Xin Hao; Lei Wang; Dan-Dan Geng (Molecular Neurobiology, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Machine learning for high-precision simulation of dissolved organic matter in sewer: Overcoming data restrictions with generative adversarial networks - Feng Hou; Shuai Liu; Wan-Xin Yin; Li-Li Gan; Hong-Tao Pang; Jia-Qiang Lv; Ying Liu; Hong-Cheng Wang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Environmental–economic total factor productivity of vegetable production in China from the life cycle perspective - Tianzuo Zhang; Yuke Jia; Ke Ren; Shuo Wang; Ziheng Li; Wei Chen; Jinglan Hong (Journal of Cleaner Production, 2024)

Novel dual-photoelectrode Z-scheme PEC system for efficient TBBPA removal and debromination: Performance and promoting mechanism - Haoran Leng; Wenqian Li; Zhiying Lv; Zhipeng Li; Guoyu Zhang; Yuhong Jia; Hong you (Journal of Cleaner Production, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Novel Cu(I)/Cu(II) oxide nanowires electrode with efficient cyclic catalytic performance for electroreduction of nitrate wastewater to ammonia - Ye Du; Wenjie Liu; Changhui Zhou; Chaoyue Xie; Zhinan Dai; Jie Wang; Jia Lin; Jinhua Li; Hong Zhu; Jing Bai; Baoxue Zhou (Journal of Environmental Chemical Engineering, 2024)

A Janus evaporator based on Donnan effect for efficient solar thermal desalination - Hai-Tao Ren; Hong-Bei He; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin (Desalination, 2024)

Recent advances in micro/nano-robots for environmental pollutant removal: Mechanism, application, and prospect - Jia-yi Hou; Hong-tao Liu; Li-ting Huang; Shu-biao Wu; Zu-lin Zhang (Chemical Engineering Journal, 2024)

Fenton chemistry activation in metal-organic frameworks for synergistic bacteria eradication - Jiayi Qin; Jia Su; Hong Li; Ling Zhang; Ling Zhang; Ke Jiang (Chemical Engineering Journal, 2024)

Meteorology-driven trends in PM2.5 concentrations and related health burden over India - Xueqing Wang; Jia Zhu; Ke Li; Lei Chen; Yang Yang; Yongqi Zhao; Xu Yue; Yixuan Gu; Hong Liao (Atmospheric Research, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)
The coral reefs along Pakistan’s coastline are of ecological and economic significance. However, they are increasingly threatened by anthropogenic threats and climate change. These vulnerable ecosystems are declining due to various factors such as sedimentation, climate change, overfishing, destructive fishing practices, marine pollution, and tourism development. We found that 29%, 24%, 26%, 16% and 18% of the studies exceeding, marine pollution, overfishing/destructive fishing, coastal tourism, climate change and sedimentation, respectively; thus, indicating inadequate water quality status in part of Pakistan coastal water. These influences lead to several negative impacts, such as jeopardized coral health, decline in biodiversity, and the simplification of reef structures. In response to these threats, conservation efforts are imperative. This literature review provides an in-depth analysis of anthropogenic threats, climate change and the conservation of coral reefs in Pakistan. This review provides suggestions on how the country could better conserve its coral reef ecosystem. These include (1) initiatives such as establishing marine protected areas (MPAs), (2) encouraging sustainable fishing practices and reducing pollution, (3) developing the country as an ecotourism destination and implementing climate change adaptation measures, and (4) community engagement through awareness campaigns and fostering collaboration among, governmental organizations, non-governmental organizations (NGOs) and scientists. These comprehensive conservation policies address human-caused and other challenges, safeguarding their ecological, economic, and cultural relevance for future generations.

Three new furanones from endophytic fungus Hypoxylon vinosopulvinatum DYR-1-7 from Cinnamomum cassia with their antifungal activity - Jia Lv; Hong Zhou; Limei Dong; Hao Wang; Li Yang; Haiqian Yu; Peixi Wu; Le Zhou; Quan Yang; Yongqian Liang; Bi Luo (Natural Product Research, 2024)

Associations between exposure to brominated flame retardants and periodontitis in U.S. adults - Jia-jie Lv; Shu-yue Li; Xiang-meng Kong; Yan Zhao; Xin-yu Li; Hong Guo; Chu Feng; Cheng-hao Yang (Chemosphere, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Understanding the extreme differentiation of granitic magmas through elemental geochemistry and Fe isotope signatures - Xiang-Long Luo; Chang-Zhi Wu; Jia-Xin She; Matthew J. Brzozowski; De-Hong Du; Shichao An; Weiqiang Li (Geochimica et Cosmochimica Acta, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

A multi-spatial scale analysis of anthropogenic nitrogen and phosphorus inputs in a large river basin: environmental effect and policy impact - Chenning Deng; Zeqian Zhang; Chaozheng Zhang; Rui Xu; Chong Nie; Qingjia Meng; Tiansen Zou; Hong Li; Jia Wu; Queping Yang (Regional Environmental Change, 2024)

Prevalence and Antibiotic Resistance Patterns of Methicillin-Resistant Staphylococcus aureus (MRSA) in a Hospital Setting: A Retrospective Study from 2018 to 2022 - Tian Lan; Bin Zhang; Jin Lu Liu; Qian Jia; Jing Gao; Liang Cao; Juan Yan; Bao Liang Li; Xiao Juan Xie; Yu Huan Xu; Hong Mei Wen (Indian Journal of Microbiology, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Temperature dependence of the rain-gas and snow-gas partition coefficients for nearly a thousand chemicals - Pu-Fei Yang; Wan-Li Ma; Hang Xiao; Kaj M. Hansen; Liang Wang; Jing-Jing Sun; Li-Yan Liu; Zi-Feng Zhang; Hong-Liang Jia; Yi-Fan Li (Chemosphere, 2024)

Effect of different concentrations of carbonate on growth performance, intestinal health and hepatic lipid metabolism of Crucian carp - Xin-yu Lei; Xue Cao; Jia Sun; Chengcheng Bi; Xin Wang; Yue-hong Li (Aquaculture, 2024)

Metabolomics profile of selenium-enriched Bacillus subtilis alleviating perfluorohexanoic acid-induced brain damage in Carassius auratus and its response to the intestinal microbial community - Xue Jiao; Ning Wang; Lei Guo; Zheng-yao Guo; Xian-wei Hou; Yu-qian Lu; Bao-lan Yao; Jia Sun; Yue-hong Li (Aquaculture, 2024)

Serum miR-192–5p is a promising biomarker for lethal radiation injury - Meng Jia; Zhanyu Wang; Xin Liu; Hong Zhang; Ying Fan; Dan Cai; Yaqiong Li; Liping Shen; Zhidong Wang; Qi Wang; Zhenhua Qi (Toxicology Letters, 2024)

Fangchinoline inhibits mouse oocyte meiosis by disturbing MPF activity - Shi-Cai Gao; Ming-Zhe Dong; Bing-Wang Zhao; Sai-Li Liu; Jia-Ni Guo; Si-Min Sun; Yuan-Yuan Li; Yuan-Hong Xu; Zhen-Bo Wang (Toxicology in Vitro, 2024)

Safety and environmental protection application of high performance solid waste unburned ceramsite and its lightweight high strength concrete - Kai-jing Tang; Hong-na An; Chuan-bei Liu; Ying-ding Li; Lu-jun Jia; Yun Tang; Qi-qiang Wang; Yong Jiang; Zi-jian Song (Sustainable Chemistry and Pharmacy, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Cevanine-type steroidal alkaloids from the bulbs of Fritillaria cirrhosa D. Don - Hui-wen Dong; Shu-hui Wang; Tse Wai Ming; Shao-bing Fu; Yun-hu Zhang; Jia-wei Li; Qing-ying Zhang; Peng-fei Tu; Hong Liang (Phytochemistry, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Screening and identification of selenium-enriched purine-lowering Lactobacillus plantarum and Lactococcus lactis with high stress tolerance and antioxidant capacity - Jia-Jun Liao; Cai-Yue Tan; Lan Liang; Yi-Zhen Luo; Hong-Lin Li; Yan-Yi Chen; Xiao-Dong Pei; Cheng-Hua Wang (Food Bioscience, 2024)

Synergetic catalysis of bimetallic sites in CoNi alloys in-situ encapsulated N-doped CNTs to accelerate sulfur redox kinetics for lithium-sulfur batteries - Jia Li; Guixiang Zhong; Jingyi Zhou; Shouyu Hong; Ji Yu; Zhenyu Yang; Ze Zhang (Chemical Engineering Journal, 2024)

Promotion of lignin depolymerization and cellulose utilization via the coupling effects of DDQ pre-oxidation and HCOOH extraction - Jiamin Ye; Haipeng Yu; Zhiwen Jia; Wanyu Li; Linghao Li; Hong Wang; Enchen Jiang; Yan Sun; Xiwei Xu (Chemical Engineering Journal, 2024)

Nighttime ozone excess days and the associated meteorological conditions in the North China Plain from 2015 to 2022 - Jia Xue; Hong Liao; Jiandong Li (Atmospheric Environment, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

MARCH5 promotes aerobic glycolysis to facilitate ovarian cancer progression via ubiquitinating MPC1 - Ying Xu; Shuhua Zhao; Yujie Shen; Yuanfeng Li; Yinghui Dang; Fenfen Guo; Zhihao Chen; Jia Li; Hong Yang (Apoptosis, 2024)
MARCH5 is a ring-finger E3 ubiquitin ligase located in the outer membrane of mitochondria. A previous study has reported that MARCH5 was up-regulated and contributed to the migration and invasion of OC cells by serving as a competing endogenous RNA. However, as a mitochondrial localized E3 ubiquitin ligase, the function of MARCH5 in mitochondrial-associated metabolism reprogramming in human cancers remains largely unexplored, including OC. We first assessed the glycolysis effect of MARCH5 in OC both in vitro and in vivo. Then we analyzed the effect of MARCH5 knockdown or overexpression on respiratory activity by evaluating oxygen consumption rate, activities of OXPHOS complexes and production of ATP in OC cells with MARCH5. Co-immunoprecipitation, western-blot, and in vitro and vivo experiments were performed to investigate the molecular mechanisms underlying MARCH5-enhanced aerobic glycolysis s in OC. In this study, we demonstrate that the abnormal upregulation of MARCH5 is accompanied by significantly increased aerobic glycolysis in OC. Mechanistically, MARCH5 promotes aerobic glycolysis via ubiquitinating and degrading mitochondrial pyruvate carrier 1 (MPC1), which mediates the transport of cytosolic pyruvate into mitochondria by localizing on mitochondria outer membrane. In line with this, MPC1 expression is significantly decreased and its downregulation is closely correlated with unfavorable survival. Furthermore, in vitro and in vivo assays revealed that MARCH5 upregulation-enhanced aerobic glycolysis played a critical role in the proliferation and metastasis of OC cells. Taken together, we identify a MARCH5-regulated aerobic glycolysis mechanism by degradation of MPC1, and provide a rationale for therapeutic targeting of aerobic glycolysis via MARCH5-MPC1 axis inhibition.

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Image-based volume estimation for food in a bowl - Wenyan Jia; Boyang Li; Qi Xu; Guangzong Chen; Zhi-Hong Mao; Megan A. McCrory; Tom Baranowski; Lora E. Burke; Benny Lo; Alex K. Anderson; Gary Frost; Edward Sazonov; et al. (Journal of Food Engineering, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Seasonal variations and sources of atmospheric EPFRs in a megacity in severe cold region: Implications for the influence of strong coal and biomass combustion - Shi-Ming Jia; Mei-Hong Chen; Pu-Fei Yang; Liang Wang; Guo-Ying Wang; Li-Yan Liu; Wan-Li Ma (Environmental Research, 2024)

Tetrabromobisphenol-A/S and their derivatives in surface particulates from workshop floors of three representative e-waste recycling sites in China - Hui Yang; Xiao-Jun Luo; Jia-Zhuo He; Yan-Hong Zeng; Bi-Xian Mai; Li-Zhong Wang; Xiang Bi (Environmental Research, 2024)

The full utilization of bagasse via deep eutectic solvent pretreatment for low-condensed lignin and cellulose smart indicator film - Wanyu Li; Jiamin Ye; Zhiwen Jia; Haipeng Yu; Linghao Li; Hong Wang; Enchen Jiang; Yan Sun; Xiwei Xu (Chemical Engineering Journal, 2024)

The basic chemical substances of total alkaloids of Menispermi Rhizoma and their anti-inflammatory activities - Yang Hong; Zhen-Fei Song; Jia-Xu Qin; Yan-Wei Li; Xin Fang; Shuang Liang (Natural Product Research, 2024)

Simulation of the dynamic processes of microplastic suspension and deposition in a lake sediment–water system - Bo Li; Jinping Peng; Bin Hong; Bowen Li; Qunpo Jia; Yongyang Wang; Yanpeng Cai; Zhifeng Yang (Environmental Science and Pollution Research, 2024)

Antibiotic resistome in landfill leachate and impact on groundwater - Wei-Li Jia; Min Zhang; Fang-Zhou Gao; Hong Bai; Lu-Xi He; Liang-Ying He; Ting Liu; Yu Han; Guang-Guo Ying (Science of The Total Environment, 2024)

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Unraveling the effect of combined heat and high-pressure homogenization treatment on the improvement of chickpea protein solubility from the perspectives of colloidal state change and structural characteristic modification - Yu Wang; Jing-jing Yuan; Ya-ru Zhang; Xing Chen; Jia-le Wang; Bo Chen; Ke Li; Yan-hong Bai (Food Chemistry, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Environmental Enrichment Improves the Recognition Memory in Adult Mice Following Social Isolation via Downregulation of Kv4.2 Potassium Channels - Qing Shang; Yi-Bei Dong; Le Xu; Jian-Hong Yang; Jia-Wen Li; Wei-Yi Yu; Jie Sun; Xiang Gao; Yi Huang; Xiao-Qin Zhang (Molecular Neurobiology, 2024)

Untapped rich microbiota of mangroves of Pakistan: diversity and community compositions - Rabia Bushra; Iftikhar Ahmed; Jia-Ling Li; Zhenghan Lian; Shuai Li; Ahmad Ali; Bushra Uzair; Arshia Amin; Muhammad Ehsan; Yong-Hong Liu; Wen‑Jun Li (Folia Microbiologica, 2024)

Alleviating effect of Astragalus polysaccharide on salinity-alkali stress-induced intestinal injury in hybrid crucian carp - Xin-yu Lei; Jia Sun; Cheng-cheng Bi; Xin Wang; Xue Cao; Hui-qing Wang; Yue-hong Li (Aquaculture International, 2024)

Identification of lignans as ATP citrate lyase (ACLY) inhibitors from the roots of Pouzolzia zeylanica - Jin-Long Li; Jia-Yi Jiang; Shan-Shan Gu; Lei Zhang; Yan Sun; Xue-Han Wang; Dan-Yu Li; Zhe-Yu Chen; Sheng-Shi Jiang; Wei-Zhong Zhu; Hao-Wen Jiang; Hong-Jie Zhang (Natural Product Research, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Stomatohabitans albus gen. nov., sp. nov., an oral living facultative anaerobic actinobacteria isolated form Steller sea lion, and proposal of Stomatohabitantaceae fam. nov. and Stomatohabitantales ord. nov - Zi-Wen Yang; Wen-Li Liu; Peng Zhang; Dan-Yuan Guo; Hong-Chuan Wang; Jia-Ling Li; Pan-Deng Wang; Gui-Xin Dong; Guo-Xing Nie; Wen-Jun Li (Systematic and Applied Microbiology, 2024)

Early bearing fault diagnosis for imbalanced data in offshore wind turbine using improved deep learning based on scaled minimum unscented kalman filter - Hai-Hong Tang; Kun Zhang; Bing Wang; Xiao-jia Zu; You-Yi Li; Wu-Wei Feng; Xue Jiang; Peng Chen; Qing-An Li (Ocean Engineering, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Cellular senescence mediates hexavalent chromium-associated lung function decline: Insights from a structural equation Model - Yali Zhang; Guiping Hu; Qiaojian Zhang; Shiyi Hong; Zekang Su; Li Wang; Tiancheng Wang; Shanfa Yu; Fang Yuan; Xiaojun Zhu; Guang Jia (Environmental Pollution, 2024)

Preparation of novel gallic acid-based dummy-template molecularly imprinted polymer adsorbents for rapid adsorption of dibutyl phthalate from water - Shunying Li; Yuanhao Zhou; Qiangqiang Xu; Haoxiang Chen; Shengpeng Shi; Ruobing Jia; Yingying Zhang; Hong Ye (Environmental Pollution, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Integrated analysis of transcriptome and small RNAome reveals regulatory network of rapid and long-term response to heat stress in Rhododendron moulmainense - Si-Jia Liu; Chang Cai; Hong-Yue Cai; Yu-Qing Bai; Ding-Yue Wang; Hua Zhang; Jin-Gen Peng; Li-Juan Xie (Planta, 2024)
Main conclusion The post-transcriptional gene regulatory pathway and small RNA pathway play important roles in regulating the rapid and long-term response of Rhododendron moulmainense to high-temperature stress. Abstract The Rhododendron plays an important role in maintaining ecological balance. However, it is difficult to domesticate for use in urban ecosystems due to their strict optimum growth temperature condition, and its evolution and adaptation are little known. Here, we combined transcriptome and small RNAome to reveal the rapid response and long-term adaptability regulation strategies in Rhododendron moulmainense under high-temperature stress. The post-transcriptional gene regulatory pathway plays important roles in stress response, in which the protein folding pathway is rapidly induced at 4 h after heat stress, and alternative splicing plays an important role in regulating gene expression at 7 days after heat stress. The chloroplasts oxidative damage is the main factor inhibiting photosynthesis efficiency. Through WGCNA analysis, we identified gene association patterns and potential key regulatory genes responsible for maintaining the ROS steady-state under heat stress. Finally, we found that the sRNA synthesis pathway is induced under heat stress. Combined with small RNAome, we found that more miRNAs are significantly changed under long-term heat stress. Furthermore, MYBs might play a central role in target gene interaction network of differentially expressed miRNAs in R. moulmainense under heat stress. MYBs are closely related to ABA, consistently, ABA synthesis and signaling pathways are significantly inhibited, and the change in stomatal aperture is not obvious under heat stress. Taken together, we gained valuable insights into the transplantation and long-term conservation domestication of Rhododendron , and provide genetic resources for genetic modification and molecular breeding to improve heat resistance in Rhododendron .

Molecular detection and genetic characteristics of porcine circovirus 3 and porcine circovirus 4 in central China - Lin-Qing Wang; Jia-Xin Li; Xi-Meng Chen; Xin-Yue Cao; Hong-Lei Zhang; Lan-Lan Zheng; Shi-Jie Ma (Archives of Virology, 2024)

Assessment of occurrence, partitioning and ecological risk for 144 steroid hormones in Taihu Lake using UPLC-MS/MS with machine learning model - Li Zhao; Chao Wang; Fuhong Sun; Haiqing Liao; Hong Chang; Xudong Jia (Chemosphere, 2024)

Machine-learning intervention progress in the field of organic waste composting: Simulation, prediction, optimization, and challenges - Li-ting Huang; Jia-yi Hou; Hong-tao Liu (Waste Management, 2024)

Uptake, tissue distribution, and biotransformation pattern of triclosan in tilapia exposed to environmentally-relevant concentrations - Li Yao; Yue-Hong Liu; Xi Zhou; Jia-Hui Yang; Jian-Liang Zhao; Zhi-Yong Chen (Science of The Total Environment, 2024)

Transport and health risk of legacy and emerging per-and polyfluoroalkyl substances in the water cycle in an urban area, China: Polyfluoroalkyl phosphate esters are of concern - Yueqing Zhang; Jing Meng; Yunqiao Zhou; Ninghui Song; Yaxin Zhao; Minghui Hong; Jia Yu; Li Cao; Yezhi Dou; Deyang Kong (Science of The Total Environment, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Phylogenomic analyses sheds new light on the phylogeny and diversification of Corydalis DC. in Himalaya–Hengduan Mountains and adjacent regions - Yan-Yan Liu; Jia-Liang Cao; Sheng-Long Kan; Peng-Hang Wang; Jun-Li Wang; Ya-Nan Cao; Hong-Wei Wang; Jia-Mei Li (Molecular Phylogenetics and Evolution, 2024)

Protective effects and mechanism of chemical- and plant-based selenocystine against cadmium-induced liver damage - Lin Zhang; Wen-Yao Shi; Jia-Ying Xu; Yan Liu; Shi-Jia Wang; Jia-Yang Zheng; Yun-Hong Li; Lin-Xi Yuan; Li-Qiang Qin (Journal of Hazardous Materials, 2024)

Microbial consortium degrading of organic pollutants: Source, degradation efficiency, pathway, mechanism and application - Huixiong Lü; Jia-Lu Wei; Guang-Xuan Tang; Yao-Si Chen; Yu-Hong Huang; Ruiwen Hu; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Cleaner Production, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Detection of adulteration of cumin powder by front-face synchronous fluorescence spectroscopy: The influence of the natural variation of adulterants - Jin Tan; Jia-Yuan Liu; Hong Su; Xiao-Han Yang; Hui-Fen Li (Food Control, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Incorporating etched ZnO nanoparticles to fabricate positively charged composite membrane for heavy metal removal - Hong-Fei Yan; Li-Han Luo; Zhen-Liang Xu; Yin-Xin Fang; Dibakar Pandaya; Jia-Yue Dai; Jing Liang; Sun-Jie Xu (Desalination, 2024)

SERS lateral flow strip detection of serum biomarkers for noninvasive assessment of operative microwave ablation outcomes of unresectable hepatocellular carcinoma - Xiaoming Su; Xinyu Liu; Yuzhen Ouyang; Yangcenzi Xie; Mingyang Chen; Pan Chen; Jia Liu; Minghua Wu; Chien-hong Lin; Hong Zhong; Ming Li (Chemical Engineering Journal, 2024)

Historical and future health burden attributable to PM2.5 exposure in China - Yang Bai; Lei Chen; Zijia Feng; Jia Zhu; Yixuan Gu; Ke Li; Hong Liao (Atmospheric Environment, 2024)

Genomic data and ecological niche modeling reveal an unusually slow rate of molecular evolution in the Cretaceous Eupteleaceae - Kun-Li Xiang; Sheng-Dan Wu; Lian Lian; Wen-Chuang He; Dan Peng; Huan-Wen Peng; Xiao-Ni Zhang; Hong-Lei Li; Jia-Yu Xue; Hong-Yan Shan; Gui-Xia Xu; Yang Liu; et al. (Science China Life Sciences, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Spatial and widely targeted metabolomics and anatomical analysis reveal the mechanisms associated with petal bicolor patterning of two Dendrobium species - Mei-Jing Ou; Hong-Yan Li; Han Liang; Zhen-Hai Deng; Zi-Bin Zhang; Jia-Wei Li (Brazilian Journal of Botany, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Miocene Equisetum tubers from the Wulan Basin, Northeast Qinghai-Tibetan Plateau and their paleoecological significance - Zhen-Dong Cao; Peng Zhang; Si-Hang Zhang; Yi-Hong Yang; Jia-Yi Chen; Li-Ming Liu; Xiang-Chuan Li; San-Ping Xie (Palaeoworld, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

Emerging and legacy per- and polyfluoroalkyl substances (PFAS) in fluorochemical wastewater along full-scale treatment processes: Source, fate, and ecological risk - Yueqing Zhang; Yunqiao Zhou; Ruochen Dong; Ninghui Song; Minghui Hong; Juying Li; Jia Yu; Deyang Kong (Journal of Hazardous Materials, 2024)

Efficient degradation of imidacloprid by surface discharge cold plasma: Mechanism of interaction between ROS and molecular structure and evaluation of residual toxicity - Jia-Bao Ni; Xiao-Fang Jia; Jun-Ying Zhang; Chang-Jiang Ding; Wen-Li Tian; Wen-Jun Peng; Sara Zielinska; Hong-Wei Xiao; Xiao-Ming Fang (Journal of Hazardous Materials, 2024)

The effect of lactic acid bacteria fermentation on physicochemical properties of starch from fermented proso millet flour - Tongze Zhang; Siqi Hong; Jia-Rong Zhang; Pin-He Liu; Siyi Li; Zixian Wen; Jianwei Xiao; Guirong Zhang; Olivier Habimana; Nagendra P. Shah; Zhongquan Sui; Harold Corke (Food Chemistry, 2024)

Quantitative analysis of key components in Qingke beer brewing process by multispectral analysis combined with chemometrics - Xianjiang Zhou; Li Li; Jia Zheng; Jianhang Wu; Lei Wen; Min Huang; Feng Ao; Wenli Luo; Mao Li; Hong Wang; Xuyan Zong (Food Chemistry, 2024)

Synergistic enhancement of supercapacitor performance: Modish designation of BPQD modified NiCo-LDH/NiCo2S4 hybrid nanotube arrays with improved conductivity and OH– adsorption - Hong Jia; Mengyang Wang; Mengyao Feng; Guangzhi Li; Longhua Li; Yu Liu (Chemical Engineering Journal, 2024)

Novel perspective on qualitative assessment of swine manure compost maturity using organic carbon density fractions - Jia-yi Hou; Hong-tao Liu; Li-xia Wang; Zu-lin Zhang (Bioresource Technology, 2024)

Establishment of in vitro pollen germination system in C4 model plant Foxtail Millet - Min Su; Dan Wang; Zi-Dong Li; Jian-Hong Hao; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Enhanced Beta2-band Oscillations Denote Auditory Hallucination in Schizophrenia Patients and a Monkey Model of Psychosis - Shuo Ma; Tianzhen Chen; Wenjun Jia; Jie Liu; Shihan Ding; Puzhe Li; Hong Gan; Dapeng Zhang; Shuxin Shao; Mu-Ming Poo; Min Zhao; Bomin Sun; et al. (Neuroscience Bulletin, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

An improved constrained velocity inversion algorithm for geological structures - Jing-Xuan Xiong; Zhen-Hua He; Le Li; Guamg-Ming He; Hong Liu; Lian-Jun Li; Guang-Yin Wang; En-Jia Zhang (Applied Geophysics, 2024)

Stalemate or consensus? Evolution of stakeholders’ behavioral strategies in construction land reduction in China - Jia-He Zhou; Yu-Ming Zhu; Cai-Hong Liu; Lei He; Hong-Li Lin (Environment, Development and Sustainability, 2024)

Potential mechanisms of lung injury and repair after hexavalent chromium [Cr(VI)] aerosol whole-body dynamic exposure - Changmao Long; Zekang Su; Guiping Hu; Qiaojian Zhang; Yali Zhang; Tian Chen; Shiyi Hong; Li Su; Guang Jia (Chemosphere, 2024)

Long-term PM2.5 exposure and early-onset diabetes: Does BMI link this risk? - Yalan Li; Jingjing Wu; Haibo Tang; Xinru Jia; Jie Wang; Changjiang Meng; Wei Wang; Shiqi Liu; Hong Yuan; Jingjing Cai; Jiangang Wang; Yao Lu (Science of The Total Environment, 2024)

Advances in the study of silica nanoparticles in lung diseases - Li-Hong Ao; Yun-Geng Wei; Hong-Ru Tian; Hua Zhao; Jun Li; Jia-Qi Ban (Science of The Total Environment, 2024)

Natural chalcopyrite mitigates nitrous oxide emissions in sediment from coastal wetlands - Sai Yang; Li-Jun Hou; Hong-Po Dong; Jia-Wei Zhang; Deng-Zhou Gao; Xiao-Fei Li; Yan-Ling Zheng; Xia Liang; Min Liu (Science of The Total Environment, 2024)

Nonlinear effect of NOx concentration decrease on secondary aerosol formation in the Beijing-Tianjin-Hebei region: Evidence from smog chamber experiments and field observations - Junling Li; Tianzeng Chen; Hao Zhang; Yongcheng Jia; Yangxi Chu; Yongxin Yan; Haijie Zhang; Yanqin Ren; Hong Li; Jingnan Hu; Weigang Wang; Biwu Chu; et al. (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Clerodane diterpenoids with in-vitro anti-neuroinflammatory activity from the tuberous root of Tinospora sagittata (Menispermaceae) - Jia-Qi Song; Kai-Cheng Yang; Xian-Zhe Fan; Li Deng; Yang-Li Zhu; Hong Zhou; Ya-Si Huang; Xiang-Qian Kong; Li-Jun Zhang; Hai-Bing Liao (Phytochemistry, 2024)

Iridoids and other constituents from the leaves and stems of Valeriana officinalis var. latifolia - Jia-Jin Liu; Jun-Jie Hao; Min Tan; Cai-Cen Liao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2024)

Exfoliated MXene/poly-melamine-formaldehyde composite membranes for removal of heavy metals and organics from aqueous solutions - Tian-Qi Zhang; Shuang Hao; Jun-Kai Zhao; Zhi-Qian Jia; Hong-Wei Tan; Yu Yang; Li-An Hou (Journal of Hazardous Materials, 2024)

Dual-specificity phosphatase 1 inhibits Singapore grouper iridovirus replication via regulating apoptosis in Epinephelus coioides - Jia-Yang He; Yi-Jie Cai; Yong-Xuan Li; Wei Huang; Yue Zhang; Ke-Jian Liu; Zhuo Sun; Li-Ling Dai; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Screening copy number variations in 35 unsolved inherited retinal disease families - Xiaozhen Liu; Hehua Dai; Genlin Li; Ruixuan Jia; Xiang Meng; Shicheng Yu; Liping Yang; Jing Hong (Human Genetics, 2024)
The purpose of this study was to screen Copy Number Variations (CNVs) in 35 unsolved Inherited Retinal Dystrophy (IRD) families. Initially, next generation sequencing, including a specific Hereditary Eye Disease Enrichment Panel or Whole exome sequencing, was employed to screen (likely) pathogenic Single-nucleotide Variants (SNVs) and small Insertions and Deletions (indels) for these cases. All available SNVs and indels were further validated and co-segregation analyses were performed in available family members by Sanger sequencing. If not, after excluding deep intronic variants, Multiplex ligation-dependent probe amplification (MLPA), quantitative fluorescence PCR (QF-PCR) and Sanger sequencing were employed to screen CNVs. We determined that 18 probands who had heterozygous SNVs/indels or whose parents were not consanguineous but had homozygous SNVs/indels in autosomal recessive IRDs genes had CNVs in another allele of these genes, 11 families had disease-causing hemizygous CNVs in X-linked IRD genes, 6 families had (likely) pathogenic heterozygous CNVs in PRPF31 gene. Of 35 families, 33 different CNVs in 16 IRD-associated genes were detected, with PRPF31 , EYS and USH2A the most common disease-causing gene in CNVs. Twenty-six and 7 of them were deletion and duplication CNVs, respectively. Among them, 14 CNVs were first reported in this study. Our research indicates that CNVs contribute a lot to IRDs, and screening of CNVs substantially increases the diagnostic rate of IRD. Our results emphasize that MLPA and QF-PCR are ideal methods to validate CNVs, and the novel CNVs reported herein expand the mutational spectrums of IRDs .

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Attentional impairment and altered brain activity in healthcare workers after mild COVID-19 - Keyi Lin; Yaotian Gao; Wei Ji; Yan Li; Wei Wang; Mengcheng Du; Jia Liu; Zhengyu Hong; Tao Jiang; Yuyang Wang (Brain Imaging and Behavior, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is highly transmissible and pathogenic. Patients with mild cases account for the majority of those infected with coronavirus disease 2019 (COVID-19). Although there is evidence that many patients with COVID-19 have varying degrees of attentional impairment, little is known about how SARS-COV-2 affects attentional function. This study included a high-risk healthcare population divided into groups of healthcare workers (HCWs) with mild COVID-19 (patient group, n = 45) and matched healthy HCWs controls (HC group, n = 42), who completed general neuropsychological background tests and Attention Network Test (ANT), and underwent resting-state functional magnetic resonance imaging (rs-fMRI) using amplitude of low-frequency fluctuation (ALFF) to assess altered brain activity; Selective impairment occurred in orienting and executive control networks, but not in alert network, in the patient group, and widespread cognitive impairment encompassing general attention, memory, and executive dysfunction. Moreover, the patient group had significantly lower ALFF values in the left superior and left middle frontal gyri than the HC group. SARS-COV-2 infection may have led to reduced brain activity in the left superior and left middle frontal gyri, thus impairing attentional orienting and executive control networks, which may explain the development of attentional deficits after COVID-19.

Gene Expression in Synovium of Rotator Cuff Tear Patients Determined by RNA Sequencing - Hong Qian; Jia Meng; Tao Yuan; Hui Jiang; Li Zhou; Lei Zhang; Jianning Zhao; Nirong Bao (Biochemical Genetics, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

Characteristic chromanone acids from Calophyllum membranaceum: Determination of C-3 configuration and anti-inflammatory activity - Wei Shen; Lun Li; Qing-He Liu; Jia-Min Cui; Wei Shi; Xin-Hong Shi; Xiao-Qi Zhang; Wen-Cai Ye; Xiao-Long Hu; Hao Wang (Phytochemistry, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

How human capital prevents intergenerational poverty transmission in rural China: Evidence based on the Chinese general social survey - Hong Chen; Jia Yu; Ze Zhang; Yuheng Li; Lijian Qin; Mingshuai Qin (Journal of Rural Studies, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

MALDI-ToF MS and chemometric analysis as a tool for identifying wild and farmed salmon - Yunhe Hong; Nicholas Birse; Brian Quinn; Yicong Li; Wenyang Jia; Saskia van Ruth; Christopher T. Elliott (Food Chemistry, 2024)

Conformational isomerization imparts low concentration dependence to multiple resonance thermally activated delayed fluorescence (MR-TADF) emitters - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Feng Huang; Kai Wang; Jia Yu; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Facile construction of tourmaline@MOFs composites via micron-scale electrical polarization to enhance photodegradation of gaseous formaldehyde - Jia He; Xin Yu; Xinqi Luan; Hong Li; Syed Jalil Shah; Weige Su; Zhaowei Jia; Jianmin Chen; Liqin Zhou; Jiguang Deng; Zhongxing Zhao; Zuqiang Huang; et al. (Chemical Engineering Journal, 2024)

Extreme Sn isotope fractionation in highly evolved granites - Ke-Ke Sun; Jia-Xin She; De-Hong Du; Weiqiang Li; Jun Deng (Chemical Geology, 2024)

Chromosome-scale assembly and gene editing of Solanum americanum genome reveals the basis for thermotolerance and fruit anthocyanin composition - Shuojun Yu; Yue Wang; Tingting Li; Huazhong Shi; Dali Kong; Jia Pang; Zhiqiang Wang; Huiying Meng; Yang Gao; Xu Wang; Yechun Hong; Jian-Kang Zhu; et al. (Theoretical and Applied Genetics, 2024)

The influence of Acetobacter pomorum bacteria on the developmental progression of Drosophila suzukii via gluconic acid secretion - Xiao‐Li Bing; Zi‐Jian Liang; Jia Tian; Xue Gong; Shao‐Qiu Huang; Jie Chen; Xiao‐Yue Hong (Molecular Ecology, 2024)
Insects are rich in various microorganisms, which play diverse roles in affecting host biology. Although most Drosophila species prefer rotten fruits, the agricultural pest Drosophila suzukii attacks ripening fruits before they are harvested. We have reported that the microbiota has positive and negative impacts on the agricultural pest D. suzukii on nutrient‐poor and ‐rich diets, respectively. On nutrient‐poor diets, microbes provide protein to facilitate larval development. But how they impede D. suzukii development on nutrient‐rich diets is unknown. Here we report that Acetobacter pomorum (Apo), a commensal bacterium in many Drosophila species and rotting fruit, has several detrimental effects in D. suzukii . Feeding D. suzukii larvae nutrient‐rich diets containing live Apo significantly delayed larval development and reduced the body weight of emerged adults. Apo induced larval immune responses and downregulated genes of digestion and juvenile hormone metabolism. Knockdown of these genes in germ‐free larvae reproduced Apo‐like weakened phenotypes. Apo was confirmed to secrete substantial amounts of gluconic acid. Adding gluconic acid to the D. suzukii larval diet hindered larval growth and decreased adult body weight. Moreover, the dose of gluconic acid that adversely affected D. suzukii did not negatively affect Drosophila melanogaster , suggesting that D. suzukii is less tolerant to acid than D. melanogaster . Taken together, these findings indicate that D. suzukii is negatively affected by gluconic acid, which may explain why it prefers ripening fruit over Apo‐rich rotting fruit. These results show an insect's tolerance to microbes can influence its ecological niche.

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Comparative study on characteristics of typhoon gusts in the coastal and offshore areas of the South China Sea - Qian-Jin Zhou; Lei Li; Shao-Jia Fan; Hong-Long Yang; Wei Sun; Hai-Rong Tang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

A mathematical model to simulate the release of Fe and Mn from sediments in a drinking water reservoir - Wenyan He; Jia Li; Min Chen; Hailong Sun; Linglei Zhang; Yongao Lu; Yunxiao Jia; Hong Zhang (Environmental Research, 2023)

Green fabrication of carbon dioxide-based polycarbonates with durable antimicrobial properties and UV resistance - Qing Huang; Wen-Zhen Wang; Shuang Liu; Xin-Gang Jia; Li Xia; Fang-Ling Qin; Qian Wang; Yun Liu; Hong-Jiu Li (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Thermokarst lake susceptibility assessment using machine learning models in permafrost landscapes of the Arctic - Rui Wang; Lanlan Guo; Yuting Yang; Hao Zheng; Hong Jia; Baijian Diao; Hang Li; Jifu Liu (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

The Dof transcription factor COG1 acts as a key regulator of plant biomass by promoting photosynthesis and starch accumulation - Zhuoyun Wei; Haoyong Zhang; Meng Fang; Shuyuan Lin; Mingsong Zhu; Yuxiu Li; Limin Jiang; Tianliang Cui; Yanwei Cui; Hong Kui; Liang Peng; Xiaoping Gou; et al. (Molecular Plant, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

Effect of electrohydrodynamic drying on bee pollen biochemical pathways - Jia-Bao Ni; Yin-Chen Wang; Hong-Wei Xiao; Sara Zielinska; Wen-Li Tian; Xiang-Xin Li; Wen-Jun Peng; Xiao-Ming Fang (Journal of Cleaner Production, 2023)

Whole-genome sequencing and bacteriocin purification of Lactiplantibacillus plantarum HY41 conﬁrms bactericidal and probiotic potential - Hongbiao Li; Ting Liu; Xiuqin Zhang; Zhiguo Xiong; Qing Hong; Shuang Jia; Yi Lin; Liping Wang; Yueliang Zhao (International Biodeterioration & Biodegradation, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Simultaneous extraction of C3H8 and C2H6 from ternary C3H8/C2H6/CH4 mixtures in an ultra-microporous metal–organic framework - Lan Lan; Nan Lu; Jia-Cheng Yin; Qiang Gao; Feifan Lang; Ying-Hui Zhang; Hong-Xiang Nie; Na Li; Xian-He Bu (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

A dual-mode method for detection of miRNA based on the photoluminescence and resonance light scattering - Xiaokun Wen; Jia Hua; Yadan Ding; Zhipeng Li; Hancheng Zhu; Guorui Wang; Jun Li; Xia Hong (Analytica Chimica Acta, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

HVT-vectored H7 vaccine protects chickens from lethal infection with the highly pathogenic H7N9 Avian inﬂuenza virus - Yi-qun Chen; Guan-ming Su; Jia-hao Zhang; Bo Li; Kai-xiong Ma; Xu Zhang; Li-hong Huang; Ming Liao; Wen-bao Qi (Veterinary Microbiology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Corrigendum to “Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni” [J Hazard Mater 452 (2023) 131367] - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Three-dimensional porous adsorbent based on chitosan-alginate-cellulose sponge for selective and efficient removal of anionic dyes - Zeng Wen; Die Gao; Hong Niu; Jing Lin; Zhou Li; Jia Zeng; Famin Ke; Kailian Zhang; Zhining Xia; Dandan Wang (Journal of Environmental Chemical Engineering, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Transcriptome analysis reveals the mechanism of the effect of perfluorocaproic acid exposure on brain injury in Carassius auratus - Xue Jiao; Zheng yao Guo; Jia Sun; Cheng Bi; Ai-dong Qian; Yue-hong Li (Aquatic Toxicology, 2023)

Phytochemistry, data mining, pharmacology, toxicology and the analytical methods of Cyperus rotundus L. (Cyperaceae): a comprehensive review - Bian-Xia Xue; Ru-Shang He; Jia-Xin Lai; Nana Ama Mireku-Gyimah; Li-Hua Zhang; Hong-Hua Wu (Phytochemistry Reviews, 2023)

Electroacupuncture Alleviates Neuropathic Pain by Suppressing Ferroptosis in Dorsal Root Ganglion via SAT1/ALOX15 Signaling - Kexing Wan; Min Jia; Hong Zhang; Yuye Lan; Suixi Wang; Kailing Zhang; Zixiao Wang; He Zhu; Xunan Zheng; Yi Luo; Lei Pei; Caihua Wu; et al. (Molecular Neurobiology, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

A comprehensive review of radioactive pollution treatment of uranium mill tailings - Jiayi Xin; Changshou Hong; Jia Wei; Jingwen Qie; Hong Wang; Bo Lei; Xiangyang Li; Ziqi Cai; Qian Kang; Zhiwei Zeng; Yong Liu (Environmental Science and Pollution Research, 2023)

Removing temperature drift for bee colony weight measurements based on linear regression model and Kalman filter - Bowen Jia; Fangchao Yang; Menghao Zhao; Liangyu Chu; Bingxue Chen; Honggang Li; Qingqing Li; Deng Zhang; Yunfan Li; Chuanqi Lu; Yuntao Lu; Shengping Liu; et al. (Biosystems Engineering, 2023)

Factors impacting the behavior of phytoremediation in pesticide-contaminated environment: A meta-analysis - Fang Jia; Yue Li; Qian-nan Hu; Lan Zhang; Lian-gang Mao; Li-zhen Zhu; Hong-yun Jiang; Xin-gang Liu; Yan Sun (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

PxRdl2 dsRNA increased the insecticidal activities of GABAR-targeting compounds against Plutella xylostella - Ben-Jie Li; Kun-Kun Wang; Ye Yu; Jia-Qi Wei; Jian Zhu; Jia-Li Wang; Fei Lin; Han-Hong Xu (Pesticide Biochemistry and Physiology, 2023)

Ultra-high output hybrid nanogenerator for self-powered smart mariculture monitoring and warning system - Liqiang Liu; Jun Li; Zhengxin Guan; Leilei Zhao; Zhiyu Tian; Shouchuang Jia; Hongxin Hong; Zeyu He; Haiyang Wen; Ruiyuan Huang; Hui Cui; Wei Ou-Yang; et al. (Chemical Engineering Journal, 2023)

Elevation, bedrock exposure, land use, interbedded limestone and clastic rock, and vegetation coverage dominate the spatiotemporal variability of soil erosion in karst basin - Mei Chen; Jia-yong Gao; Hong-lian Chen; Jun Jing; Rui Li (Journal of Mountain Science, 2023)

mTORC1/rpS6 and mTORC2/PKC regulate spermatogenesis through Arp3-mediated actin microfilament organization in Eriocheir sinensis - Zhen-Fang Li; Hong-Yu Qi; Jia-Ming Wang; Zhan Zhao; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2023)

Effect of gaseous pollutant and greenness exposure on mortality during treatment of newly treated tuberculosis patients: a provincial population-based cohort study - Jia-Wen Zhao; Xin-Qiang Wang; Zhen-Hua Li; Yi-Cheng Mao; Sun Zhang; Kai Huang; Cheng-Yang Hu; Xiu-Jun Zhang; Xiao-Hong Kan (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Nrf2 protects against methamphetamine-induced nephrotoxicity by mitigating oxidative stress and autophagy in mice - Wenjuan Dong; Jia Wan; Hao Yu; Baoyu Shen; Genmeng Yang; Qianyun Nie; Yan Tian; Lixiang Qin; Chunhui Song; Bingzheng Chen; Lihua Li; Shijun Hong (Toxicology Letters, 2023)

A sublethal dose of neonicotinoid imidacloprid precisely sensed and detoxified by a C-minus odorant-binding protein 17 highly expressed in the legs of Apis cerana - Yi-Lei Qiu; Fan Wu; Li Zhang; Hu-Qiang Jiang; Jin-Tao Chen; Ying-Jia Pan; Hong-Liang Li (Science of The Total Environment, 2023)

Aerobic granulation in an oxidation ditch using the residual sludge after extracting slime-extracellular polymer substances - Yan-Ru Jia; Zheng-Hong Wen; Yi-Jiang Shang-Guan; Zhi-Hua Li (Journal of Water Process Engineering, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

New insights into sulfur input induced methylmercury production and accumulation in paddy soil and rice - Yunyun Li; Nali Zhu; Wenjun Hu; Yu-rong Liu; Wen Jia; Guoming Lin; Hong Li; Yufeng Li; Yuxi Gao; Jiating Zhao (Journal of Hazardous Materials, 2023)

Life cycle environmental and cost assessment of prefabricated components manufacture - Ziyue Cheng; Tianzuo Zhang; Xinying Zhou; Ziheng Li; Yuke Jia; Ke Ren; Tianshu Xu; Changting Li; Jinglan Hong (Journal of Cleaner Production, 2023)

Carbon emission pinch analysis for shipping fuel planning considering multiple period and fuel conversion rates - Bingyuan Hong; Changhao Wang; Kangxin Zhang; Jeng Shiun Lim; Petar Sabev Varbanov; Xiaoping Jia; Mengmeng Ji; Hengcong Tao; Zheng Li; Bohong Wang (Journal of Cleaner Production, 2023)

Post-harvest ripening affects drying behavior, antioxidant capacity and flavor release of peach via alteration of cell wall polysaccharides content and nanostructures, water distribution and status - Jia-Bao Ni; Magdalena Zielinska; Jun Wang; Xiao-Ming Fang; Parag Prakash Sutar; Suo-Bin Li; Xiang-Xin Li; Hui Wang; Hong-Wei Xiao (Food Research International, 2023)

Fabrication of modified electrode by reduced graphene oxide (rGO) and polyaniline (PANI) for enhancing azo dye decolorization in bio-electrochemical systems (BESs) - Ai-Hong Chen; Yue-Jia Yang; Shuai Wang; Li-Ming Yang; Xue-Yun Gao; Dan Cui (Environmental Research, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Health Risk Assessment of Organophosphate Flame Retardants in Soil Across China Based on Monte Carlo Simulation - Mei-Hong Chen; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Archives of Environmental Contamination and Toxicology, 2023)

Climate and geochemistry at different altitudes influence soil fungal community aggregation patterns in alpine grasslands - Jia Li; Xia Wang; Jin Hong Wu; Yu Xin Sun; Yuan Ye Zhang; Yun Fei Zhao; Zheng Huang; Wen Hui Duan (Science of The Total Environment, 2023)

A new method for long-term in situ monitoring of seabed interface evolution: A self-potential probe - Zhihan Fan; Xianming Zhu; Haibo Xu; Zhiwen Sun; Hong Zhang; Xianbin Bi; Cong Hu; Dequan Lu; Zhongqiang Sun; Kai Li; Yongzheng Quan; Yonggang Jia (Ocean Engineering, 2023)

Effects of combined chickpea protein isolate and chitosan on the improvement of technological quality in phosphate-free pork meat emulsions: Its relation to modifications on protein thermal and structural properties - Yu Wang; Jing-jing Yuan; Ke Li; Jia-le Wang; Jun-guang Li; Bo Chen; Yan-hong Bai (Meat Science, 2023)

Morphology and origin of liquefaction-related sediment failures on the Yellow River subaqueous delta - Hong Zhang; Yang Lu; Xiaolei Liu; Xingyu Li; Zhenhao Wang; Chunsheng Ji; Chao Zhang; Zekun Wang; Shaodong Jing; Yonggang Jia (Marine and Petroleum Geology, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

Hierarchical pattern recognition of landform elements considering scale adaptation - Yue-xue Xu; Hong-chun Zhu; Jin-yu Li; Sheng-jia Zhang (Journal of Mountain Science, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Semi-empirical models for predicting stable water inflow and influence radius of a tunnel considering non-Darcian effect - Hong-Bin Liu; Jia-Qing Zhou; Changdong Li; Jie Tan; Di Hou (Journal of Hydrology, 2023)

Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Mariculture affects antibiotic resistome and microbiome in the coastal environment - Lu-Xi He; Liang-Ying He; Fang-Zhou Gao; Min Zhang; Jun Chen; Wei-Li Jia; Pu Ye; Yu-Wei Jia; Bai Hong; Si-Si Liu; You-Sheng Liu; Jian-Liang Zhao; et al. (Journal of Hazardous Materials, 2023)

Mining genes related to anthocyanin synthesis and regulation in different potato varieties based on comparative transcriptomics - En-fang Qi; Xiao-xia Jia; He-ping Lv; Wei Huang; Guo-hong Wen; Zhang Li; Jian-wu Li (Journal of Plant Biochemistry and Biotechnology, 2023)

Effects of phosphorus fertilizer application rate on transformation processes of phosphorus fractions in the purple alluvial soil of a riparian zone - Li-ping He; Kai-tao Jia; Dan Liu; Ke-hong Wang; Lin-Yan Duan; Jun-jie Lin (Journal of Mountain Science, 2023)

Reduction and valorization of dairy manure by organic chelating acid-assisted hydrothermal process: Dewatering performance, energy recovery, and effluent toxicity - Yihang Zhang; Yuqing Zhao; Jie Ji; Weitao Zhang; Wei Wei; Jia Li; Yue Liu; Hong Tao; He Zhang (Waste Management, 2023)

Endophytic Phthalate-degrading Bacillus subtilis N-1-gfp colonizing in soil-crop system shifted indigenous bacterial community to remove di-n-butyl phthalate - Li-Hui Liu; Jia-Yan Zhang; Guang-Xuan Tang; Yu-Hong Huang; Xiang-Qing Xie; Jun Geng; Hui-Xiong Lü; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Application of steam explosion treatment on the collagen peptides extraction from cattle bone - Hongru Zhang; Hong Liu; Liwei Qi; Xiong Xv; Xia Li; Yujie Guo; Wei Jia; Chunhui Zhang; Aurore Richel (Innovative Food Science & Emerging Technologies, 2023)

Source or sink role of an urban lake for microplastics from Guangdong-Hong Kong-Macao greater bay area, China - Bo Li; Bowen Li; Qunpo Jia; Bin Hong; Yulei Xie; Xiao Yuan; Jinping Peng; Yanpeng Cai; Zhifeng Yang (Environmental Research, 2023)

FTO-Nrf2 axis regulates bisphenol F-induced leydig cell toxicity in an m6A-YTHDF2-dependent manner - Shi-meng Zhou; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Wen-bo Yuan; Yu Shi; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

A simple and efficient protocol for transient transformation of sliced grape berries - Mao-Song Pei; Hai-Nan Liu; Charles Ampomah-Dwamena; Tong-Lu Wei; Yi-He Yu; Jia-Bing Jiao; Ying-Ying Lv; Feng Li; Hong-Chao Li; Xue-Jie Zhu; Da-Long Guo (Protoplasma, 2023)

Description of Limnobaculum eriocheiris sp. nov., an intestinal bacterium of Eriocheir sinensis, and reclassification of the genera Jinshanibacter and Insectihabitans as Limnobaculum - Nan-Nan Li; Hong-Chuan Wang; Jia-Yu Li; Wei He; Hua-Peng Xue; Tian-Heng Gao; Zhe Zhao; Dao-Feng Zhang (Antonie van Leeuwenhoek, 2023)

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Multidecadal heavy metals and microplastic deposition records in an urban lake: the ecological risk assessments and influencing factors - Bo Li; Qunpo Jia; Bowen Li; Bin Hong; Yanpeng Cai; Jinping Peng; Zhifeng Yang (Environmental Science and Pollution Research, 2023)

es-Arp3 and es-Eps8 regulate spermatogenesis via microfilaments in the seminiferous tubule of Eriocheir sinensis - Jia-Ming Wang; Zhen-Fang Li; Hong-Yu Qi; Zhan Zhao; Wan-Xi Yang (Tissue and Cell, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

The construction of synthetic communities improved the yield and quality of Salvia miltiorrhiza Bge. - Hong-M. Jia; Bo Li; Yu-R. Wu; Yun-T. Ma; Zhu-Y. Yan (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Response of occurrence in microplastics and its adsorped cadmium capacity to simulated agricultural environmental scenarios in sludge-amended soil - Xin-yu Li; Jia-yu Lin; Jun Zhang; Hong-tao Liu (Environmental Research, 2023)

Seismic response study of a steel lattice transmission tower considering the hysteresis characteristics of bolt joint slippage - Jia-Xiang Li; Jin-Peng Cheng; Chao Zhang; Chun-Xu Qu; Xiao-Hong Zhang; Wen-Qiang Jiang (Engineering Structures, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

LncRNA GNAS-AS1 knockdown inhibits keloid cells growth by mediating the miR-188-5p/RUNX2 axis - Yun Liu; Lei Li; Jia-Yao Wang; Fei Gao; Xia Lin; Shi-Shuai Lin; Zhi-Yang Qiu; Zun-Hong Liang (Molecular and Cellular Biochemistry, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Visual analysis of Alzheimer disease biomarker via low-potential driven bipolar electrode - Yi-Lei Jia; Cong-Hui Xu; Xiao-Qiong Li; Hong-Yuan Chen; Jing-Juan Xu (Analytica Chimica Acta, 2023)

Climatological diagnostics and subseasonal‐to‐seasonal predictions of Madden–Julian Oscillation events - Jie Wu; Hong‐Li Ren; Xiaolong Jia; Peiqun Zhang (International Journal of Climatology, 2023)
The Madden–Julian Oscillation (MJO) is the dominant mode of tropical intraseasonal variability, which serves as a primary source of subseasonal‐to‐seasonal (S2S) predictability. Noticeably, MJO is not always a regularly recurring cycle but is characterized by discrete episodes. In this study, considering the quasi‐consecutive actives and eastward propagating features, a standard metric is proposed to identify MJO events based on the real‐time multivariate MJO (RMM) index. The re‐identification of historical MJO events reveals that there were 5.4 MJO events each year since 1981, and the average duration of each event is about 31.5 days. More MJO events tend to occur in the boreal winter and spring, with stronger intensity, longer duration and faster propagating speed than those in the boreal summer. Furthermore, MJO events are more likely to initiate in Phases 2 and 5, with a longer lifetime than those initiating in other phases. The amplitude and propagation characteristics of MJO events are strongly modulated by the dominant modes of sea surface temperature interannual variability with a strong regional dependence. Based on hindcast datasets of six S2S models, the prediction skill for the MJO is evaluated in the perspective of individual events. The longest leading time of the skilful prediction for individual MJO events ranges from 11 to 17 days, far below the traditional recognition. This result could be attributed to the apparent prediction barrier of MJO initiation, that is, a rapid decrease in prediction skill when predictions are carried out before the initiation of MJO events. In addition, the prediction skills of MJO events depends on interannual variabilities, with relatively higher skills under the conditions of the El Niño and Indian Ocean basin warming. These findings may shed light on the complexity and challenges of profoundly understanding and skilfully predicting MJO events.

Polyketides with potential bioactivities from the mangrove-derived fungus Talaromyces sp. WHUF0362 - Huawei Lv; Haibo Su; Yaxin Xue; Jia Jia; Hongkai Bi; Shoubao Wang; Jinkun Zhang; Mengdi Zhu; Mahmoud Emam; Hong Wang; Kui Hong; Xing-Nuo Li (Marine Life Science & Technology, 2023)
Metabolites of microorganisms have long been considered as potential sources for drug discovery. In this study, five new depsidone derivatives, talaronins A-E ( 1–5 ) and three new xanthone derivatives, talaronins F–H ( 6–8 ), together with 16 known compounds ( 9–24 ), were isolated from the ethyl acetate extract of the mangrove-derived fungus Talaromyces species WHUF0362. The structures were elucidated by analysis of spectroscopic data and chemical methods including alkaline hydrolysis and Mosher’s method. Compounds 1 and 2 each attached a dimethyl acetal group at the aromatic ring. A putative biogenetic relationship of the isolated metabolites was presented and suggested that the depsidones and the xanthones probably had the same biosynthetic precursors such as chrysophanol or rheochrysidin. The antimicrobial activity assay indicated that compounds 5 , 9 , 10 , and 14 showed potent activity against Helicobacter pylori with minimum inhibitory concentration (MIC) values in the range of 2.42–36.04 μmol/L. While secalonic acid D ( 19 ) demonstrated significant antimicrobial activity against four strains of H. pylori with MIC values in the range of 0.20 to 1.57 μmol/L. Furthermore, secalonic acid D ( 19 ) exhibited cytotoxicity against cancer cell lines Bel-7402 and HCT-116 with IC 50 values of 0.15 and 0.19 μmol/L, respectively. The structure–activity relationship of depsidone derivatives revealed that the presence of the lactone ring and the hydroxyl at C-10 was crucial to the antimicrobial activity against H. pylori . The depsidone derivatives are promising leads to inhibit H. pylori and provide an avenue for further development of novel antibiotics.

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

New insight into enhanced transport of multi-component porous covalent-organic polymers with alkyl chains as injection agents for levofloxacin removal in saturated sand columns - Aiyuan Jia; Yongsheng Zhao; Zhi Liu; Fangyuan Zhang; Can Shi; Zhisheng Liu; Mei Hong; Yangxue Li (Science of The Total Environment, 2023)

New insights into the microbial-driven metal reductive dissolution for enhanced phosphorus release from iron-rich sludge - Ruo-hong Li; Wei-jun Wang; Ren-xin Zhao; Jia-yu Zhang; Lianpeng Sun; Xiao-yan Li; Bing Li (Journal of Cleaner Production, 2023)

One-step synthesis of aldehyde-functionalized dual-emissive carbon dots for ratiometric fluorescence detection of bisulfite in food samples - Cui Cui Deng; Zi Yi Xu; Zhe Sun; Jia Hao Xie; Hong Qun Luo; Nian Bing Li (Food Chemistry, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

A highly sensitive electrochemical immunosensor based on electrospun nanocomposite for the detection of parathion - Wen-jia Yin; Jing-xian Zhang; Hong Wang; Yu Wang; Xi Zeng; Zhen-lin Xu; Jin-yi Yang; Zhi-li Xiao; Bruce D. Hammock; Peng Wen (Food Chemistry, 2023)

RNA binding protein YTHDF1 mediates bisphenol S-induced Leydig cell damage by regulating the mitochondrial pathway of BCL2 and the expression of CDK2-CyclinE1 - Jing-zhi Li; Shi-meng Zhou; Wen-bo Yuan; Hong-qiang Chen; Yong Zeng; Jun Fan; Zhe Zhang; Na Wang; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Maternal exposure to 4-vinylcyclohexene diepoxide during pregnancy induces subfertility and birth defects of offspring in mice - Wei Song; Ang Li; Qian-Qian Sha; Shao-Yuan Liu; Yong Zhou; Chang-Yin Zhou; Xue Zhang; Xiao-Zhen Li; Jia-Xin Jiang; Fei Li; Chao Li; Heide Schatten; et al. (Science of The Total Environment, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Increases in ozone-related mortality in China over 2013–2030 attributed to historical ozone deterioration and future population aging - Lei Chen; Hong Liao; Jia Zhu; Ke Li; Yang Bai; Xu Yue; Yang Yang; Jianlin Hu; Meigen Zhang (Science of The Total Environment, 2023)

Integration of high-throughput phenotyping, GWAS, and predictive models reveals the genetic architecture of plant height in maize - Weixuan Wang; Weijun Guo; Liang Le; Jia Yu; Yue Wu; Dongwei Li; Yifan Wang; Huan Wang; Xiaoduo Lu; Hong Qiao; Xiaofeng Gu; Jian Tian; et al. (Molecular Plant, 2023)

Transcriptome reveals the exposure effects of CeO2 nanoparticles on pakchoi (Brassica chinensis L.) photosynthesis - Jie Hong; Siying Jia; Chao Wang; Yi Li; Feng He; Jorge L. Gardea-Torresdey (Journal of Hazardous Materials, 2023)

Applications of functional nanoparticle–stabilized surfactant foam in petroleum-contaminated soil remediation - Jia Liu; Wen-yan Li; Hong-xin Chen; Shuang-qiang Li; Li-heng Yang; Kai-ming Peng; Chen Cai; Xiang-feng Huang (Journal of Hazardous Materials, 2023)

Coupled effects of environmental conditions on the spatio-temporal variability of phytoplankton in canyon-shaped reservoirs - Ning Liao; Hong Li; Linglei Zhang; Min Chen; Jia Li; Lihua You (Journal of Cleaner Production, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

High sensitivity tactile sensors with ultrabroad linear range based on gradient hybrid structure for gesture recognition and precise grasping - Shuai Wang; Zaoxu Zhang; Bin Yang; Xin Zhang; Huiming Shang; Li Jiang; Hong Liu; Jia Zhang; PingAn Hu (Chemical Engineering Journal, 2023)

Sulfur isotope, fluid inclusions, and quartz solubility model decipher multistage hydrothermal fluids evolution and ore precipitation mechanism at the Nantai porphyry Mo deposit, Qinling, Central China - Zhong-Yu Zhang; Yin-Hong Wang; Jia-Jun Liu; Shan-Yuan Lin; Fang-Fang Zhang; Wei Zhang; Zhen-Yu Bo; Hui Zhang; Hong-Yu Li (Chemical Geology, 2023)

Spatial distribution and driving factors of sediment net nitrogen mineralization in riparian zone of the Three Gorges Reservoir - Kai-tao Jia; Li-ping He; Ke-hong Wang; Zhi-guo Yu; Li-jiao Liang; Zhuo-lin Yu; Jun-jie Lin (Journal of Mountain Science, 2023)

TET1 involved in bisphenol A induced TM3 Leydig cell toxicity by regulating Cav3.3 hydroxymethylation - Shi-meng Zhou; Wen-bo Yuan; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Chemosphere, 2023)

Large-scale testing of the mortise and tenon joint performance of the tunnel lining of prefabricated frame tunnels - Zhen Huang; Hai-wen Bai; Shao-kun Ma; Jia-wei Zhang; Yi-miao Chen; Hong-zhou Li (Tunnelling and Underground Space Technology, 2023)

Challenges and solutions to biodiversity conservation in arid lands - Yuanming Zhang; Akash Tariq; Alice C. Hughes; Deyuan Hong; Fuwen Wei; Hang Sun; Jordi Sardans; Josep Peñuelas; Gad Perry; Jianfang Qiao; Alishir Kurban; Xiaoxia Jia; et al. (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Paddy rice methane emissions across Monsoon Asia - Zutao Ouyang; Robert B. Jackson; Gavin McNicol; Etienne Fluet-Chouinard; Benjamin R.K. Runkle; Dario Papale; Sara H. Knox; Sarah Cooley; Kyle B. Delwiche; Sarah Feron; Jeremy Andrew Irvin; Avni Malhotra; et al. (Remote Sensing of Environment, 2023)

Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities - Dao-Qun Shi; Jia-Jin Liu; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Effect of gradual increase of atmospheric CO2 concentration on nitrification potential and communities of ammonia oxidizers in paddy fields - Bing-jie Ren; Li-dong Shen; Xin Liu; Jing-hao Jin; He-chen Huang; Mao-hui Tian; Yu-ling Yang; Wang-ting Yang; Jia-qi Liu; Cai-yu Geng; Hong-sheng Wu; Zheng-hua Hu (Journal of Environmental Management, 2023)

Simulation analysis of rural land use using rate of change driven by population and economic dynamics - A case study of Huangguashan village in Chongqing, China - Hong Jin; Heping Li; Jia Lee; Weitong Sun (Ecological Modelling, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Temperature-gradient-induced enhanced fog collection on polymer brush surfaces - Zheng-Hong Liang; Rui Feng; Jia-Min Wu; Dong Li; Fang Wang; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Building a satisfactory indoor environment for healthcare facility occupants: A literature review - Xiumei Shen; Hong Zhang; Ying Li; Kaichen Qu; Liang Zhao; Guangyan Kong; Wenzhao Jia (Building and Environment, 2023)

A near-infrared Fluorescent Probe Based on Dicyanisophorone for the Detection of Zinc Ions (Zn2+) in Water and Living Cells - Liqiang Yan; Cuiping Zhou; Jia Li; Hong Yang; Xiongzhi Wu; Lin Li (Journal of Fluorescence, 2023)

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

Research on Maneuverability Prediction of Double Waterjet Propulsion High Speed Planing Craft - Hua-Wei Sun; Jing-Lei Yang; Bo Liu; Hong-Wei Li; Jia-Feng Xiao; Han-Bing Sun (Journal of Marine Science and Engineering, 2022)
A mathematical model for predicting the maneuvering motion of a ship is constructed, using a planing craft with dual waterjet propulsion as the object of study. This model is based on the standard approach of the MMG (Maneuvering Modeling Group) and uses the Runge–Kutta algorithm to solve the differential equations. For the simulation of the turning and Z-shape maneuvering motion, the RANS equation is first solved using the program STAR-CCM + and then the PMM motion of the hull is simulated using the overlapping grid approach to derive the hydrodynamic derivative. The established method for predicting the ship’s maneuverability is feasible, as shown by the calculated results, which agree well with those obtained using data from the sea trials. This method was used to simulate the rudder rotation and Z-shape motion of the planing craft at medium and high speeds to predict the maneuverability index.

Body mass index–based predictions and personalized clinical strategies for colorectal cancer in the context of PPPM - Yun-Jia Gu; Li-Ming Chen; Mu-En Gu; Hong-Xiao Xu; Jing Li; Lu-Yi Wu (EPMA Journal, 2022)
Currently colorectal cancer (CRC) is the third most prevalent cancer worldwide. Body mass index (BMI) is frequently used in CRC screening and risk assessment to quantitatively evaluate weight. However, the impact of BMI on clinical strategies for CRC has received little attention. Within the framework of the predictive, preventive, and personalized medicine (3PM/PPPM), we hypothesized that BMI stratification would affect the primary, secondary, and tertiary care options for CRC and we conducted a critical evidence-based review. BMI dynamically influences CRC outcomes, which helps avoiding adverse treatment effects. The outcome of surgical and radiation treatment is adversely affected by overweight (BMI ≥ 30) or underweight (BMI < 20). A number of interventions, such as enhanced recovery after surgery and robotic surgery, can be applied to CRC at all levels of BMI. BMI-controlling modalities such as exercise, diet control, nutritional therapy, and medications may be potentially beneficial for patients with CRC. Patients with overweight are advised to lose weight through diet, medication, and physical activity while patients suffering of underweight require more focus on nutrition. BMI assists patients with CRC in better managing their weight, which decreases the incidence of adverse prognostic events during treatment. BMI is accessible, noninvasive, and highly predictive of clinical outcomes in CRC. The cost–benefit of the PPPM paradigm in developing countries can be advanced, and the clinical benefit for patients can be improved with the promotion of BMI-based clinical strategy models for CRC.

A Novel Splicing Mutation c.335–1 G > A in the Cardiac Transcription Factor NKX2-5 Leads to Familial Atrial Septal Defect Through miR-19 and PYK2 - Li Jia; Dai Limeng; Tan Xiaoyin; Wang Junwen; Zhu Xintong; Xiong Gang; Bai Yun; Guo Hong (Stem Cell Reviews and Reports, 2022)

Genome-Wide Identification Reveals the Potential Functions of the bZIP Gene Family in Common Bean (Phaseolus vulgaris) in Response to Salt Stress During the Sprouting Stage - Qi Zhang; Wen-jing Zhang; Zhen-gong Yin; Wei-jia Li; Chun-Yang Xia; Hao-Yue Sun; Yi-Ming Yang; Hong-Bin Wu; Shuo Zhang; Hao-hao Zhao; Wen-Hui Zhang; Yong-xia Guo; et al. (Journal of Plant Growth Regulation, 2022)

Correction to: MiR‑30c‑1‑3p targets matrix metalloproteinase 9 involved in the rupture of abdominal aortic aneurysms - Lin Yang; Hong‑Gang Sui; Meng‑Meng Wang; Jia‑Yin Li; Xiao‑Feng He; Jing‑Yuan Li; Xiao‑Zeng Wang (Journal of Molecular Medicine, 2022)

Effect of Iron Plaque on Gaseous Elemental Mercury Uptake, Translocation, and Volatilization by Paddy Rice - Yanlin Wang; Shuai Shang; Xin Li; Sinan Chen; Ran Li; Weiwei Jia; Hong Deng (Bulletin of Environmental Contamination and Toxicology, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Brevilaterin B from Brevibacillus laterosporus has selective antitumor activity and induces apoptosis in epidermal cancer - Zhou Chen; Lulu Wang; Yangliu Liu; Panpan Han; Dan Hong; Siting Li; Aijin Ma; Yingmin Jia (World Journal of Microbiology and Biotechnology, 2022)

Methyl Jasmonate Triggers Cadmium Detoxification in Tomato Plants via Depressing Cd2+ Influx, Altering the Subcellular Distribution, and Chemical Forms of Cadmium - Ting Wei; Yanni Sun; Hong Li; Li Hua; Xinhao Ren; Honglei Jia; Junkang Guo (Water, Air, & Soil Pollution, 2022)

mTORC1/C2 regulate spermatogenesis in Eriocheir sinensis via alterations in the actin filament network and cell junctions - Zhen-Fang Li; Shuang-Li Hao; Lan-Min Wang; Hong-Yu Qi; Jia-Ming Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

Preservation of soil organic carbon in coastal wetlands promoted by glomalin–iron–organic carbon ternary system - Bo Zhao; Yunlong Jia; Shengjie Wu; Lili Wei; Jian Li; Hualong Hong; Chongling Yan; Mark A. Williams; Qiang Wang (Limnology and Oceanography, 2022)
Iron‐bound soil organic carbon (Fe‐bound SOC) and microbial residues are vital for SOC preservation, a process crucial for drawdown of anthropogenic carbon. However, the relative importance of Fe‐bound SOC in coastal wetlands, and its interaction with microbial residues remain poorly understood. Here, we used glomalin as a proxy for microbial residues, with the goal of determining microbial residues binding to Fe and Fe‐bound SOC across a 1000 km coastline of China including seven typical mangrove wetlands. As hypothesized, it was found that the glomalin fraction was strongly associated with and likely bound to Fe‐bound SOC complexes, which accounted for 21.4% ± 1.6% of mangrove SOC. Mean level of Fe‐bound glomalin was 1.2 ± 0.1 mg cm −3 , accounting for 40.6% ± 1.5% of total glomalin and 35.4% ± 3.2% of Fe‐bound SOC in the top 10 cm mangrove soil layer at regional scale. Due to the growing realization that Fe may be a crucial factor of glomalin cycling, we performed multiple chemical characterization techniques to identify the association between Fe and glomalin. Our results suggested that association to Fe was a main stabilization mechanism of glomalin in soils, and glomalin served as organic ligands in the formation of Fe‐bound SOC. We also found that the bulk glomalin extracts were a glomalin–Fe–OC ternary complex, which constituted an important proportion of mangrove SOC. These findings highlight the important effect of glomalin bound to Fe as a major mechanism of SOC persistence in coastal wetlands.

Tetramethylpyrazine protects neural stem cells against sevoflurane-induced toxicity through Akt/GSK-3β pathway - Yan Feng; Kui Wang; Ning Wang; Pengyu Jia; Lei Zhang; Haozheng Yuan; Pan Lu; Yang Lu; Hong Zhang; Rong Li; Yan Zhang; Qianqian Li; et al. (Metabolic Brain Disease, 2022)

Differences in small-world networks between methamphetamine and heroin use disorder patients and their relationship with psychiatric symptoms - Yan Liu; Qiang Li; Tianyi Zhang; Lei Wang; Yarong Wang; Jiajie Chen; Jia Zhu; Hong Shi; Wei Wang; Wei Li (Brain Imaging and Behavior, 2022)

Aculeaquamide A, cytotoxic paraherquamide from the marine fungus Aspergillus aculeatinus WHUF0198 - Jun Wu; Fuqian Wang; Li-Ming He; Si-Yuan Zhou; Shou-Bao Wang; Jia Jia; Kui Hong; You-Sheng Cai (Natural Product Research, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Responses of absorptive root and mycorrhizal colonization of Chinese fir (Cunninghamia lanceolata) to varied environmental conditions - Ying-Chun Liao; Hou-Bao Fan; Liang Li; Xiao-Hua Wei; Hui-Min Wang; Hong-Lang Duan; Wen-Fei Liu; Jia-Li Liu (Plant Ecology, 2022)

Effects of urease-producing bacteria and eggshell on physiological characteristics and Cd accumulation of pakchoi (Brassica chinensis L.) plants - Ting Wei; Hong Li; Noman Yashir; Xian Li; Honglei Jia; Xinhao Ren; Jing Yang; Li Hua (Environmental Science and Pollution Research, 2022)

MiR-30c-1-3p targets matrix metalloproteinase 9 involved in the rupture of abdominal aortic aneurysms - Lin Yang; Hong-Gang Sui; Meng-Meng Wang; Jia-Yin Li; Xiao-Feng He; Jing-Yuan Li; Xiao-Zeng Wang (Journal of Molecular Medicine, 2022)
Abdominal aortic aneurysm (AAA) can be fatal if ruptured, but there is no predictive biomarker. Our aim was to evaluate the prognostic potential of microRNAs (miRNAs/miRs) in an AAA mouse model and patients with unruptured AAA (URAAA) and ruptured AAA (RAAA). Among the 64 miRNAs differentially expressed in mice with AAA compared to control, miR-30c-1-3p, miR-432-3p, miR-3154, and miR-379-5p had high homology with human miRNAs. MiR-30c-1-3p plasma levels were significantly lower in patients with RAAA than in those with URAAA or control and tended to negatively correlate with the maximum aortic diameter ( r = −0.3153, P = 0.06109). MiR-30c-1-3p targeted matrix metalloproteinase ( MMP)-9 mRNA through the coding region and downregulated its expression in vitro. MMP-9 plasma concentrations were significantly higher in the RAAA group than in the URAAA group ( P < 0.001) and were negatively associated with miR-30c-1-3p levels ( r = −0.3671, P = 0.01981) and positively–with the maximal aortic diameter ( r = 0.6251, P < 0.0001). The optimal cutoff values for MMP-9 expression and the maximal aortic diameter were 461.08 ng/ml and 55.95 mm, with areas under the curve of 0.816 and 0.844, respectively. Our results indicate that plasma levels of miR-30c-1-3p and MMP-9 may be candidate biomarkers of AAA progression. Key messages Downregulation of miR-30c-1-3p expression and upregulation of its potential target MMP-9 are predictors of the devastation of AAA. Downregulation of miR-30c-1-3p expression and its downstream impact on MMP-9 have a potential on predicting the development and rupture of AAA.

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Short-term effect of sulfur dioxide (SO2) change on the risk of tuberculosis outpatient visits in 16 cities of Anhui Province, China: the first multi-city study to explore differences in occupational patients - Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Wen-Jie Yu; Jie Wang; Ying-Qing Li; Xin Cheng; Zhen-Hua Li; Yi-Cheng Mao; Cheng-Yang Hu; Kai Huang; Kun Ding; et al. (Environmental Science and Pollution Research, 2022)

Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Quantitative detection of parasitic ciliate Cryptocaryon irritans in seawater with an optimized sample processing method - Jia‐Jia Tang; Zhi‐Hong Zhong; Zhi‐Cheng Li; Qing‐Kai Guo; Shi‐Yu Li; Yi‐Xuan Guo; Biao Jiang; An‐Xing Li (Journal of Fish Diseases, 2022)
The protozoan Cryptocaryon irritans is one of the most important ectoparasites of marine fish, causing ‘white spot disease’ and mass mortality in aquaculture. To accurately predict disease outbreaks and develop prevention strategies, improved detection methods are required that are sensitive, convenient and rapid. In this study, a pair of specific primers based on the C . irritans 18S rRNA gene was developed and used in a real‐time PCR (qPCR) assay. This assay was able to detect five theronts in 1 L of natural seawater. Furthermore, a linear model was established to analyse the log of Ct value and parasite abundance in seawater (y = –2.9623x + 24.2930), and the coefficient of determination (R 2 ) value was 0.979. A lysis buffer was optimized for theront DNA extraction and used for storage sample. This method was superior to the commercial water DNA kit, and there was no significant degradation of DNA at room temperature for 24–96 hr. A dilution method was developed to manage qPCR inhibitors and used to investigate natural seawater samples in a net cage farm with diseased fish, and the findings were consistent with the actual situation. This study provides a valuable tool for assisting in the early monitoring and control of cryptocaryoniasis in aquaculture.

Alternaria species causing leaf spot on hemp (Cannabis sativa) in Northern China - Hong Cheng; Lin Zhao; Xin Wei; Xi Liu; Guo-Yang Gao; Jian-Xin Deng; Mei-Jia Li (European Journal of Plant Pathology, 2022)

Functional connectivity alteration of the deprived auditory regions with cognitive networks in deaf and inattentive adolescents - Jianhong Li; Weiwei Men; Jia-Hong Gao; Yang Wang; Xiaoxia Qu; David Chao Dong Zhu; Junfang Xian (Brain Imaging and Behavior, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Algae, shrimp grazing, and fecal pellets synergistically increase microbial activity and enhance N immobilization during Typha angustifolia leaf litter decomposition - Xiangshi Kong; Can Wu; Bei Yao; Zaihua He; Hong Lin; Xingbing He; Yonghui Lin; Tingting Cao; Yanyan Jia; Yongfei Li; Kai Tian; Xingjun Tian (Environmental Science and Pollution Research, 2022)

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

Stilbenoids from the roots of Stemona tuberosa - Hong-Mei Li; Tian-Tian He; Miao Zhang; Jia-Ning Liu; Xue Zhao; Jie Liu; Lei Fang (Natural Product Research, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Delayed body development with reduced triglycerides levels in leptin transgenic pigs - Yubo Qing; Muhammad Ameen Jamal; Dejia Shi; Sumei Zhao; Kaixiang Xu; Deling Jiao; Heng Zhao; Honghui Li; Baoyu Jia; Haizhen Wang; Hong-Ye Zhao; Hong-Jiang Wei (Transgenic Research, 2022)

Responses and feedback of litter properties and soil mesofauna to herbaceous plants expansion into the alpine tundra on Changbai Mountain, China - Ying-jie Zhang; Ying-hua Jin; Jia-wei Xu; Hong-shi He; Yan Tao; Zhi-peng Yang; Jing Zhao; Yin-xia Diao; Chen-hui Sun; Mai-He Li (Journal of Mountain Science, 2022)

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

Regulatory role of miR-129 and miR-384-5p on apoptosis induced by oxygen and glucose deprivation in PC12 cell - Hui-Lin Guan; Yue Guan; Wen-Yuan Li; Jia-Wei Liu; Yu-Jia Zheng; Yan-Zhong Guan; Hong-Feng Liu; Li-Xin Guan; Feng-Guo Zhai (Experimental Brain Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Different changes in pre- and postsynaptic components in the hippocampal CA1 subfield after transient global cerebral ischemia - Yan Zhang; Bai-Hong Tan; Shuang Wu; Cheng-Hao Wu; Jia-Le Suo; Yue Gui; Cheng-Mei Zhou; Yan-Chao Li (Brain Structure and Function, 2022)

Discriminative optimization algorithm with global–local feature for LIDAR point cloud registration - Jia Wang; Ping Wang; Biao Li; Ruigang Fu; Siyi Zhao; Hong Zhang (International Journal of Remote Sensing, 2021)

MicroRNA-197-3p mediates damage to human coronary artery endothelial cells via targeting TIMP3 in Kawasaki disease - Chaowu Liu; Deguang Yang; Hong Wang; Shengwei Hu; Xiaofei Xie; Li Zhang; Hongling Jia; Qi Qi (Molecular and Cellular Biochemistry, 2021)

Astaxanthin Ameliorates Blood Pressure in Salt-Induced Prehypertensive Rats Through ROS/MAPK/NF-κB Pathways in the Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Yan Zhang; Chen-Long Wang; Yi-Ming Lei; Jia-Yue Yu; Dong-Miao Zong; Kai-Li Liu; Dong-Dong Zhang; Ying Li; Hua Tian; Nian-Ping Zhang; et al. (Cardiovascular Toxicology, 2021)

Correction to: lncRNA MEG3, Acting as a ceRNA, Modulates RPE Differentiation Through the miR-7-5p/Pax6 Axis - Hong-Jing Sun; Fang-Fang Zhang; Qing Xiao; Jia Xu; Li-Jin Zhu (Biochemical Genetics, 2021)

lncRNA MEG3, Acting as a ceRNA, Modulates RPE Differentiation Through the miR-7-5p/Pax6 Axis - Hong-Jing Sun; Fang-Fang Zhang; Qing Xiao; Jia Xu; Li-Jin Zhu (Biochemical Genetics, 2021)

Assessment of probiotic adhesion and inhibitory effect on Escherichia coli and Salmonella adhesion - Ya Wang; Dan Jia; Jia-hui Wang; He-hai Li; Jun-long Liu; Ai-hong Liu; Jin-ming Wang; Gui-quan Guan; Jian-xun Luo; Hong Yin; You-quan Li (Archives of Microbiology, 2021)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Food-grade γ-aminobutyric acid production by immobilized glutamate decarboxylase from Lactobacillus plantarum in rice vinegar and monosodium glutamate system - Li-Li Yao; Jia-Ren Cao; Chang-Jiang Lyu; Fang-Fang Fan; Hong-Peng Wang; Hong-Wei Cao; Jun Huang; Le-He Mei (Biotechnology Letters, 2021)

Water resources response and prediction under climate change in Tao’er River Basin, Northeast China - Jia-qi Sun; Hong-yan Li; Xiao-jun Wang; Shamsuddin Shahid (Journal of Mountain Science, 2021)

Future variation in mountainous discharge in arid northwestern China: A basin case study - Lei Wu; Chang-bin Li; Xu-hong Xie; Jia-nan Lv; Jian-mei Wei; Xuan Zhou; Lin-shan Yang (Journal of Mountain Science, 2021)

Study of the mechanical performance of excavation under asymmetrical pressure and reinforcement measures - Wenchao Zhang; Na Wu; Pengjiao Jia; Xiaoqi Zhou; Hong Li; Guoguang Wang (Arabian Journal of Geosciences, 2021)

Rock physics inversion based on an optimized MCMC method - Jia-Jia Zhang; Hong-Bing Li; Guang-Zhi Zhang; Yi-Peng Gu; Zhuo-Fan Liu (Applied Geophysics, 2021)

Maternal exposure to sulfur dioxide and the risk of oral clefts in Liaoning Province, China: a population-based case-control study - Fang-Hua Liu; Ze Xing; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; et al. (Environmental Science and Pollution Research, 2021)

Strong in vitro and in vivo cytotoxic effects of two platinum(II) complexes with cryptolepine derivatives - Li-Qin Qin; Zu-Zhuang Wei; Lin Yang; Qi-Pin Qin; Jia-Jing Zeng; Ming-Xiong Tan; Hong Liang (Medicinal Chemistry Research, 2021)

A novel de-rusting method with molten salt precleaning and laser cleaning for the recycling of steel parts - Xing Wang; Jianfeng Li; Liming Wang; Xiujie Jia; Minghui Hong; Yuan Ren; Mingliang Ma (Clean Technologies and Environmental Policy, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Mapping Domain- and Age-Specific Functional Brain Activity for Children’s Cognitive and Affective Development - Lei Hao; Lei Li; Menglu Chen; Jiahua Xu; Min Jiang; Yanpei Wang; Linhua Jiang; Xu Chen; Jiang Qiu; Shuping Tan; Jia-Hong Gao; Yong He; et al. (Neuroscience Bulletin, 2021)

RNA-Seq Transcriptome Analysis of the Liver and Brain of the Black Carp (Mylopharyngodon piceus) During Fasting - Ya-Fan Dai; Yu-bang Shen; Shen-Tong Wang; Jia-Hua Zhang; Yu-Hong Su; Sheng-Chen Bao; Xiao-Yan Xu; Jia-Le Li (Marine Biotechnology, 2021)

SR-B1 and CD10 combined immunoprofile for differential diagnosis of metastatic clear cell renal cell carcinoma and clear cell carcinoma of the ovary - Teng Jiang; Xiaoli Diao; Meili Ding; Xiao Niu; Chao Wang; Yan Qi; Wei Jia; Lijuan Pang; Wenhao Hu; Hong Zou; Feng Li (Journal of Molecular Histology, 2021)
Both clear cell renal carcinoma (ccRCC) and clear cell carcinoma of the ovary (CCOC) have a clear cytoplasmic morphological feature, hence it is difficult to identify metastatic ccRCC and CCOC by morphology alone. At present, there are no effective immunohistochemical markers to distinguish between these two tumors. Studies have shown that the clear cytoplasm of ccRCC is mainly caused by cholesterol-rich lipids in the cytoplasm, while that of CCOC is due to the accumulation of cytoplasmic glycogen. Objective: to hypothesize that the scavenger receptor class B-type 1 (SR-B1) protein responsible for HDL cholesterol uptake may be differentially expressed in ccRCC and CCOC, and high CD10 expression in the renal tubular epithelium may assist in distinguishing between ccRCC and CCOC. Methods: effective immunohistochemical markers were applied in 90 cases of renal clear cell carcinoma and 31 cases of ovarian cancer to distinguish between the two types of tumors.Result: SR-B1 and CD10 expression is significantly higher in ccRCC than CCOC. Both SR-B1 and CD10 exhibited focal weak-medium intensity staining in CCOC, and their staining extent and intensity were significantly lower than ccRCC. The sensitivity and specificity of SR-B1 for identifying ccRCC were 74.4% and 83.9%, respectively. The sensitivity and specificity of CD10 for identifying CCOC were 93.3% and 80.6%, respectively. The combined SR-B1( +) CD10( +) immunoprofile supports the diagnosis of ccRCC with a specificity of 93.5%. The combined SR-B1(-) CD10(-) immunoprofile supports the diagnosis of CCOC with a specificity of 93.3%. Conclusions: our findings demonstrate that the combination of SR-B1 and CD10 immunoprofiling is a valuable tool for differential diagnosis of ccRCC and CCOC.

Inhibition of the p38 MAPK pathway attenuates renal injury in pregnant rats with acute necrotizing pancreatitis - Jiacheng Zhang; Fangchao Mei; Liang Zhao; Teng Zuo; Yupu Hong; Man Li; Jia Yu; Weixing Wang (Immunologic Research, 2021)

Effects of multi-phase inoculation on the fungal community related with the improvement of medicinal herbal residues composting - Xiao-Lin Lu; Hao Wu; Shi-Li Song; Hong-Yan Bai; Meng-Jun Tang; Fang-Ji Xu; Yan Ma; Chuan-Chao Dai; Yong Jia (Environmental Science and Pollution Research, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

DeepMapi: a Fully Automatic Registration Method for Mesoscopic Optical Brain Images Using Convolutional Neural Networks - Hong Ni; Zhao Feng; Yue Guan; Xueyan Jia; Wu Chen; Tao Jiang; Qiuyuan Zhong; Jing Yuan; Miao Ren; Xiangning Li; Hui Gong; Qingming Luo; et al. (Neuroinformatics, 2021)
The extreme complexity of mammalian brains requires a comprehensive deconstruction of neuroanatomical structures. Scientists normally use a brain stereotactic atlas to determine the locations of neurons and neuronal circuits. However, different brain images are normally not naturally aligned even when they are imaged with the same setup, let alone under the differing resolutions and dataset sizes used in mesoscopic imaging. As a result, it is difficult to achieve high-throughput automatic registration without manual intervention. Here, we propose a deep learning-based registration method called DeepMapi to predict a deformation field used to register mesoscopic optical images to an atlas. We use a self-feedback strategy to address the problem of imbalanced training sets (sampling at a fixed step size in nonuniform brains of structures and deformations) and use a dual-hierarchical network to capture the large and small deformations. By comparing DeepMapi with other registration methods, we demonstrate its superiority over a set of ground truth images, including both optical and MRI images. DeepMapi achieves fully automatic registration of mesoscopic micro-optical images, even macroscopic MRI datasets, in minutes, with an accuracy comparable to those of manual annotations by anatomists.

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Correction to: P2Y12 receptor upregulation in satellite glial cells is involved in neuropathic pain induced by HIV glycoprotein 120 and 2',3'-dideoxycytidine - Zhihua Yi; Lihui Xie; Congfa Zhou; Huilong Yuan; Shuai Ouyang; Zhi Fang; Shanhong Zhao; Tianyu Jia; Lifang Zou; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2021)

Application of Phage-Displayed Peptides in Tumor Imaging Diagnosis and Targeting Therapy - Chunyan Li; Jia Li; Ying Xu; Ying Zhan; Yu Li; Tingting Song; Jiao Zheng; Hong Yang (International Journal of Peptide Research and Therapeutics, 2021)

Efficient Editing of an Adenoviral Vector Genome with CRISPR/Cas9 - Qiang Li; Hui Wang; Chen-yu Gong; Zhao Chen; Jia-xing Yang; Hong-wei Shao; Wen-feng Zhang (Indian Journal of Microbiology, 2021)

Maternal exposure to ambient SO2 and risk of polydactyly and syndactyly: a population-based case-control study in Liaoning Province, China - Yu-Ting Jiang; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; Qi-Jun Wu (Environmental Science and Pollution Research, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Observed trends of different rainfall intensities and the associated spatiotemporal variations during 1958–2016 in Guangxi , China - Nian Xiu Qin; Jun Neng Wang; Liang Gao; Yang Hong; Jia Li Huang; Qin Qin Lu (International Journal of Climatology, 2021)
In a changing climate, drought and flood hazards become more frequent, posing high risks to human life and property. The Guangxi Zhuang Autonomous Region is selected as the study area. The flood and drought records, and the daily precipitation data at 23 stations from 1958 to 2016 are adopted. The temporal and spatial trends of precipitation intensities, precipitation days and the corresponding proportions relative to the total amounts are examined using the Mann‐Kendall trend test. The influence of the rainfall intensity on floods and droughts in Guangxi is also investigated. During the past 59 years in Guangxi, there is a significant decrease in light rain, and an increase in rainstorm in general. The larger the rainfall intensity is, the more stations show increasing trends of the corresponding rain events on different time scales (the monthly, seasonal or annual scale). Significant decreasing trends of the number of days with light precipitation are found over entire Guangxi, while increasing trends of the number of days with rainstorm events are widely distributed in most parts of Guangxi. There is a decrease in the number of stations indicating increases in proportion of light precipitation days, while an increase in the number of stations showing increases in proportion of rainstorm days. A significant increase in flood hazards is detected since the 1990s. The precipitation in Guangxi tends to be intensified in the future. The frequency and intensity of drought and flood events are very likely to increase, posing challenges to future agricultural production, water resources planning and management.

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Correction to: The effect of teprenone on the intestinal morphology and microbial community of Chinese sea bass (Lateolabrax maculatus) under intermittent hypoxic stress - Hong-biao Dong; Yong-xu Sun; Ya-fei Duan; Hua Li; Yong Li; Qing-song Liu; Wen-hao Wang; Jia-song Zhang (Fish Physiology and Biochemistry, 2020)

The extract of aquatic macrophyte Carex cinerascens induced colony formation in bloom-forming cyanobacterium Microcystis aeruginosa - Lin Li; Xiao-ling Jing; Ling Wang; Zhi-gao Zeng; Wen-hong Chen; Jia-hao Zhai; Si-qin Qi (Environmental Science and Pollution Research, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Targeting glutathione with the triterpenoid CDDO-Im protects against benzo-a-pyrene-1,6-quinone-induced cytotoxicity in endothelial cells - Halley Shukla; Ho Young Lee; Ashkon Koucheki; Humaira A. Bibi; Gabriella Gaje; Xiaolun Sun; Hong Zhu; Y. Robert Li; Zhenquan Jia (Molecular and Cellular Biochemistry, 2020)

Influence of near-fault ground motion characteristics on the seismic response of cable-stayed bridges - Chao Zhang; Jian-bing Lu; Hong-yu Jia; Zhi-chao Lai; Xu Li; Pi-guang Wang (Bulletin of Earthquake Engineering, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

The effect of teprenone on the intestinal morphology and microbial community of Chinese sea bass (Lateolabrax maculatus) under intermittent hypoxic stress - Hong-biao Dong; Yong-xu Sun; Ya-fei Duan; Hua Li; Yong Li; Qing-song Liu; Wen-hao Wang; Jia-song Zhang (Fish Physiology and Biochemistry, 2020)

Transcriptome analysis of rice leaves in response to Rhizoctonia solani infection and reveals a novel regulatory mechanism - De Peng Yuan; Xiao Feng Xu; Woo-Jong Hong; Si Ting Wang; Xin Tong Jia; Yang Liu; Shuang Li; Zhi Min Li; Qian Sun; Qiong Mei; Shuai Li; Ki-Hong Jung; et al. (Plant Biotechnology Reports, 2020)

Boron availability in top- and sub-soils as affected by topography and climate - Xin Zhang; Meng-Jia Li; Lin-Qing Zhan; Wei Wu; Hong-Bin Liu (Nutrient Cycling in Agroecosystems, 2020)

OP16 induces deadly autophagy and apoptosis of cells by inhibiting Akt in esophageal squamous cell carcinoma - Guiqin Hou; Ang Jia; Li Yang; Yu Zhao; Yi Hu; Wuduo Zhao; Wen Zhao; Hong-Min Liu; Zhaoming Lu (Molecular and Cellular Biochemistry, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Holocene negative coupling of summer temperature and moisture availability over southeastern arid Central Asia - Jianyong Li; Ninglian Wang; John Dodson; Hong Yan; Xiaojian Zhang; Peter Weiming Jia; Heikki Seppä (Climate Dynamics, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Assessing drug cue-induced brain response in heroin dependents treated by methadone maintenance and protracted abstinence measures - Xuan Wei; Wei Li; Jiajie Chen; Yongbin Li; Jia Zhu; Hong Shi; Jierong Liu; Jiuhua Xue; Wei Liu; Fan Wang; Yan Liu; Shan Dang; et al. (Brain Imaging and Behavior, 2020)

Effects of an oasis protective system on aeolian sediment deposition: a case study from Gelintan oasis, southeastern edge of the Tengger Desert, China - Jing Ding; Yun-hu Xie; Xiao-jia Li; Hong-tao Jiang; Ji Wang; Xiao-xi Liu; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai (Journal of Mountain Science, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Scutellarin Exerts Anti-Inflammatory Effects in Activated Microglia/Brain Macrophage in Cerebral Ischemia and in Activated BV-2 Microglia Through Regulation of MAPKs Signaling Pathway - Hao-Lun Chen; Wen-Ji Jia; Hong-E Li; Hong Han; Fan Li; Xiao-Li-Na Zhang; Juan-Juan Li; Yun Yuan; Chun-Yun Wu (NeuroMolecular Medicine, 2020)

Genetic diversity of Prorocentrum donghaiense population during bloom in the East China Sea revealed by microsatellite - Hong-jia Huang; Chu-qiao Gan; Shao-wen Xiao; Cheng Zou; Srinivasan Balamurugan; Hong-ye Li; Jie-sheng Liu; Wei-dong Yang (Journal of Applied Phycology, 2020)

Correction to: Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)

Improved production of GTKO/hCD55/hCD59 triple-gene-modified Diannan miniature pigs for xenotransplantation by recloning - Heng Zhao; Yuying Li; Thanapa Wiriyahdamrong; Zaimei Yuan; Yubo Qing; Honghui Li; Kaixiang Xu; Jianxiong Guo; Baoyu Jia; Xuezeng Zhang; Wenmin Cheng; Yanhua Su; et al. (Transgenic Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

A Simple Approach to the Toxicity Prediction of Anilines and Phenols Towards Aquatic Organisms - Jules Muhire; Bao Qiong Li; Hong Lin Zhai; Sha Sha Li; Jia Ying Mi (Archives of Environmental Contamination and Toxicology, 2020)

Abnormal differentiation of regulatory T cells and Th17 cells induced by perinatal bisphenol A exposure in female offspring mice - You-dan Dong; Liang Gao; Feng-juan Wu; Ren Lin; Yuan Meng; Li-hong Jia; Xiao-fei Wang (Molecular & Cellular Toxicology, 2020)

Non-linear temperature sensitivity of litter component decomposition under warming gradient with precipitation addition on the Tibetan plateau - Wangwang Lv; Lirong Zhang; Haishan Niu; Bowen Li; Qi Wang; Yang Zhou; Yanfen Wang; Lili Jiang; Peipei Liu; Huan Hong; Shugang Jia; Caiyun Luo; et al. (Plant and Soil, 2020)

Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)
Simulated microgravity can significantly affect various cell types and multiple systems of the human body, such as cardiovascular system, skeletal muscle system, and immune system, and is known to cause anemia and loss of electrolyte and fluids. Epidermal stem cells (EpSCs) were cultured in a rotary cell culture system (RCCS) bioreactor to simulate microgravity. The metabolites of EpSCs were identified by liquid chromatography-mass spectrometry (LC-MS). Compared with normal gravity (NG) group, a total of 57 different metabolites of EpSCs were identified ( P < 0.05, VIP > 1), including lipids and lipid-like molecules (51 molecules), amino acids (5 molecules), nucleosides, nucleotides, and analogues (1 molecule). According to the partial least squares discriminant analysis (PLS-DA) score plot, a VIP > 1 and P < 0.05 were obtained for the 57 different metabolites, of which 23 molecules were significantly downregulated and 34 were significantly upregulated in simulated microgravity (SMG) group. These results showed that SMG has a significant impact on different pathways, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that multiple pathways were involved, mainly the amino acid metabolism pathway, lipid metabolism pathway, membrane transport pathway, and cell growth and death pathways. Thus, the metabolic profile of EpSCs was changed under SMG. Exploring the metabolic profile of EpSCs would be helpful to further understand the growth characteristics of EpSCs under SMG, which will provide a new approach to explore the metabolomics mechanism of stress injury and repair trauma under SMG.

Comparative study on the bioaccumulation of lead, cadmium and nickel and their toxic effects on the growth and enzyme defence strategies of a heavy metal accumulator, Hydrilla verticillata (L.f.) Royle - Hong Zhang; Ling-Lei Zhang; Jia Li; Min Chen; Rui-Dong An (Environmental Science and Pollution Research, 2020)

Review of Cystic Echinococcosis in Nigeria: A Story of Neglect - John Asekhaen Ohiolei; Hong-Bin Yan; Li Li; Guo-Qiang Zhu; Rosline James Muku; Yan-Tao Wu; Wan-Zhong Jia (Acta Parasitologica, 2020)

Uptake, depuration, bioaccumulation, and selective enrichment of dechlorane plus in common carp (Cyprinus carpio) - Dapeng Wang; Hongliang Jia; Wen-Jun Hong; Xiaohong Xue; Yeqing Sun; Yi-Fan Li; Weijun Guo (Environmental Science and Pollution Research, 2020)

A Review of Research on Tropical Air-Sea Interaction, ENSO Dynamics, and ENSO Prediction in China - Hong-Li Ren; Fei Zheng; Jing-Jia Luo; Run Wang; Minghong Liu; Wenjun Zhang; Tianjun Zhou; Guangqing Zhou (Journal of Meteorological Research, 2020)

One-step generation of zebrafish carrying a conditional knockout-knockin visible switch via CRISPR/Cas9-mediated intron targeting - Jia Li; Hong-Yu Li; Shan-Ye Gu; Hua-Xing Zi; Lai Jiang; Jiu-Lin Du (Science China Life Sciences, 2020)

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Autotrophic archaeal nitrification is preferentially stimulated by rice callus mineralization in a paddy soil - Haiyang Liu; Hong Pan; Hangwei Hu; Zhongjun Jia; Qian Zhang; Yimeng Liu; Jianming Xu; Hongjie Di; Yong Li (Plant and Soil, 2019)

Energy transition, CO2 mitigation, and air pollutant emission reduction: scenario analysis from IPAC model - Kejun Jiang; Sha Chen; Chenmin He; Jia Liu; Sun Kuo; Li Hong; Songli Zhu; Xiang Pianpian (Natural Hazards, 2019)

Tibial growth plate vascularization is inhibited by the dithiocarbamate pesticide thiram in chickens: potential relationship to peripheral platelet counts alteration - Shu-Cheng Huang; Lei Li; Mujeeb Ur Rehman; Jin-dong Gao; Li-hong Zhang; Xiao-le Tong; Muhammad Waqas; Jia-kui Li (Environmental Science and Pollution Research, 2019)

Experimental study on the physical modeling of loess tunnel-erosion rate - Li Wang; Xi-An Li; Lin-Cui Li; Bo Hong; Jia Liu (Bulletin of Engineering Geology and the Environment, 2019)

First Report of Theileria Infection of Bactrian Camels (Camelus bactrianus) in Xinjiang, China - Youquan Li; Xuan Li; Junlong Liu; Jinmin Wang; Dan Jia; Aihong Liu; Zonglin He; Guiquan Guan; Zhijie Liu; Guangyuan Liu; Jianxun Luo; Hong Yin (Acta Parasitologica, 2019)

Effects of Chronic Voluntary Alcohol Drinking on Thiamine Concentrations, Endoplasmic Reticulum Stress, and Oxidative Stress in the Brain of Crossed High Alcohol Preferring Mice - Hong Xu; Dexiang Liu; Jing Chen; Hui Li; Mei Xu; Wen Wen; Jacqueline A. Frank; Nicholas J. Grahame; Haining Zhu; Jia Luo (Neurotoxicity Research, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Brain structural basis of individual variability in dream recall frequency - Shuqin Zhou; Jing Xu; Zihui Su; Yuezhen Li; Yan Shao; Hongqiang Sun; Huaiqiu Zhu; Qihong Zou; Jia-Hong Gao (Brain Imaging and Behavior, 2019)

Identification of the optimal insertion site for expression of a foreign gene in an infectious hematopoietic necrosis virus vector - Jing-Zhuang Zhao; Li-Ming Xu; Miao Liu; Yong-Sheng Cao; Jia-Sheng Yin; Hong-Bai Liu; Tong-Yan Lu; Zhen-Yu Zhang (Archives of Virology, 2019)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

iTRAQ-based proteomic analysis of resistant Nicotiana tabacum in response to Bemisia tabaci infestation - Song-tao Zhang; Yue Long; Song-jie Zhang; Ning Li; De-xin Chen; Hong-fang Jia; Hong-ying Zhang; Yong-xia Yang (Arthropod-Plant Interactions, 2019)

First Report on Toxoplasma gondii Seroprevalence in Free-Ranging Pigs in Northeastern China - Qi Li; Si-Yuan Qin; Shuo Li; Peng Peng; Quan Zhao; Hong-Lin Jia; Chun-Ren Wang (Acta Parasitologica, 2019)

Serum and Seminal Plasma Element Concentrations in Relation to Semen Quality in Duroc Boars - Ying-hui Wu; Wen Lai; Zi-hui Liu; Hong-kui Wei; Yuan-fei Zhou; Jia-jian Tan; Hai-qing Sun; Sheng-qing Li; Jian Peng (Biological Trace Element Research, 2019)

Pterostilbene, an active component of the dragon’s blood extract, acts as an antidepressant in adult rats - Liang Yang; Yuanyuan Ran; Zhenzhen Quan; Ran Wang; Qinghu Yang; Qiutian Jia; Heao Zhang; Yanhui Li; Yiheng Peng; JianHua Liang; Hui Wang; Hiroshi Nakanishi; et al. (Psychopharmacology, 2019)

Year-round film mulching system with monitored fertilization management improve grain yield and water and nitrogen use efficiencies of winter wheat in the dryland of the Loess Plateau, China - Tingliang Li; Yinghe Xie; Zhiqiang Gao; Jianping Hong; Li Li; Huisheng Meng; Hongmei Ma; Junxiang Jia (Environmental Science and Pollution Research, 2019)

Contribution of Cathepsin L to Autolysis of Sea Cucumber Stichopus japonicus Intestines - Jia-Nan Yan; Xiao-Kun Guo; Yue Tang; Ao-Ting Li; Zhi-Mo Zhu; Xiao-Qian Chai; Xiu-Hong Duan; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2019)

Spatiotemporal variation of atmospheric nitrated polycyclic aromatic hydrocarbons in semi-arid and petrochemical industrialized Lanzhou City, Northwest China - Panliang Liu; Yuanli Ju; Yaojie Li; Zhanxiang Wang; Xiaoxuan Mao; Hongmei Cao; Chenhui Jia; Tao Huang; Hong Gao; Jianmin Ma (Environmental Science and Pollution Research, 2019)

Characterization of reactive photoinduced species in rainwater - Jun Hong; Jia Liu; Li Wang; Shaofei Kong; Chen Tong; Jun Qin; Lei Chen; Yue Sui; Baoqing Li (Environmental Science and Pollution Research, 2018)

Preservation of Lipid Molecular Fossils in the Sediments from an Oil-Gas Releasing Zone in the South China Sea - Hong Qiu; Li Zou; Minsheng Zhang; Chaoqi Zhu; Yonggang Jia (Journal of Ocean University of China, 2018)

Design parameters and treatment efficiency of a retrofit bioretention system on runoff nitrogen removal - Chun-bo Jiang; Jia-ke Li; Bin-hong Zhang; Tian-shun Ruan; Huai-en Li; Wen Dong (Environmental Science and Pollution Research, 2018)

Three new 3,4-seco-cycloartane triterpenes from Gardenia sootepensis - Wei-Wu Song; Xue-Qin Wang; Hua-Li Jia; Zheng-Kun Zhang; Yong-Jie Ding; Ya-Hong Chen (Natural Product Research, 2018)

Successful Sequential Treatment with Itraconazole and ALA-PDT for Cutaneous Granuloma by Candida albicans: A Case Report and Literature Review - Qing Cai; Lian-juan Yang; Jia Chen; Hong Yang; Zhi-qin Gao; Xiu-li Wang (Mycopathologia, 2018)

Constitutive and Chloroplast Targeted Expression of Acetyl-CoA Carboxylase in Oleaginous Microalgae Elevates Fatty Acid Biosynthesis - Da-Wei Li; Wei-Hong Xie; Ting-Bin Hao; Jia-Xi Cai; Tian-Bao Zhou; Srinivasan Balamurugan; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Marine Biotechnology, 2018)

NLRP1 promotes TGF-β1-induced myofibroblast differentiation in neonatal rat cardiac fibroblasts - Jing Zong; Hao Zhang; Fang-fang Li; Kai Liang; Jia-li Liu; Lu-hong Xu; Wen-hao Qian (Journal of Molecular Histology, 2018)

Anxiolytic potency of iridoid fraction extracted from Valeriana jatamansi Jones and its mechanism: a preliminary study - Xue-Mei Zhang; Jia-Li Zhu; Yong Sun; Yao-Lan Dai; Xiu Chen; Jia-Hong Cao; Ruo-Cong Yang; Chang Chen; Chao-Ying Ma; Tian-E Zhang; Yun-Hui Chen; Zhi-Yong Yan (Natural Product Research, 2018)

Three different downstream fates of the boreal-summer MJOs on their passages over the Maritime Continent - Joshua-Xiouhua Fu; Wanqiu Wang; Hong-Li Ren; Xiaolong Jia; Toshiaki Shinoda (Climate Dynamics, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

Anxiolytic-like effects of paeoniflorin in an animal model of post traumatic stress disorder - Zhi-Kun Qiu; Jia-Li He; Xu Liu; Jia Zeng; Wei Xiao; Qing-Hong Fan; Xiao-Meng Chai; Wei-Hai Ye; Ji-Sheng Chen (Metabolic Brain Disease, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Identification, characterization and expression analysis of genes involved in steroidal saponin biosynthesis in Dracaena cambodiana - Jia-Hong Zhu; Hui-Liang Li; Dong Guo; Ying Wang; Hao-Fu Dai; Wen-Li Mei; Shi-Qing Peng (Journal of Plant Research, 2018)

P2Y12 receptor upregulation in satellite glial cells is involved in neuropathic pain induced by HIV glycoprotein 120 and 2′,3′-dideoxycytidine - Zhihua Yi; Lihui Xie; Congfa Zhou; Huilong Yuan; Shuai Ouyang; Zhi Fang; Shanhong Zhao; Tianyu Jia; Lifang Zou; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2018)

Roles of Nitric Oxide Synthase Isoforms in Neurogenesis - Cheong-Meng Chong; Nana Ai; Minjing Ke; Yuan Tan; Zhijian Huang; Yong Li; Jia-Hong Lu; Wei Ge; Huanxing Su (Molecular Neurobiology, 2018)

Oestrogen regulates the expression of cathepsin E-A-like gene through ER $$\upbeta $$ β in liver of chicken (Gallus gallus) - Hang Zheng; Hong Li; Wenbo Tan; Chunlin Xu; Lijuan Jia; Dandan Wang; Zhuanjian Li; Gunrong Sun; Xiangtao Kang; Fengbin Yan; Xiaojun Liu (Journal of Genetics, 2018)

Large Deformation Characteristics and Reinforcement Measures for a Rock Pillar in the Houziyan Underground Powerhouse - Xin-hong Xiao; Pei-wei Xiao; Feng Dai; Hai-bo Li; Xue-bin Zhang; Jia-wen Zhou (Rock Mechanics and Rock Engineering, 2018)

The anxiolytic-like effects of puerarin are associated with the changes of monoaminergic neurotransmitters and biosynthesis of allopregnanolone in the brain - Zhi-Kun Qiu; De-Sheng Zhong; Jia-Li He; Xu Liu; Ji-Sheng Chen; Hong Nie (Metabolic Brain Disease, 2018)

Complementary feeding patterns among ethnic groups in rural western China - Peng-fei Qu; Ya Zhang; Jia-mei Li; Ruo Zhang; Jiao-mei Yang; Fang-liang Lei; Shan-shan Li; Dan-meng Liu; Shao-nong Dang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2018)

Release and kinetics of arsenic and plumbum in the Songhua River surficial sediments - Guang-Min Liu; Qing An; Li-Juan Wang; Xin Jia; Si-Hui Feng; Shu-Mei Xia; Yi-Ning Wu; Hong Qi (Environmental Science and Pollution Research, 2018)

Archaea and bacteria respectively dominate nitrification in lightly and heavily grazed soil in a grassland system - Hong Pan; Kexin Xie; Qichun Zhang; Zhongjun Jia; Jianming Xu; Hongjie Di; Yong Li (Biology and Fertility of Soils, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Fertility outcomes in infertile women with complex hyperplasia or complex atypical hyperplasia who received progestin therapy and in vitro fertilization - Miao Li; Jia-lun Song; Ying Zhao; She-ling Wu; Hong-bin Liu; Rong Tang; Lei Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Identification and expression analysis of genes involved in histone acetylation in Hevea brasiliensis - Hui-Liang Li; Dong Guo; Jia-Hong Zhu; Ying Wang; Shi-Qing Peng (Tree Genetics & Genomes, 2017)

Complete genome sequence of a Capsicum chlorosis virus in China and the structural variation and evolutionary origin of its S RNA intergenic region - Ying Huang; Hao Hong; Xiao-Hui Zhao; Jia Li; Xiao-Rong Tao (Archives of Virology, 2017)

Establishment of a cell line with high transfection efficiency from zebrafish Danio rerio embryos and its susceptibility to fish viruses - Y. L. Jin; L. M. Chen; Y. Le; Y. L. Li; Y. H. Hong; K. T. Jia; M. S. Yi (Journal of Fish Biology, 2017)
A cell line ZBE3 isolated from a continuous cell culture derived from zebrafish Danio rerio blastomeres by clonal growth was characterized. ZBE3 cells had been subcultured for >120 passages since the initial primary culture of the blastomeres. The ZBE3 cells grow stably at temperature from 20 to 32° C with an optimum temperature of 28° C in ESM2 or ESM4 medium with 15% foetal bovine serum (FBS). The optimum FBS concentration for ZBE3 cell growth ranged from 15 to 20%. Cytogenetical analysis indicated that the modal chromosome number of ZBE3 cells was 50, the same as the diploid chromosome number of D. rerio . Significant cytopathic effect was observed in ZBE3 cells after infection with redspotted grouper nervous necrosis virus, Singapore grouper iridovirus and grass carp reovirus, and the viral replication in the cells was confirmed by real‐time quantitative PCR and transmission electron microscopy, indicating the susceptibility of ZBE3 cells to the three fish viruses. After transfected with pEGFP‐N3 plasmid, ZBE3 cells showed a transfection efficiency of about 40% which was indicated by the percentage of cells expressing green fluorescence protein. The stable growth, susceptibility to fish viruses as well as high transfection efficiency make ZBE3 cells be a useful tool in transgenic manipulation, fish virus‐host cell interaction and immune response in fish.

Experimental Study on Failure Characteristics of Schist Under Unloading Condition - Hua-yan Yao; Shan-po Jia; Hong-guo Li (Geotechnical and Geological Engineering, 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Genome-wide identification, characterization, and expression analysis of SnRK2 family in Hevea brasiliensis - Dong Guo; Hui-Liang Li; Jia-Hong Zhu; Ying Wang; Feng An; Gui-Shui Xie; Shi-Qing Peng (Tree Genetics & Genomes, 2017)

Down-Regulation of Neuregulin1/ErbB4 Signaling in the Hippocampus Is Critical for Learning and Memory - Jia Tian; Fei Geng; Feng Gao; Yi-Hua Chen; Ji-Hong Liu; Jian-Lin Wu; Yu-Jie Lan; Yuan-Ning Zeng; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Molecular Neurobiology, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Recessive male sterility in cabbage (Brassica oleracea var. capitata) caused by loss of function of BoCYP704B1 due to the insertion of a LTR-retrotransposon - Jia-lei Ji; Li-mei Yang; Zhi-yuan Fang; Mu Zhuang; Yang-yong Zhang; Hong-hao Lv; Yu-mei Liu; Zhan-sheng Li (Theoretical and Applied Genetics, 2017)

Erratum to: The effect of sinomenine in diabetic neuropathic pain mediated by the P2X3 receptor in dorsal root ganglia - Shenqiang Rao; Shuangmei Liu; Lifang Zou; Tianyu Jia; Shanhong Zhao; Bing Wu; Zhihua Yi; Shouyu Wang; Yun Xue; Yun Gao; Changshui Xu; Guilin Li; et al. (Purinergic Signalling, 2017)

The effect of sinomenine in diabetic neuropathic pain mediated by the P2X3 receptor in dorsal root ganglia - Shenqiang Rao; Shuangmei Liu; Lifang Zou; Tianyu Jia; Shanhong Zhao; Bing Wu; Zhihua Yi; Shouyu Wang; Yun Xue; Yun Gao; Changshui Xu; Guilin Li; et al. (Purinergic Signalling, 2017)

Cryptococcosis in Patients with Nephrotic Syndrome: A Pooled Analysis of Cases - Wenjie Fang; Nan Hong; Yingfang Li; Jia Liu; Lei Zhang; Weiwei Jiang; Bo Qiu; Jianping Xu; Wanqing Liao; Min Chen; Weihua Pan (Mycopathologia, 2017)

Spectroscopic, Polarographic, and Microcalorimetric Studies on Mitochondrial Dysfunction Induced by Ethanol - Long Ma; Jia-Xin Dong; Can Wu; Xue-Yi Li; Jing Chen; Hong Zhang; Yi Liu (The Journal of Membrane Biology, 2017)

Gap junction protein connexin43 deregulation contributes to bladder carcinogenesis via targeting MAPK pathway - Xiao-lin Ai; Qiang Chi; Yu Qiu; Hong-yang Li; Dong-jie Li; Jia-xu Wang; Zhi-yong Wang (Molecular and Cellular Biochemistry, 2017)

Simultaneous Determination of Aniline, Benzidine, Microcystins, and Carbaryl in Water Using Ultra-Performance Liquid Chromatography–Electrospray Ionization Tandem Mass Spectrometry - Fei Shen; Li-Hong Wang; Qing Zhou; Xiao-Hua Huang; Jia-Zhi Zhang; Pei-Yu Zhu; Xiu-Li Dai; Yan-Juan Xu (Water, Air, & Soil Pollution, 2017)

Frequency specific brain networks in Parkinson’s disease and comorbid depression - Long Qian; Yi Zhang; Li Zheng; Xuemei Fu; Weiguo Liu; Yuqing Shang; Yaoyu Zhang; Yuanyuan Xu; Yijun Liu; Huaiqiu Zhu; Jia-Hong Gao (Brain Imaging and Behavior, 2017)

Chemical constituents from the roots of Ampelopsis delavayana and their antibacterial activities - Shuang-Xi Mei; Xu-Hong Li; Li-Guo Yang; Xiao-Hui Li; Jia-Ying Xie; Qi Yao; Mei Su; Tao Cui; Jing-Kun Wang; Zhao-Yun Zhu (Natural Product Research, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

Design, synthesis, and antimicrobial activities of new tanshinone IIA esters - Lin-Wei Zeng; Chang-Xin Zhou; Jia-Dong Liu; Chang-Hong Liu; Jian-Xia Mo; A-Fang Hou; Wei Yao; Zhen-Zhen Wang; Li-She Gan (Natural Product Research, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

A new Secondary metabolites of the crinoid ( Comanthina schlegeli ) associated fungus Alternaria brassicae 93 - Liu-Hong Zhang; Hong-Wei Wang; Jia-Yi Xu; Jing Li; Lan Liu (Natural Product Research, 2016)

Different effects of isolation-rearing and neonatal MK-801 treatment on attentional modulations of prepulse inhibition of startle in rats - Zhe-Meng Wu; Yu Ding; Hong-Xiao Jia; Liang Li (Psychopharmacology, 2016)

Spherical cap harmonic analysis of regional magnetic anomalies based on CHAMP satellite data - Yan Feng; Yong Jiang; Yi Jiang; Bao-Jia Liu; Jin Jiang; Zhong-Wei Liu; Mei-Chen Ye; Hong-Shen Wang; Xiu-Ming Li (Applied Geophysics, 2016)

Growth and antioxidant production of Spirulina in different NaCl concentrations - Chang Liu; Lu-Jia Li; Chun-Yuan Wu; Kang-Ning Guo; Jian-Hong Li (Biotechnology Letters, 2016)

Neuroprotective effects of a chromatin modifier on ischemia/reperfusion neurons: implication of its regulation of BCL2 transactivation by ERα signaling - Jun Guo; Tao Zhang; Jia Yu; Hong-Zeng Li; Cong Zhao; Jing Qiu; Bo Zhao; Jie Zhao; Wei Li; Tian-Zhi Zhao (Cell and Tissue Research, 2016)

Cytotoxic monoterpenoid indole alkaloids isolated from the barks of Voacanga africana Staph. - Hong-Mei Chen; Yu-Ting Yang; Hong-Xiang Li; Zhi-Xing Cao; Xiao-Mei Dan; Ling Mei; Da-Le Guo; Chuan-Xia Song; Yu Dai; Jia Hu; Yun Deng (Natural Product Research, 2016)

Human cytomegalovirus UL49 encodes an early, virion-associated protein essential for virus growth in human foreskin fibroblasts - Feng Zhu; Jian Yuan; Hong-Jian Li; Zhi-Feng Zeng; Zhi-Wen Luo; Shi-Qian Li; Chi-Qiang He; Xue-Fang Jia; Xin Zhang; Hui Zuo; Yi-Min Liu; Martin Chang; et al. (Archives of Virology, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Evaluation of Groundwater Leakage into a Drainage Tunnel in Jinping-I Arch Dam Foundation in Southwestern China: A Case Study - Yi-Feng Chen; Jia-Min Hong; Hua-Kang Zheng; Yi Li; Ran Hu; Chuang-Bing Zhou (Rock Mechanics and Rock Engineering, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Synthesis of some new thiazolo[3,2-a]pyrimidine derivatives and screening of their in vitro antibacterial and antitubercular activities - Dong Cai; Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Shi-Ti Zhang; Liang-Jing Zou; Li-Hong Meng; Fang Li; Bing-Jie Fu (Medicinal Chemistry Research, 2016)

Meiofauna distribution in intertidal sandy beaches along China shoreline (18°–40°N) - Er Hua; Zhinan Zhang; Hong Zhou; Fanghong Mu; Jia Li; Ting Zhang; Bingqing Cong; Xiaoshou Liu (Journal of Ocean University of China, 2016)

Location- and Subunit-Specific NMDA Receptors Determine the Developmental Sevoflurane Neurotoxicity Through ERK1/2 Signaling - Wen-Yuan Wang; Li-Jie Jia; Yan Luo; Hong-Hai Zhang; Fang Cai; Hui Mao; Wei-Cai Xu; Jun-Biao Fang; Zhi-You Peng; Zheng-Wen Ma; Yan-Hong Chen; Juan Zhang; et al. (Molecular Neurobiology, 2016)

Leaf and root glucosinolate profiles of Chinese cabbage (Brassica rapa ssp. pekinensis) as a systemic response to methyl jasmonate and salicylic acid elicitation - Yun-xiang Zang; Jia-li Ge; Ling-hui Huang; Fei Gao; Xi-shan Lv; Wei-wei Zheng; Seung-beom Hong; Zhu-jun Zhu (Journal of Zhejiang University-SCIENCE B, 2015)

Saussurea medusa, source of the medicinal herb snow lotus: a review of its botany, phytochemistry, pharmacology and toxicology - Jia-Yi Fan; Hu-Biao Chen; Lin Zhu; Hong-Li Chen; Zhong-Zhen Zhao; Tao Yi (Phytochemistry Reviews, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Effects of heat stress on serum insulin, adipokines, AMP-activated protein kinase, and heat shock signal molecules in dairy cows - Li Min; Jian-bo Cheng; Bao-lu Shi; Hong-jian Yang; Nan Zheng; Jia-qi Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Caspase-8 Mediates Amyloid-β-induced Apoptosis in Differentiated PC12 Cells - Min-cai Qian; Jing Liu; Jia-shu Yao; Wei-min Wang; Jian-hong Yang; Li-li Wei; Yue-di Shen; Wei Chen (Journal of Molecular Neuroscience, 2015)

Expression of Cyclooxygenase-2 in Squamous Cell Carcinoma and Keratoacanthoma and its Clinical Significance - Hai-Kang Hua; Cheng Jin; Li-Jia Yang; Shi-Qin Tao; Xiao-Hong Zhu (Cell Biochemistry and Biophysics, 2015)

Polycyclic aromatic hydrocarbons in Chinese surface soil: occurrence and distribution - Wan-Li Ma; Li-Yan Liu; Chong-Guo Tian; Hong Qi; Hong-Liang Jia; Wei-Wei Song; Yi-Fan Li (Environmental Science and Pollution Research, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Methylopila henanense sp. nov., a novel methylotrophic bacterium isolated from tribenuron methyl-contaminated wheat soil - Ya-Nan Wang; Wen-Yu Tian; Wei-Hong He; Guo-Can Chen; Ming-Li An; Bin Jia; Li Liu; Yang Zhou; Shuang-Jiang Liu (Antonie van Leeuwenhoek, 2015)

E2F1 regulates p53R2 gene expression in p53-deficient cells - Jun-Juan Qi; Ling Liu; Ji-Xiang Cao; Guo-Shun An; Shu-Yan Li; Gang Li; Hong-Ti Jia; Ju-Hua Ni (Molecular and Cellular Biochemistry, 2015)

Effect of freeze-thaw cycles on mechanical properties and permeability of red sandstone under triaxial compression - Jin Yu; Xu Chen; Hong Li; Jia-wen Zhou; Yan-yan Cai (Journal of Mountain Science, 2015)

Multiple correlations of mRNA expression and protein abundance in human cytokine profile - Hong-wu Du; Guang-yu Chen; Chun-he Yang; Chuan-bao Li; Yi-ping Xun; Jia Liu; Peng Chen; Li-li Shi (Molecular Biology Reports, 2014)

Erratum to: Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

Screening for Differentially Expressed Genes in Endophytic Fungus Strain 39 During Co-culture with Herbal Extract of its Host Dioscorea nipponica Makino - Chang-Hong Ding; Xiao-Wei Du; Ying Xu; Xiao-Meng Xu; Jin-Chao Mou; Dan Yu; Jun-Kai Wu; Fan-Jia Meng; Yan Liu; Wan-Li Wang; Li-Juan Wang (Current Microbiology, 2014)

Epitope mapping of the infectious hematopoietic necrosis virus glycoprotein by flow cytometry - Li-Ming Xu; Miao Liu; Jing-Zhuang Zhao; Yong-Sheng cao; Jia-Sheng Yin; Hong-Bai Liu; Tongyan Lu (Biotechnology Letters, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Increased body weight induced by perinatal exposure to bisphenol A was associated with down-regulation zinc-alpha2-glycoprotein expression in offspring female rats - Ling Zhang; Hong Yuan Zhang; Cui Cui Ma; Wei Wei; Li Hong Jia (Molecular & Cellular Toxicology, 2014)

Corynoxine, a Natural Autophagy Enhancer, Promotes the Clearance of Alpha-Synuclein via Akt/mTOR Pathway - Lei-Lei Chen; Ju-Xian Song; Jia-Hong Lu; Zhen-Wei Yuan; Liang-Feng Liu; Siva Sundara Kumar Durairajan; Min Li (Journal of Neuroimmune Pharmacology, 2014)

Sequence variability in the HC-Pro coding regions of Korean soybean mosaic virus isolates is associated with differences in RNA silencing suppression - Mei-Jia Li; Jung-Kyu Kim; Eun-Young Seo; Seok Myeong Hong; Eui-Il Hwang; Jung-Kyung Moon; Leslie L. Domier; John Hammond; Young-Nam Youn; Hyoun-Sub Lim (Archives of Virology, 2014)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Screening of multi-copy mannanase recombinants of Pichia pastoris based on colony size - Jia Zheng; Ning Guo; Fu-lai Lin; Li-shuang Wu; Hong-bo Zhou (World Journal of Microbiology and Biotechnology, 2014)

Protection of MES23.5 dopaminergic cells by obestatin is mediated by proliferative rather than anti-apoptotic action - Xiao-Li Shen; Feng-Ju Jia; Ning Song; Jun-Xia Xie; Hong Jiang (Neuroscience Bulletin, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

HIRA is essential for the development of gibel carp - Meng-Yu Wang; Qiu-Hong Guo; Xin-Zheng Du; Li Zhou; Qian Luo; Qiao-Hui Zeng; Jia-Lin Wang; Hao-Bin Zhao; Yu-Feng Wang (Fish Physiology and Biochemistry, 2014)

Runoff characteristics of the Nen River Basin and its cause - Hong-yan Li; Yu-xin Wang; Li-na Jia; Ya-nan Wu; Miao Xie (Journal of Mountain Science, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

E2F1-mediated DNA damage is implicated in 8-Cl-adenosine-induced chromosome missegregation and apoptosis in human lung cancer H1299 cells - Yu-Ying Han; Zhe Zhou; Ji-Xiang Cao; Ya-Qiong Jin; Shu-Yan Li; Ju-Hua Ni; Guo-Shun An; Yu-Xiang Zhang; Hong-Ti Jia (Molecular and Cellular Biochemistry, 2013)

Effect of bisphenol A exposure during early development on glucose metabolism and adipokine expression in adolescent female rats - Ling Zhang; Hong Yuan Zhang; Cui Cui Ma; Ling Ling Zhai; Li Hong Jia (Molecular & Cellular Toxicology, 2013)

Microbial Diversity and Succession in the Chinese Luzhou-Flavor Liquor Fermenting Cover Lees as Evaluated by SSU rRNA Profiles - Ke Li; Qing Zhang; Xiao-Ting Zhong; Bi-Hong Jia; Chun-Hong Yuan; Sen Liu; Zhen-Ming Che; Wen-Liang Xiang (Indian Journal of Microbiology, 2013)

The PpLTP1 Primary Allergen Gene is Highly Conserved in Peach and Has Small Variations in Other Prunus Species - Ying-tao Ma; Xiang Zhou; Zhong-shan Gao; Xiong-wei Li; Hui-juan Jia; Hong-xia Wu; Rang-jin Xie; Zhi-qiang Wang; Ming-liang Yu; Ke Cao; Shuang-jian Chen; Ying-hui Li; et al. (Plant Molecular Biology Reporter, 2013)

Impacts of Urbanization and Station-relocation on Surface Air Temperature Series in Anhui Province, China - Yuan-Jian Yang; Bi-Wen Wu; Chun-e Shi; Jia-Hua Zhang; Yu-Bin Li; Wei-An Tang; Hua-Yang Wen; Hong-Qun Zhang; Tao Shi (Pure and Applied Geophysics, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

β-Ionone arrests cell cycle of gastric carcinoma cancer cells by a MAPK pathway - Hong-Wei Dong; Shuang Zhang; Wen-Guang Sun; Qian Liu; Juan C. Ibla; Sulpicio G. Soriano; Xiao-Hui Han; Lian-Xin Liu; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

TAK1 inhibitor 5Z-7-oxozeaenol sensitizes neuroblastoma to chemotherapy - Yihui Fan; Jin Cheng; Sanjeev A. Vasudevan; Roma H. Patel; Li Liang; Xin Xu; Yanling Zhao; Wei Jia; Fengmin Lu; Hong Zhang; Jed G. Nuchtern; Eugene S. Kim; et al. (Apoptosis, 2013)

Two novel ansamitocin analogs from Actinosynnema pretiosum - Siyu-Mao; Hong-Chen; Li-Chen; Chuanxi-Wang; Wei-Jia; Xiaoming-Chen; Huangjian-Yang; Wei-Huang; Wei-Zheng (Natural Product Research, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Erratum to: Hydroxyapatite/regenerated silk fibroin scaffold-enhanced osteoinductivity and osteoconductivity of bone marrow-derived mesenchymal stromal cells - Jia Jiang; Wei Hao; Yuzhuo Li; Jinrong Yao; Zhengzhong Shao; Hong Li; Jianjun Yang; Shiyi Chen (Biotechnology Letters, 2013)

Re-Examination of the Genotoxic Activity of Water Taken From the Songhua River in P. R. China - Jia Yu; Hong-Wei Dong; Li-Tian Shi; Hui-Ling Jiang; Jian-Wen Yu; Qian-Wen Zhao; Shi-Chun Cai; Dan Han; Xuan-Yue Tang; Jia-Ren Liu (Archives of Environmental Contamination and Toxicology, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Protection against peroxynitrite-induced DNA damage by mesalamine: implications for anti-inflammation and anti-cancer activity - Paul M. Graham; Jason Z. Li; Xueging Dou; Hong Zhu; Hara P. Misra; Zhenquan Jia; Yunbo Li (Molecular and Cellular Biochemistry, 2013)

Neurotrophic Tyrosine Kinase Receptor Type 2 (NTRK2) Gene Associated with Treatment Response to Mood Stabilizers in Patients with Bipolar I Disorder - Zuowei Wang; Jinbo Fan; Keming Gao; Zezhi Li; Zhenghui Yi; Lingxiao Wang; Jia Huang; Chengmei Yuan; Wu Hong; Shunying Yu; Yiru Fang (Journal of Molecular Neuroscience, 2013)

Comparative studies of saponins in 1–3-year-old main roots, fibrous roots, and rhizomes of Panax notoginseng, and identification of different parts and growth-year samples - Xiu-Hong Jia; Chao-Qun Wang; Jin-Huai Liu; Xiao-Wei Li; Xuan Wang; Ming-Ying Shang; Shao-Qing Cai; Shu Zhu; Katsuko Komatsu (Journal of Natural Medicines, 2013)

In vitro isolation and cultivation of rabbit tracheal epithelial cells using tissue explant technique - Hong-Can Shi; Dan Lu; Hai-Jia Li; Shi Han; Yan-Jun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2013)

Hydroxyapatite/regenerated silk fibroin scaffold-enhanced osteoinductivity and osteoconductivity of bone marrow-derived mesenchymal stromal cells - Jia Jiang; Wei Hao; Yuzhuo Li; Jinrong Yao; Zhengzhong Shao; Hong Li; Jianjun Yang; Shiyi Chen (Biotechnology Letters, 2013)

Successful establishment and evaluation of a new animal model for studying the hepatitis B virus YVDD mutant - Yan-Xiu Ma; Zhi-Wei Song; Xu Teng; Li-Juan Fu; Mei-Li Hao; Si-Jia Chen; Wei-Zhen Xu; Hong-Xi Gu (Archives of Virology, 2013)

Bioactive alkaloids produced by Pseudomonas brassicacearum subsp. Neoaurantiaca, an endophytic bacterium from Salvia miltiorrhiza - Xiao-Jun Li; Hao-Yu Tang; Jia-Li Duan; Jin-Ming Gao; Quan-Hong Xue (Natural Product Research, 2013)

Apoptosis initiation of β-ionone in SGC-7901 gastric carcinoma cancer cells via a PI3K-AKT pathway - Qian Liu; Hong-Wei Dong; Wen-Guang Sun; Ming Liu; Juan C. Ibla; Lian-Xin Liu; John W. Parry; Xiao-Hui Han; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Synthesis, structure, and biological assay of cinnamic amides as potential EGFR kinase inhibitors - Mao Zhang; Xiang Lu; Hong-Jia Zhang; Na Li; Yu Xiao; Hai-Liang Zhu; Yong-Hao Ye (Medicinal Chemistry Research, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Methylglyoxal Induces Tau Hyperphosphorylation via Promoting AGEs Formation - Xiao-Hong Li; Jia-Zhao Xie; Xia Jiang; Bing-Ling Lv; Xiang-Shu Cheng; Lai-Ling Du; Jia-Yu Zhang; Jian-Zhi Wang; Xin-Wen Zhou (NeuroMolecular Medicine, 2012)

Note added in proof to: Molecular characterization of the pentacyclic triterpenoid biosynthetic pathway in Catharanthus roseus - Lili Huang; Jia Li; Hechun Ye; Changfu Li; Hong Wang; Benye Liu; Yansheng Zhang (Planta, 2012)

Molecular characterization of the pentacyclic triterpenoid biosynthetic pathway in Catharanthus roseus - Lili Huang; Jia Li; Hechun Ye; Changfu Li; Hong Wang; Benye Liu; Yansheng Zhang (Planta, 2012)

Pseudomonas nitritireducens sp. nov., a nitrite reduction bacterium isolated from wheat soil - Ya-Nan Wang; Wei-Hong He; Hua He; Xun Du; Bin Jia; Zhi-Peng Zeng; Ming-Li An; Guo-Can Chen (Archives of Microbiology, 2012)

VEGF upregulates VEGF receptor-2 on human outer root sheath cells and stimulates proliferation through ERK pathway - Wei Li; Zhong-Fa Lu; Xiao-Yong Man; Chun-Ming Li; Jiong Zhou; Jia-Qi Chen; Xiao-Hong Yang; Xian-Jie Wu; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2012)

Impairment of liver regeneration by the histone deacetylase inhibitor valproic acid in mice - Qi Ke; Rui-na Yang; Feng Ye; Yu-jia Wang; Qiong Wu; Li Li; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2012)

The Regulation of Exogenous Jasmonic Acid on UV-B Stress Tolerance in Wheat - Xiao Liu; Hong Chi; Ming Yue; Xiaofei Zhang; Wenjuan Li; Enping Jia (Journal of Plant Growth Regulation, 2012)

Microsatellite markers developed for the multi-ocellated racerunner, Eremias multiocellata (Lacertidae) - Lian Chen; Jia Guo; Zong-Shi Zhou; Hong Li (Conservation Genetics Resources, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

EPR studies on hydroxyl radical-scavenging activities of pravastatin and fluvastatin - Nathan Vandjelovic; Hong Zhu; Hara P. Misra; Ryan P. Zimmerman; Zhenquan Jia; Yunbo Li (Molecular and Cellular Biochemistry, 2012)

An Acyl–acyl Carrier Protein Thioesterase Gene Isolated from Wintersweet (Chimonanthus praecox), CpFATB, Enhances Drought Tolerance in Transgenic Tobacco (Nicotiana tobaccum) - Li-Hong Zhang; Baolei Jia; Ren-Ying Zhuo; Jin-Liang Liu; Hong-Yu Pan; Timothy C. Baldwin; Shi-Hong Zhang (Plant Molecular Biology Reporter, 2012)

Polymorphic variations in manganese superoxide dismutase (MnSOD), glutathione peroxidase-1 (GPX1), and catalase (CAT) contribute to elevated plasma triglyceride levels in Chinese patients with type 2 diabetes or diabetic cardiovascular disease - Hong Chen; Ming Yu; Ming Li; Ruie Zhao; Qihan Zhu; Wenrui Zhou; Ming Lu; Yufeng Lu; Taishan Zheng; Jiamei Jiang; Weijing Zhao; Kunsan Xiang; et al. (Molecular and Cellular Biochemistry, 2012)

Mechanistic insights into the link between visfatin gene C-1535T polymorphism and coronary artery disease: an in vitro study - Yong-Sheng Wang; Wei Gao; Hong-Fen Li; Ze-Mu Wang; Jun Zhu; Huan Zhao; Jian-Jun Yan; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular and Cellular Biochemistry, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Genetic polymorphism analysis of killer cell immunoglobulin-like receptor genes in the Chinese Uygur population - Hong-dan Wang; Bo-feng Zhu; Chun-mei Shen; Guo-lian Yuan; Guang Yang; Juan-ning Guo; Jiang-wei Yan; Hai-xia Qin; Jian-xin Guo; Li-ping Zhang; Xiao-qin Jia; Rudolf Lucas (Molecular Biology Reports, 2012)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

Genetic and physical mapping of qHY-8, a pleiotropic QTL for heading date and yield-related traits in rice - Hai-Ya Cai; Shu Diao; Yong-Gang He; Li-Pan Zhang; Shao-Jia Liu; Ying-Guo Zhu; Zhi-Hong Zhang (Euphytica, 2012)

Fusion of HSA influences TNF-α neutralizing activity of shTNFRs - Jia Zhan; Ying Chen; Han-Ying Yuan; Hai Li; Hong Lu (Biotechnology Letters, 2012)

Rock critical porosity inversion and S-wave velocity prediction - Jia-Jia Zhang; Hong-Bing Li; Feng-Chang Yao (Applied Geophysics, 2012)

Identification and expression analysis of four 14-3-3 genes during fruit ripening in banana (Musa acuminata L. AAA group, cv. Brazilian) - Mei-Ying Li; Bi-Yu Xu; Ju-Hua Liu; Xiao-Liang Yang; Jian-Bin Zhang; Cai-Hong Jia; Li-Cheng Ren; Zhi-Qiang Jin (Plant Cell Reports, 2012)

Insulin-like growth factor binding protein-6 interacts with the thyroid hormone receptor α1 and modulates the thyroid hormone-response in osteoblastic differentiation - Jia Qiu; Xiao-Li Ma; Xin Wang; Hong Chen; Bing-Ren Huang (Molecular and Cellular Biochemistry, 2012)

A novel genus of multicellular magnetotactic prokaryotes from the Yellow Sea - Ke Zhou; Wen‐Yan Zhang; Kui Yu‐Zhang; Hong‐Miao Pan; Sheng‐Da Zhang; Wei‐Jia Zhang; Hai‐Dong Yue; Ying Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2012)
Summary Multicellular magnetotactic prokaryotes (MMPs) are a group of magnetotactic microorganisms composed of 10–40 Gram‐negative cells. Currently, all the identified MMPs show a spherical morphology and synthesize mainly iron sulfide magnetosomes. In this study, we report a novel genus of MMPs with peculiar ellipsoidal morphology and iron oxide magnetosomes, which were discovered in intertidal sediment of the Yellow Sea in China. Optical and fluorescence microscopy revealed that this organism was ∼10 × 8 µm in size and composed of ∼40 cells enveloped by an outer layer. Scanning electron microscopy showed that the cells were arranged in 4–6 interlaced circles. Bullet‐shaped magnetite magnetosomes were organized in chains roughly parallel to the long axis of the ellipsoidal MMPs when analysed by transmission electron microscopy. These MMPs displayed special escape motility, i.e. swimming rapidly from the edge to the centre of the droplet and then slowly back to the edge. In addition, they exhibited negative phototaxis. Light microscopy observations showed that the ellipsoidal MMPs reproduced by division along the body long axis. Both analysis of 16S rRNA gene sequence and fluorescence in situ hybridization revealed the ellipsoidal MMPs as a new genus of the Deltaproteobacteria . In summary, this novel genus of MMPs exhibit unique morphology, peculiar division process and distinct phylogenetic affiliation compared with the other MMPs.

Different sperm sources and parameters can influence intracytoplasmic sperm injection outcomes before embryo implantation - Yue-hong Lu; Hui-juan Gao; Bai-jia Li; Ying-ming Zheng; Ying-hui Ye; Yu-li Qian; Chen-ming Xu; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

Green synthesis of silver nanoparticles using Rhodobacter Sphaeroides - Hong-Juan Bai; Bin-Sheng Yang; Chun-Jing Chai; Guan-E. Yang; Wan-Li Jia; Zhi-Ben Yi (World Journal of Microbiology and Biotechnology, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Environmental Lead Exposure Among Children in Chengdu, China, 2007–2009 - Hua Shi; Yong-mei Jiang; Jia-yuan Li; Fang Liu; Hong Wang; Fan Yu; Hui Yang (Biological Trace Element Research, 2011)

Development and characterization of EST-SSR markers in the freshwater pearl mussel (Hyriopsis Cumingii) - Zhi Yi Bai; Dong Hong Niu; Jia Le Li (Conservation Genetics Resources, 2011)

Methyl-1-hydroxy-2-naphthoate, a novel naphthol derivative, inhibits lipopolysaccharide-induced inflammatory response in macrophages via suppression of NF-κB, JNK and p38 MAPK pathways - Jun-Yan Zhang; Hong Jin; Guang-Fa Wang; Peng-Jiu Yu; Shao-Yu Wu; Zheng-Guang Zhu; Zhong-Huang Li; Yuan-Xin Tian; Wei Xu; Jia-Jie Zhang; Shu-Guang Wu (Inflammation Research, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of the crude extract of Polygala tenuifolia Willd on human sperm in vitro - Yi Qiu; Lei-guang Wang; Yi-fang Jia; Dan-tong Yang; Mei-hua Zhang; Yan-ping Zhang; Li-hong Zhang; Ling Gai (Journal of Zhejiang University-SCIENCE B, 2011)

Differentiation of Fecal Escherichia coli from Human, Livestock, and Poultry Sources by rep-PCR DNA Fingerprinting on the Shellfish Culture Area of East China Sea - Hong-Jia Ma; Ling-Lin Fu; Jian-Rong Li (Current Microbiology, 2011)

Verapamil exerts biphasic modulation on phenobarbital transport across the blood–brain barrier: evidence from an in vivo and in vitro study - Dan Yao; Zhi-Hong Yang; Li Liu; Jia Li; Yun-Li Yu; Lu-Lu Zhang; Xian Pan; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Targets for human encoded microRNAs in HBV genes - Fang-li Wu; Wei-Bo Jin; Jia-hong Li; Ai-Guang Guo (Virus Genes, 2011)

Seismic noise attenuation using nonstationary polynomial fitting - Guo-Chang Liu; Xiao-Hong Chen; Jing-Ye Li; Jing Du; Jia-Wen Song (Applied Geophysics, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Functional conservation of the plant EMBRYONIC FLOWER2 gene between bamboo and Arabidopsis - Hong Xu; Ling-Jing Chen; Li-Jia Qu; Hong-Ya Gu; De-Zhu Li (Biotechnology Letters, 2010)

Mycorrhizal specificity, preference, and plasticity of six slipper orchids from South Western China - Li Yuan; Zhu L. Yang; Shu-Yun Li; Hong Hu; Jia-Lin Huang (Mycorrhiza, 2010)

Epigenetic regulation of adipocyte differentiation and adipogenesis - Hong-xing Li; Lei Xiao; Cheng Wang; Jia-li Gao; Yong-gong Zhai (Journal of Zhejiang University-SCIENCE B, 2010)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Isolation of a methyl parathion-degrading strain Stenotrophomonas sp. SMSP-1 and cloning of the ophc2 gene - Yu-jia Shen; Pen Lu; Huan Mei; Hao-jie Yu; Qing Hong; Shun-peng Li (Biodegradation, 2010)

Propranolol regulates cardiac transient outward potassium channel in rat myocardium via cAMP/PKA after short-term but not after long-term ischemia - Li Zhang; Chao-Qian Xu; Yuan Hong; Jia-Lin Zhang; Ying Liu; Mei Zhao; Yan-Xiu Cao; Yan-Jie Lu; Bao-Feng Yang; Hong-Li Shan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

A New Phosphorimetry for the Determination of Trace Alkaline Phosphatase Using Multi-wall Carbon Nanotubes and Its Diagnosis of Human Diseases - Jia-Ming Liu; Ying Rao; Li Chen; Xin-Xing Wang; Li-Ping Lin; Chang-Qing Lin; Li-Hong Zhang; Ying Ou-Yang (Journal of Fluorescence, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

Effects of Reactive Oxygen Species Metabolic System on Soybean (Glycine max) Under Exogenous Chitosan to Ozone Stress - Tian Hong Zhao; Jun Li Wang; Yan Wang; Jia Wei Sun; Ying Cao (Bulletin of Environmental Contamination and Toxicology, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Polymorphic microsatellite loci for population studies of Bullacta exarata - Shu-Liang Wang; Dong-Hong Niu; Ming-Jing Jia; Jia-Le Li (Conservation Genetics, 2010)

Erratum to: Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Lin; Shuan-Yow Li (Human Genetics, 2010)

Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Li; Shuan-Yow Li (Human Genetics, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Dissipation and Residues of Chlormequat in Wheat and Soil - Xing-li Guo; Chun-hong Jia; Er-cheng Zhao; Yan-jun Xu; Li-jun Han; Shu-ren Jiang (Bulletin of Environmental Contamination and Toxicology, 2010)

Isolation and characterization of 10 polymorphic microsatellites in Meretrix meretrix - Shu-Liang Wang; Dong-Hong Niu; Jia-Le Li (Conservation Genetics Resources, 2009)

Multicentre evaluation of the Elecsys® hepatitis B surface antigen II assay for detection of HBsAg in comparison with other commercially available assays - Ji-Dong Jia; Ma Hong; Lai Wei; Xin-Xin Zhang; Yuan-Li Mao; Lan-Lan Wang; Zhi-Liang Gao; Jin-Lin Hou; Jun Zhang (Medical Microbiology and Immunology, 2009)

Valsartan preconditioning protects against myocardial ischemia–reperfusion injury through TLR4/NF-κB signaling pathway - Jian Yang; Hong Jiang; Jun Yang; Jia-Wang Ding; Li-Hua Chen; Song Li; Xiao-Dong Zhang (Molecular and Cellular Biochemistry, 2009)

Two spawning stocks of icefish Neosalanx taihuensis revealed from annual reproductive cycle analyses - Wang Bao Gong; Hong Tao Li; Shou Qi Xie; Jia Shou Liu; Brian R. Murphy; Song Guang Xie (Fisheries Science, 2009)

Complete genomic sequence analyses of Turnip mosaic virus basal-BR isolates from China - Hong-Yan Wang; Jin-Liang Liu; Rui Gao; Jia Chen; Yun-Hua Shao; Xiang-Dong Li (Virus Genes, 2009)

Detection of plasmid-mediated IMP-1 metallo-β-lactamase and quinolone resistance determinants in an ertapenem-resistant Enterobacter cloacae isolate - Li-rong Chen; Hong-wei Zhou; Jia-chang Cai; Rong Zhang; Gong-xiang Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Osteogenic differentiation of mesenchymal stem cells promoted by overexpression of connective tissue growth factor - Jin-jing Wang; Feng Ye; Li-jia Cheng; Yu-jun Shi; Ji Bao; Huai-qiang Sun; Wei Wang; Peng Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2009)

Chromosomal aberrations and DNA damage in human populations exposed to the processing of electronics waste - Qiang Liu; Jia Cao; Ke Qiu Li; Xu Hong Miao; Guang Li; Fei Yue Fan; Yong Cheng Zhao (Environmental Science and Pollution Research, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Alpha-lipoic acid potently inhibits peroxynitrite-mediated DNA strand breakage and hydroxyl radical formation: implications for the neuroprotective effects of alpha-lipoic acid - Zhenquan Jia; Hong Zhu; Michael J. Vitto; Bhaba R. Misra; Yunbo Li; Hara P. Misra (Molecular and Cellular Biochemistry, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

Polycyclic Aromatic Hydrocarbons in Urban Street Dust and Surface Soil: Comparisons of Concentration, Profile, and Source - De-Gao Wang; Meng Yang; Hong-Liang Jia; Lei Zhou; Yi-Fan Li (Archives of Environmental Contamination and Toxicology, 2009)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Characterization of a putative pollen-specific arabinogalactan protein gene, BcMF8, from Brassica campestris ssp. chinensis - Li Huang; Jia-Shu Cao; Ai-Hong Zhang; Yi-Qun Ye (Molecular Biology Reports, 2008)

Cloning and characterization of a novel cysteine protease gene (HbCP1) from Hevea brasiliensis - Shi-Qing Peng; Jia-Hong Zhu; Hui-Liang Li; Wei-Min Tian (Journal of Biosciences, 2008)

Molecular Identification of cDNA, Immunolocalization, and Expression of a Putative Odorant-Binding Protein from an Asian Honey Bee, Apis cerana cerana - Hong-Liang Li; Ya-Li Zhang; Qi-Kang Gao; Jia-An Cheng; Bing-Gan Lou (Journal of Chemical Ecology, 2008)

Polymorphic microsatellite loci for population studies of the razor clam, Sinonovacula constricta - Dong-Hong Niu; Jia-Le Li; Da-Bo Liu (Conservation Genetics, 2008)

Potent Induction of Total Cellular and Mitochondrial Antioxidants and Phase 2 Enzymes by Cruciferous Sulforaphane in Rat Aortic Smooth Muscle Cells: Cytoprotection Against Oxidative and Electrophilic Stress - Hong Zhu; Zhenquan Jia; Jeannine S. Strobl; Marion Ehrich; Hara P. Misra; Yunbo Li (Cardiovascular Toxicology, 2008)

PolyQ-expanded ataxin-3 interacts with full-length ataxin-3 in a polyQ length-dependent manner - Na-Li Jia; Er-Kang Fei; Zheng Ying; Hong-Feng Wang; Guang-Hui Wang (Neuroscience Bulletin, 2008)

EPR studies on the superoxide-scavenging capacity of the nutraceutical resveratrol - Zhenquan Jia; Hong Zhu; Bhaba R. Misra; James E. Mahaney; Yunbo Li; Hara P. Misra (Molecular and Cellular Biochemistry, 2008)

Nuclear Factor E2-Related Factor 2-Dependent Myocardiac Cytoprotection Against Oxidative and Electrophilic Stress - Hong Zhu; Zhenquan Jia; Bhaba R. Misra; Li Zhang; Zhuoxiao Cao; Masayuki Yamamoto; Michael A. Trush; Hara P. Misra; Yunbo Li (Cardiovascular Toxicology, 2008)

Characterization of tomato zonate spot virus, a new tospovirus in China - Jia-Hong Dong; Xiao-Fei Cheng; Yue-Yan Yin; Qi Fang; Ming Ding; Ting-Ting Li; Li-Zhen Zhang; Xiao-Xia Su; Jenifer Huang McBeath; Zhong-Kai Zhang (Archives of Virology, 2008)

Effects of ATP sensitive potassium channel opener on the mRNA and protein expressions of caspase-12 after cerebral ischemia-reperfusion in rats - Hong Zhang; Li-Chun Song; Chun-Hong Jia; Yong-Li Lu (Neuroscience Bulletin, 2008)

Molecular cloning, characterization and expression of two rapeseed (Brassica napus L.) cDNAs orthologous to Arabidopsis thaliana phenylalanine ammonia-lyase 1 - Yu Ni; Hong-Lin Jiang; Bo Lei; Jia-Na Li; You-Rong Chai (Euphytica, 2008)

Generation of superoxide from reaction of 3H-1,2-dithiole-3-thione with thiols: implications for dithiolethione chemoprotection - Zhenquan Jia; Hong Zhu; Michael A. Trush; Hara P. Misra; Yunbo Li (Molecular and Cellular Biochemistry, 2007)

The Highly Expressed and Inducible Endogenous NAD(P)H:quinone Oxidoreductase 1 in Cardiovascular Cells Acts as a Potential Superoxide Scavenger - Hong Zhu; Zhenquan Jia; James E. Mahaney; David Ross; Hara P. Misra; Michael A. Trush; Yunbo Li (Cardiovascular Toxicology, 2007)

A follow-up study of mortality among the arseniasis patients exposed to indoor combustion of high arsenic coal in Southwest Guizhou Autonomous Prefecture, China - Ji-gang Chen; Yu-gang Chen; Yun-shu Zhou; Guo-fang Lin; Xiu-jie Li; Chao-gang Jia; Wei-chao Guo; Hui Du; Hong-chao Lu; Hong Meng; Xin-jiang Zhang; Klaus Golka; et al. (International Archives of Occupational and Environmental Health, 2007)

Solid Substrate-Room Temperature Phosphorescence Method for the Determination of Trace Mn(II) Based on Oxidizing Reaction of Hydrogen Peroxide Using α,α′-Bipyridine as Sensitizer - Jia-Ming Liu; Xiao-Jie Cui; Fei Gao; Lai-Ming Li; Xiu-Chai Huang; Min-Lan Yang; Fei-Ming Li; Hong Wu (Journal of Fluorescence, 2006)

Genetic diversity within Oryza rufipogon germplasms preserved in Chinese field gene banks of wild rice as revealed by microsatellite markers - Li-Zhi Gao; Chi-Hong Zhang; Dao-Yuan Li; Da-Jian Pan; Ji-Zeng Jia; Yu-Shen Dong (Biodiversity and Conservation, 2006)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Effects of Biological Soil Crusts on Seed Bank, Germination and Establishment of Two Annual Plant Species in the Tengger Desert (N China) - Xin-Rong Li; Xiao-Hong Jia; Li-Qun Long; Stefan Zerbe (Plant and Soil, 2005)

Activation of the WUS Gene Induces Ectopic Initiation of Floral Meristems on Mature Stem Surface in Arabidopsis thaliana - Yun-Yuan Xu; Xiao-Min Wang; Jia Li; Ju-Hua Li; Jin-Song Wu; John C. Walker; Zhi-Hong Xu; Kang Chong (Plant Molecular Biology, 2005)

Activation of the WUS gene induces ectopic initiation of floral meristems on mature stem surface in Arabidopsis thaliana - Yun-Yuan Xu; Xiao-Min Wang; Jia Li; Jun-Hua Li; Jin-Song Wu; John C. Walker; Zhi-Hong Xu; Kang Chong (Plant Molecular Biology, 2005)

Frequent loss of membranous E-cadherin in gastric cancers: A cross-talk with Wnt in determining the fate of β-catenin - Xiao-Xin Cheng; Zi-Chuang Wang; Xiao-Yan Chen; Yuan Sun; Qing-You Kong; Jia Liu; Xue Gao; Hong-Wei Guan; Hong Li (Clinical & Experimental Metastasis, 2005)

Relations of the type and branch of surface N-glycans to cell adhesion, migration and integrin expressions - Ying Zhang; Jia-hong Zhao; Xia-ying Zhang; Hua-bei Guo; Fei Liu; Hui-li Chen (Molecular and Cellular Biochemistry, 2004)

A deletion mutation in the ?A1/A3 crystallin gene (CRYBA1/A3) is associated with autosomal dominant congenital nuclear cataract in a Chinese family - Yanhua Qi; Hongyan Jia; Shangzhi Huang; Hui Lin; Jingzhi Gu; Hong Su; Tieying Zhang; Ya Gao; Lijun Qu; Dandan Li; Ying Li (Human Genetics, 2004)

Molecular cloning and characterization of betaine aldehyde dehydrogenase gene from Suaeda liaotungensis and its use in improved tolerance to salinity in transgenic tobacco - Qiu-Li Li; Xiao-Rong Gao; Xiao-Hong Yu; Xing-Zhi Wang; Li-Jia An (Biotechnology Letters, 2003)

Identification of estrogen-responsive genes in chick liver - Yunfeng Zhu; Mei Wang; Hong Lin; Zheng Li; Jia Luo (Cell and Tissue Research, 2001)